Optimization and Evaluation of Aceclofenac Loaded Solid Lipid Nanoparticles via Response Surface Methodology - Khadija Saleem; Nariman Shahid; Badarqa Tul Ayesha; Alia Erum; Amna Wajdan; Kashif Barkat; Ume Ruqia Tulain; Muhammad Umer Ashraf; Sana Hanif (Journal of Pharmaceutical Innovation, 2027)

Pesticide residue profiles, dietary risk assessment, and mitigation strategies in citrus production systems of Pakistan - Muneer Abbas; Akbar Hayat; Sohaib Afzaal; Muhammad Ghayoor Husnain; Hira Tariq; Fiaz Hussain; Niaz Hussain; Muhammad Saleem; Dilbar Hussain; Aleena Alam; Wang Dongze; Sohail Abbas (Food Control, 2026)

High prevalence of ESBL encoding genes in enterobacterales isolated from hospital and environmental wastewater in Pakistan- One Health challenge - Muhammad Usman Qamar; Muhammad Rizwan; Fatima Tuz Zahra; Faiqa Arshad; Asma Ejaz; Aatika; Sana Rehman; Zikria Saleem (Molecular Biology Reports, 2026)

Celastrol at the obesity–cancer interface: critical appraisal of molecular mechanisms, preclinical evidence, and translational barriers - Asma B. Omer; Muhammad Afzal; Shakir Saleem; Mohd Masih Uzzaman Khan; A. Rekha; Rajat Sharma (Molecular Biology Reports, 2026)

Multivariate analysis highlights genetic structure in Olive (Olea Europaea L.) germplasm using Resource-Efficient RAPD marker system - Ayesha Wadood; Amjad Hameed; Muhammad Yussouf Saleem; Abdul Rehman Khan; Saba Akram (Molecular Biology Reports, 2026)

Exogenous dopamine alleviates chilling injury of sapodilla (Manilkara zapota) fruit by modulating reactive oxygen species and ascorbate-glutathione cycle activities - Sajid Ali; Syed Muhammad Kashan Haider; Safina Naz; Hafiz Umer Javed; Aamir Nawaz; Shaghef Ejaz; Muhammad Shahzad Saleem (Postharvest Biology and Technology, 2026)

Geophysical and remote sensing insights into tectonics and mineralization of Hattian, Azad Jammu and Kashmir - Shahid Ahmed; Muhammad Rustam Khan; Fahad Hameed; Muhammad Saleem Mughal; Khawaja Umair Majeed; Junaid Yousif (Journal of Applied Geophysics, 2026)

Next-generation hybrid membranes integrating MXene and MOF architectures for energy-efficient water treatment - Saleem Raza; Luqman Ali; Muhammad Usman Hameed; Sidra Khalid; Sundas Shoukat; Mamuna Ahmad; Liguo Shen; Ghafar Ali; Imran Shakir (Desalination, 2026)

Multi-model drought index for Pakistan's croplands: A data fusion framework and comparative performance analysis - Akash Hussain; Wenting Han; Muhammad Amjad Saleem; Mubashir Ali Ghaffar; Mohsin Ijaz; Wajahat Waseem; Mahmood Hemat; Atiyyah Rafaqat (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Recent advances in electrochemical ion separation: Materials, mechanisms and sustainable applications for water and resource recovery - Luqman Ali; Abdul Majid Khan; Muhammad Usman Hameed; Saleem Raza; Liguo Shen; Imran Shakir; Muhammad Hafeez (Desalination, 2026)

Investigational Studies of Mn/Ag/Graphene@PANI Quaternary Composite for Ni(II) Removal Efficiency - Muhammad Saleem; Aamir Rasheed; Aneeqa Surkhab; Mahnoor Shireen; Rana Hamza Zafar (Water, Air, & Soil Pollution, 2026)

Corrigendum to “TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy” [J Hazard Mater 494 (2025) 138515] - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2026)

Retraction notice to “Polyvinyl alcohol and aminated cellulose nanocrystal membranes with improved interfacial compatibility for environmental applications” [Environ. Res. 214 (2022) 113793] - Saleem Ahmad; Zaib Jahan; Farooq Sher; Muhammad Bilal Khan Niazi; Tayyaba Noor; Honghao Hou; Ofaira Azhar; Emina Karahmet Sher (Environmental Research, 2026)

Structure–network–function engineering of carrageenan edible film for food packaging: A comprehensive review of blend design, nanocomposite architectures and active/intelligent application performance - Fatima Shehzadi; Hafiz Muhammad Jawad Saleem; Gholamreza Abdi (Carbohydrate Polymers, 2026)

Towards Safer Antimicrobial Peptide Therapeutics: A Predictive–Generative Framework Targeting ESKAPE Pathogens - Zubia Rashid; Hania Ahmed; Kashif Saleem; Muhammad Razi Uddin Siddiqui (Probiotics and Antimicrobial Proteins, 2026)

Bifurcation and chaos design of radial basis neural network for predictive modeling of fractional double-strain HIV co-infection model with intercellular delays and stochastic effects - Muhammad Wajahat Anjum; Noreen Sher Akbar; M. Bilal Habib; A. Alzubaidi; S. Saleem (Theory in Biosciences, 2026)

Effect of ambient pressure on microwave-enhanced laser-induced plasma: Influence on signal stability and intensity at different laser energies - Seher Saleem; Muhammad Rizwan; Zongyu Hou; Zhe Wang (Analytica Chimica Acta, 2026)

Antibiofilm efficacy and genomic characterization of a lytic bacteriophage targeting MDR uropathogenic Escherichia coli - Muhammad Hassan; Iqbal Ahmad Alvi; Sadiq Noor Khan; Dawood Ahmed; Muhammad Asif; Afshan Saleem; Abdul Jabbar (Archives of Microbiology, 2026)

Dopamine Receptor D2 gene Polymorphisms rs2005313, rs4274224, and rs4938019 in Pakistani Patients with Schizophrenia:a Diagnostic Tool for Schizophrenia - Ishrat Yaseen; Saleem Ahmad; Muhammad Ghalib; Muhammad Shahbaz Aslam; Rabbia Tariq; Osheen Sajjad; Faisal Yaseen (Journal of Molecular Neuroscience, 2026)

Retraction notice to “Environmentally responsive and anti-bugs textile finishes – Recent trends, challenges, and future perspectives” [Sci. Total Environ. 690 (2019) 667–682] - Shahzad Ali Shahid Chatha; Muhammad Asgher; Rabbia Asgher; Abdullah Ijaz Hussain; Yasir Iqbal; Syed Makhdoom Hussain; Muhammad Bilal; Faizan Saleem; Hafiz M.N. Iqbal (Science of The Total Environment, 2026)

Recent developments in design and fabrication of ZIF-based materials for CO2 mitigation and environmental remediation - Hafsa Khalid; Aimon Saleem; Umer Younas; Parveen Akhter; Heena Ameen; Faisal Ali; M.I. Khan; Muhammad Pervaiz (Journal of Environmental Management, 2026)

An analysis of impact of soil co-pollution with lead and traditional/biodegradable microplastics on growth characteristics of maize (Zea mays L.) - Muhammad Kashif Irshad; Saba Saleem; Jamilur R. Ansari; Ali Noman; Muhammad Aqeel; Mohamed O. Alshahrani; Modhi O. Alotaibi; Muhammad Sohaib Irshad; Sang Soo Lee (Journal of Environmental Sciences, 2026)

Development and Performance Evaluation of an Indigenized Smart Field Lysimeter for Relative Crop Water-Use Assessment - Muhammad Faisal; Fiaz Hussain; Shoaib Rashid Saleem; Saliha Qamar (Water Conservation Science and Engineering, 2026)

Structure Guided Identification of Small Molecule Inhibitors Targeting Staphylococcus aureus α-Hemolysin - Saeed Ullah Khattak; Nida Raza; Mawahib Ahmed; Ayesha Saleem; Muhammad Salim; Sajjad Ahmad (Journal of Pharmaceutical Innovation, 2026)

Revolutionizing the potential of laccase from Bacillus paralicheniformis as an eco-friendly solution to reduce polychlorinated dibenzofurans contamination through integrated computational approach - Muhammad Naveed; Ayesha Saleem; Tariq Aziz; Urooj Rasheed; Arooj Azeem; Maryum Rasheed; Manal F. Elkhadragy; Ashwag Shami; Hanan Abdulrahman Sagini; Rewaa S. Jalal; Hayam A. Alwabsi; Fakhria A. Al-Joufi (Biodegradation, 2026)

Sulfur isotope composition of sulfides from the Chah-Firozeh porphyry Cu deposit, Iran: implications for magmatic sulfur sources - Johar Ali; Sina Asadi; Muhammad Saleem Mughal; George Kontakiotis; Assimina Antonarakou (Mediterranean Geoscience Reviews, 2026)

Deciphering the structural–functional dynamics of glucosyltransferases from novel Apilactobacillus isolates through in silico analysis - Hira Kiran; Munir A. Anwar; Waqar Ahmad; Iqra Jawad; Ayesha Siddiqa; Muhammad Imran; Moazur Rahman; Muhammad Saleem (Biologia, 2026)

Preclinical evaluation of silver-doped copper carbonate nanoparticles for antidiabetic and wound healing effects in mice - Muhammad Zahir Tahir; Ali Umar; Waseem Ul Ghafoor; Misbah Ullah Khan; Muhammad Saleem Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Multilevel barriers to antimicrobial stewardship in tertiary care hospitals: A comparative systematic scoping review of high-income versus low-/middle-income countries evidence mapped by study design and healthcare professionals - Azfar Athar Ishaqui; Zikria Saleem; Tauqeer Hussain Mallhi; Sultan M. Alshahrani; Khalid Orayj; Salman Ashfaq Ahmad; Rayah Asiri; Emad Ali Alsaleh; Muhammad Imran; Mohammed Ali Kaddoura; Bilal Jawed; Narendar Kumar; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Diosgenin-loaded niosomes ameliorate cadmium-induced neurotoxicity and endocrine disruption in female rats through modulation of oxidative stress, apoptosis, and inflammatory markers - Kanza Hashmi; Ammara Saleem; Shakila Sabir; Shahana Ehsan; Aisha Mobashar; Muhammad Imran khan; Shahnaz; Zulcaif Ahmad; Muhammad Furqan Akhtar; Musaab Dauelbait; Amir Bouallegue; Esmael M. Alyami; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Exploration of molecular mechanisms responsible for arthritis alleviating attributes of Calliandra haematocephala extracts - Inaam Ur Rehman; Taha Muhammad; Abir Abdullah Alamro; Eman Hassan Alshehri; Hamza Ahmad Odeibat; Rodney B. Luwor; Adrian A. Achuthan; Mohammad Saleem; Mohamed Farouk Elsadek (Inflammopharmacology, 2026)

The dynamic interaction between the semi-circular canyon and a nearby building with a rigid foundation surrounded by flexible bearing layers under incident SH waves - Nasir Abbas; Jebran Saleem; Zeeshan Haider; Darakshan Zahra; Muhammad Lawal Usman (Innovative Infrastructure Solutions, 2026)

Population fluctuations of wheat aphids (Hemiptera: Aphididae) in response to weather variations - Saba Naz; Tamseela Mumtaz; Dilbar Hussain; Muhammad Saleem; Zainab Tariq; Eman Arshad (International Journal of Tropical Insect Science, 2026)

Overcoming cellular secretion bottlenecks: advanced secretion engineering and molecular tailoring for next-generation microbial α-amylases with enhanced industrial performance - Saleem Ahmad; Muhammad Nauman Aftab; Muhammad Ghalib; Muhammad Shahbaz Aslam (World Journal of Microbiology and Biotechnology, 2026)

Design and development of a low-cost industrial prototype of spot-specific spraying system for potato weed detection using deep learning - Faiza Khan; Muhammad Naveed Tahir; Muhammad Aqib; Yubin Lan; Noureen Zafar; Shoaib Saleem; Zainab Haroon; Wenjiang Huang (Computers and Electronics in Agriculture, 2026)

Protein-lipid-carbohydrate interactions in flavor retention: Emerging insight from nonthermal technologies to advanced analytics - Abdul Mueed; Ateeq Ahmad; Muhammad Hussain Ghazali; Molan Zhang; Abdullah Ahmed Butt; Fizza Saleem; Lijun You (Trends in Food Science & Technology, 2026)

Provenance and fluvial-aeolian process of the late Pleistocene Houtian sand hills in Poyang Lake area, south China: Constrained by detrital zircon U–Pb geochronology - Dingding Du; Shuyuan Tian; Zhiwen Li; Jingjing Yu; Muhammad Saleem Mughal (Quaternary International, 2026)

Advances in functional carbon composites for electrochemical energy conversion and catalysis: Design strategies, mechanisms and future prospects - Luqman Ali; Muhammad Usman Hameed; Xingfen Huang; Saleem Raza; Abdul Majid Khan; Mashkoor Ahmad; Akif Safeen; Imran Shakir (Journal of Environmental Chemical Engineering, 2026)

Unlocking ketone dimerization efficiency with multifunctional Zr and Hf based UiO-66 and NUS-6 MOFs: A synergy of experiment and theory - Muhammad Kashif Majeed; Rashid Iqbal; M.Umar Majeed; Muhammad Akram; M.Zeeshan Ashfaq; Adil Saleem (Fuel, 2026)

Highly sensitive label-free SERS detection of okadaic acid using gold nanorods coupled with DFT and chemometrics - Muhammad Saleem; Md Mehedi Hassan; Muhammad Shoaib; Yi Xu; Quansheng Chen (Food Bioscience, 2026)

Sustainable valorization of recycled polypropylene waste in concrete composites via compression casting: Integrating lifecycle, cost, and engineering assessments for plastic waste management - Syed Minhaj Saleem Kazmi; Muhammad Junaid Munir; Yu-Fei Wu (Environmental Research, 2026)

Engineering hybrid hydrogels from sticker–spacer peptide and molybdenum disulfide (MoS2) for advanced antimicrobial therapy - Muhammad Younis; Farhat Rafiq; Shuo Jin; Mussarat Tasleem; Muhammad Saleem; Yongchang Tian; Li Chen; Mohammad Aslam; Dalaver H. Anjum; Jabir Ubaid; Rehan Umer; Xiaofei Chen; et al. (Chemical Engineering Journal, 2026)

Influence of thermal pretreatment on characteristic and anaerobic digestion of Sunflower meal - Asad Ayub Rajput; Zeshan; Muhammad Raheel Bawani; Saleem Raza Chalgri (Bioresource Technology Reports, 2026)

Plant viruses as next-generation vectors for transgene-free genome editing, gene regulation, and rapid crop improvement - Abdul Ali Azam; Muhammad Salman Iqbal; Huma Saleem; Revocatus Bahitwa; Hai Wang (Plant Molecular Biology, 2026)

Green-Synthesized Silver Nanoparticles Enhance Soybean Tolerance to Cadmium through Redox Regulation and Metabolic Reprogramming - Shifa Shaffique; Muhmmad Farooq; Muhmmad Saleem Khan; Ali Umar; Muhammad Aaqil Khan; Sang-Mo Kang; In-Jung Lee (Journal of Soil Science and Plant Nutrition, 2026)

Silicon Role in Improving Leaf Physiology, Yield and Quality of Rice (Oryza Sativa L.) Under High Temperature Stress - Rania Baloch; Muhammad Farrukh Saleem; Muhammad Awais Arshad; Abdul Rehman; Aqsa Baloch; Muhammad Sarwar; Muhammad Ashfaq Wahid (Journal of Soil Science and Plant Nutrition, 2026)

Paleocene stratigraphic framework and sedimentary architecture in the Sub-Himalayan Fold and Thrust Belt of Muzaffarabad, Pakistan: Depositional environment, Biotas, Paleogeographic and Economic Significance - Syed Kamran Ali; Arslan Sajjad; George Kontakiotis; Hammad Tariq Janjuhah; Muhammad Saleem Mughal; Ahmer Bilal; Aamir Asghar; Aijaz Ali Halepoto; Evangelia Besiou; Assimina Antonarakou (Journal of Sedimentary Environments, 2026)

Enhancing Farm Productivity and Sustainability Through Maize-Soybean Intercropping with Diverse Nitrogen Management - Rukhsar Saleem; Abdul Khaliq; Muhammad Zia Ul Haq; Muhammad Aamer Maqsood (International Journal of Plant Production, 2026)

Zaleya pentandra L. produces anti-arthritic effects by downregulating IL-6, NF-κB, and TNF-α and mitigating oxidative stress - Ayesha Shafi; Naureen Shehzadi; Khalid Hussain; Muhammad Saleem; Fatima Rasool; Mubashara Gul (Inflammopharmacology, 2026)

Geochemical and petrographic insights into the Lumshiwal Formation (NW Himalayas): implications for provenance, paleoclimate, and economic potential - Syed Nohman Gilani; Muhammad Saleem Mughal; Khawaja Umair Majeed; Hammad Tariq Janjuhah; Yongzhi Wang; Muhammad Atif Bilal; Ahmer Bilal; Syed Wajee-Ul Hassan Gillani; Muhammad Hafeez (Carbonates and Evaporites, 2026)

Disruption of lipid metabolism under plastic siege: Unraveling the toxic mechanisms of microplastics and nanoplastics - Muhammad Furqan Akhtar; Ammara Saleem (Toxicology and Environmental Health Sciences, 2026)

Modeling synaptic dynamics in neurons via soliton solutions of fractional and stochastic coupled Konno–Oono systems - Musarat Bibi; Salah Mahmoud Boulaaras; Muhammad Shoaib Saleem (Theory in Biosciences, 2026)

Multi-scale meteorological and hydrological drought severity in a high-altitude Himalayan basin: An intensity–duration–frequency approach using SPI and SSI (1970–2016) - Nuaman Ejaz; Muhammad Rashid; Muhammad Waqar Saleem; Amro Elfeki; Songhao Shang (Journal of Mountain Science, 2026)

Foliar application of silicon alleviates adverse effect of drought stress by improving growth, physiological attributes, and antioxidant defense of camelina (Camelina sativa L.) - Bilal Ahmad Shahzad; Ejaz Ahmad Waraich; Muhammad Saleem; Saddam Hussain; Saifullah (Acta Physiologiae Plantarum, 2026)

Enhanced Antimicrobial Photodynamic Effect Against Escherichia coli Using MXene-Based Silver–Curcumin 2D Nanocomposite Photosensitizers - Saliha Noor; Shahzad Anwar; Rafaqat Ali Khan; Sawera Malik; Hina Ali; Farwa Nurjis; Shaista Taimur; Muhammad Iftikhar; Muhammad Saleem; Babar Manzoor Atta (Journal of Fluorescence, 2026)

Nutritional and phytochemical profiling of Solanum melongena L. root extract using LC-ESI-MS/MS; In-silico and biological evaluation - Asad Saleem Sial; Muhammad Mohtasheemul-Hasan; Khizar Abbas; Rizwana Manzoor; Usman Javaid; Syed Zia Ul Hasnain; Adnan Amin (South African Journal of Botany, 2026)

Evaluation and progression of marine heatwaves over the northwestern Indian Ocean: A comparative study using satellite and numerical model data - Akurathi Venkata Sai Chaitanya; Abdul Azeez Saleem; Muhammad Shafeeque; Salim Lateef; Mohamed Asharaf; Jiya Albert (Regional Studies in Marine Science, 2026)

Cobalt nanostructures induced hematotoxicity and renal toxicity in albino mice: an experimental and computational evaluation - Ali Umar; Muhammad Saleem Khan; Muhammad Wajid (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Biochemical and Yield Response of Rice (Oryza sativa L.) to Exogenous Application of Glutathione Under High Temperature Stress at Flowering Stage - Rania Baloch; Muhammad Farrukh Saleem; Muhammad Sarwar; Muhammad Awais Arshad; Muhammad Aown Sammar Raza; Aqsa Baloch; Amina Rashid (Journal of Plant Growth Regulation, 2026)

Amelioration of experimentally induced-arthritis by guaiazulene through targeting inflammatory and oxidative stress biomarkers in Wistar rat - Ammara Saleem; Arooj Fatima; Muhammad Furqan Akhtar (Inflammopharmacology, 2026)

Dichlorvos toxicity on hemato-biochemical, histopathological, and behavioral parameters in the grass carp (Ctenopharyngodon idella) - Mehvish Saleem; Cristiana Roberta Multisanti; Sana Ullah; Wardah Fazal; Muhammad Sohail; Muhammad Bilal; Muhammad Kashif Ashraf; Caterina Faggio (Ecotoxicology, 2026)

Optimized identification of glacial lake outburst flood hazard using multi-criteria decision analysis - Aniqa Murtaza; Muhammad Waqar Saleem; Hamza Farooq Gabriel; Khalil Ur Rahman; Zafar Iqbal; Deqiang Mao (Hydrological Sciences Journal, 2026)

Data-driven explainable artificial intelligence models for predicting CO2 uptake in metal–organic frameworks - Mohd Azfar Shaida; Laiba Saleem; Syed Ali Waqas Ahmad; Saad Shamim Ansari; Syed Muhammad Ibrahim (Environmental Science and Pollution Research, 2026)

Trends in emerging analytical strategies for okadaic acid detection in aquatic food commodities - Muhammad Saleem; Md Mehedi Hassan; Waqas Ahmad; Liang Tian; Muhammad Fahad Khan; Faiz-ul-Hassan Shah; Yi Xu; Quansheng Chen (Trends in Food Science & Technology, 2026)

Efficient solar-driven decontamination of waterborne antibiotics and dyes via 2D/2D/2D heterointerface engineering and S-scheme charge transfer in a Ti3C2 MXene/BiOIO3/g-C3N4 ternary heterostructure - Ganesh Koyyada; Anam Giridhar Babu; Abdullah A. AI-Kathani; Muhammad Imran Saleem; Jae Hong Kim (Journal of Water Process Engineering, 2026)

Facile and Low Cost Synthesis of NiFe-LDH/ZnO Composites for Efficient Photodegradation of MB in Aqueous Solution Under the Illumination of Natural Sunlight - Ramsha Saleem; Humera Shaikh; Muhammad Saajan Barhaam; Qurban Ali Shah; Baradi Waryani; Mazhar Ali Abbasi; Imran Ali Halepoto; Nek Muhammad Shaikh; Muhammad Ali Bhatti; Rafat M. Ibrahim; Elmuez Dawi; Aneela Tahira; et al. (Water, Air, & Soil Pollution, 2026)

Unlocking the Functional Dynamics of ERF013 in Arabidopsis thaliana: A Key Player in Plant Growth Regulation - Rahmatullah Jan; Lubna; Saleem Asif; Zakirullah Khan; Muhammad Farooq; Eman R. Elsharkawy; Sajjad Asaf; Kyung-Min Kim (Journal of Plant Growth Regulation, 2026)

Physicochemical Characterization and Molecular Docking of Salicylic Acid-Binding Protein 2 (SABP2) Suggest Drought-Responsive Mechanisms in Tobacco - Mirza Muhammad Ahad Baig; Sarmad Farogh Arshad; Muhammad Asif Saleem; Abdulsmad Baig; Muhammad Mudasir; Zeeshan Ahmad; Taimoor Ali; Abdul Rehman (Journal of Crop Health, 2026)

Retraction Note: Assessment of genetic diversity in cotton genotypes using simple sequence repeat (SSR) markers: insights from interspecific and intraspecific variations - Muhammad Arslan; Akash Fatima; Fatima Javeria; Sehrish Ijaz; Umair Riaz; Gulnaz Saleem; Mounir M. Bekhit; Milad A. Mezher; Rashid Iqbal (Genetic Resources and Crop Evolution, 2026)

Myoinositol-mediated regulation of leaf physiology, biochemistry, and water relations confers heat stress tolerance in Quinoa - Rashid Iqbal; Muhammad Sarwar; Basharat Ali; Muhammad Farrukh Saleem; Hassaan Ahmad; Muhammad Shahid; Javed Iqbal; Khairiah Mubarak Alwutayd; Dilfuza Jabborova; Sajad Ali; Ghulam Murtaza (Plant Biosystems, 2026)

Harnessing novel biosynthesized ZrO₂ biochar nanocomposites for reactive orange 16 dye adsorption: kinetic modeling and cytotoxicity insights - Mubashara Fayyaz; Mohamed A. Habib; Syed Kashif Ali; Saif Ullah; Muhammad Imran Kanjal; Tahreem Saleem; Rana Muhammad Zulqarnain; Ahmed B. M. Ibrahim (Biodegradation, 2026)

Exploring the biocatalytic potential of Amycolatopsis japonica DyP in degrading plasticizer and phenolic-derived xenobiotic compounds - Muhammad Naveed; Ayesha Saleem; Tariq Aziz; Sadia Jabeen; Sana Miraj Khan; Maida Salah Ud Din; Nantenaina Tombozara; Mayasar I. Al-zaban; Ashwag Shami; Hayam A. Alwabsi (Biodegradation, 2026)

Molecular Characterization of Oculocutaneous Albinism in Consanguineous Pakistani Families: Unraveling Disease-Causing Pathogenic Variants in OCA2 and TYR Genes for Precision Diagnosis - Haiba Kaul; Shagufta Naz; Hafiz Ishfaq Ahmad; Nameerah Saleem; Muhammad Shakil; Sabika Firasat; Bilal Majeed; Saima Sharif; Farzana Rashid; Abdullah Etezaz; Muhammad Umer Khan (Biochemical Genetics, 2026)

Exploiting endogenous Protoporphyrin IX for Photodynamic inactivation of Pseudomonas aeruginosa - Muhammad Bilal; Rabia Anjum; Sana Imtiaz; Muhammad Saleem (Journal of Fluorescence, 2026)

Augmenting solar irradiance forecasting through novel hybrid models leveraging multistage feature extraction - Snoober Saleem; Muhammad Sibtain; Xianshan Li; Qurat-ul-Ain; Qiang Shi; Fei Li; Halit Apaydin (Theoretical and Applied Climatology, 2026)

Chitosan Mitigates Heat Stress in BT Cotton by Activating Antioxidant Defense System and Improving Water Relations - Abdul Shakoor; Muhammad Farrukh Saleem; Muhammad Zia Ul Haq; Muhammad Shahbaz Farooq; Muhammad Shahid (International Journal of Plant Production, 2026)

Retraction Note: Esculin-loaded nanoparticles ameliorate adjuvant-induced polyarthritis via subduing inflammatory and oxidative stress biomarkers in Wistar rats - Mehak Fatima; Ammara Saleem; Muhammad Furqan Akhtar; Kanwal Akhtar; Muhammad Imran Khan (Inflammopharmacology, 2026)

Glutathione role in improving leaf physiology, yield and quality of rice (Oryza sativa L.) under high temperature stress at flowering stage - Rania Baloch; Muhammad Farrukh Saleem; Muhammad Sarwar; Muhammad Awais Arshad; Muhammad Shahid; Amina Rashid (Cereal Research Communications, 2026)

Hydrogeochemical dynamics of sub-Himalayan springs: assessing health risks and environmental impacts in Muzaffarabad, Pakistan - Mansoor Awan; Abrar Niaz; Ahmer Bilal; Muhammad Saleem Mughal; Li Yang; Xingyue Qu; Ali Yousaf Khan (Carbonates and Evaporites, 2026)

Experimental and computational evaluation of dinaphthodiospyrol F and dinaphthodiospyrol G from Diospyros lotus L. as ectonucleotide pyrophosphatase/phosphodiesterase 1 (ENPP1) inhibitors - Abdur Rauf; Yahya S. Al-Awthan; Omar S. Bahattab; Muhammad Saleem; Zuneera Akram; Giovanni Ribaudo (Natural Product Research, 2026)

Genome-wide identification, functions, and expression analysis of carbonic anhydrase gene family in the gills of O. niloticus under salinity stress - Ahmad Waheed; Samra Farooq; Jabbir Ali Khan; Imran Ahmad Khan; Samra Shafqat; Hina Naz; Muhammad Saleem Khan; Muhammad Wajid (Aquaculture, 2026)

The transformative role of artificial intelligence in water resources engineering: A comprehensive review - Muhammad Rashid; Adan Saeed; Mohiq Khalid; Aniqa Murtaza; Muhammad Waqar Saleem (Environmental Modelling & Software, 2026)

Recent advancements in SERS strategies for biotoxin detection in different food matrices - Muhammad Saleem; Md Mehedi Hassan; Waqas Ahmad; Tianhui Jiao; Afang Zhu; Xinying Wang; Yi Xu; Quansheng Chen (Chemical Engineering Journal, 2026)

Evaluation of climate change and land-use impacts on groundwater dynamics in the bari doab canal system - Saif Haider; Muhammad Rashid; Jawad Saleem (Theoretical and Applied Climatology, 2026)
Globally, groundwater depletion has grown to be a serious issue, as land and water resources have been gravely exhausted due to the rising population's desire for food and water. The current research evaluated the decline in groundwater caused by land use and climate change in the Bari Doab Canal, Pakistan, utilizing the latest Coupled Model Intercomparison Project (CMIP6) of the global climate model (GCM). Sixteen years of data (2005–2020) from the Punjab Irrigation Department were used to generate IDW interpolation maps within the ArcGIS environment. The Penman–Monteith equation in the CROPWAT model was used to calculate crop water requirements. Cellular Automata Markov Chain model was used to create LULC maps of 2030, 2060, and 2100 by analyzing the changes based on Landsat (7 and 8) satellite imagery gathered in 2000, 2010, and 2020. Groundwater extraction was estimated through the deficit of effective rainfall and net canal water use from evapotranspiration after compensating for soil moisture storage changes. GCM projected rainfall and temperature under two Shared Socioeconomic Pathways (SSPs), SSP2 and SSP5, were downscaled using the CMhyd model till the end of the twenty-first century. The precipitation, maximum and minimum temperatures, and crop water requirements were anticipated to increase by downscaled projections of a selected model (MPI-ESM1-2-HR) till the end of the twenty-first century (2015–2100) compared to the baseline period (1981–2020). The water table dropped by 0.62 m annually over 16 years (2005–2020). Urbanization increased steadily from 2000 to 2100, while all other categories, water, dense vegetation, vegetation, and barren land experienced a decline. The Visual MODFLOW model outcomes demonstrated the detrimental effects of the expected changes in land use and climate on the groundwater in Bari Doab. This study supports the development of appropriate adaptation measures by policymakers and stakeholders to mitigate the detrimental impacts of climate and land use change on groundwater dynamics.

Curative potential of resveratrol and pterostilbene against epoxy resin–induced reproductive toxicity in female rats - Sidra Malik; Ammara Saleem; Qurat-Ul-Ain; Muhammad Imran Khan; Zulcaif Ahmad; Syeda Momna Ishtiaq; Muhammad Furqan Akhtar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Drimiopsis maculata methanol extract attenuates inflammation in experimental rat model of polyarthritis: a biochemical and molecular insight - Malik Saadullah; Farwa Tahir; Maryam Farrukh; Samina Afzal; Rabia Munir; Usman Ashraf; Uzma Saleem; Muhammad Ajmal Shah; Ibrahim Aljaezi; Ana Sanchez Silva; Norah K. Algarzae; Musaad Bedah Alsahly (Inflammopharmacology, 2026)

Formulation and characterization of escin loaded-chitosan nanoparticles and assessment of its anti-arthritic potential in Wistar rats: a mechanistic approach - Ayesha Riaz; Ammara Saleem; Muhammad Furqan Akhtar (Inflammopharmacology, 2026)

In silico characterization and molecular docking of the MIOX gene in Nile tilapia (Oreochromis niloticus) - Samra Farooq; Samra Shafqat; Jabbir Ali Khan; Ahmad Waheed; Ali Umar; Muhammad Saleem Khan (Fish Physiology and Biochemistry, 2026)

Zinc-regulated growth, chlorophyll, and antioxidant activity drive biofortification in rice varieties - Hafiza Ammara; Asma Zulfiqar; Ammara Saleem; Rehana Sardar; Usman Zulfiqar; Muhammad Aown Sammar Raza; Muhammad Faisal Maqsood; Hossam S. El-Beltagi; Mashael Daghash Alqahtani (BioMetals, 2026)

Status of insecticide resistance in Spodoptera litura (Lepidoptera: Noctuidae) on cauliflower, Punjab, Pakistan - Dilbar Hussain; Muhammad Sohail Qadir; Muhammad Asrar; Muhammad Saleem; Usama Saleem; Zeeshan Javed; Kanwal Hanif; Arshed Makhdoom Sabir; Ijaz Haider; Muhammad Jawad Saleem; Muhammad Bilal Bin Iqbal (International Journal of Tropical Insect Science, 2026)

Mechanistic insights into the synergistic pharmacology of quercetin–kaempferol against SARS-CoV-2 infection - Farman Ali; Muhammad Zubair Saleem; Muhammad Mohsin; Saleem Ahmad; Waqar Islam; Wasim Qasim; Muhammad Tayyab (In Silico Pharmacology, 2026)

Synergistic effects of biochar and silicon dioxide nanoparticles abate cadmium uptake and oxidative stress in tomato: Achieving crop resilience and environmental sustainability - Muhammad Kashif Irshad; Muhammad Waseem; Saba Saleem; Jamilur R. Ansari; Sana Ashraf; Wasim Javed; Ali Noman; Muhammad Aqeel; Muhammad Rizwan; Afrah E. Mohammed; Modhi O. Alotaibi; Muhammad Rizwan; et al. (Plant Science, 2026)

Activated Solanum tuberosum peel and its magnetic iron oxide nanocomposites as efficient adsorbents for the removal of Eriochrome Black-T from aqueous solutions - Basit Ali; Sayyar Muhammad; Saleem Nawaz (Journal of Water Process Engineering, 2026)

Dual photo/electrocatalytic CO2 reduction by porphyrin based metal organic framework under visible light and electrochemical bias - Mamuna Aslam; Uzma Saleem; Ibrahim A. Shaaban; Tahani Rahil Aldhafeeri; Ataf Ali Altaf; Muzammil Iqbal; Muhammad Tariq; Mohammed A. Assiri; Shahid Hussain; Hafiz Muhammad Asif (Fuel, 2026)

Intensification of plasma process for the decomposition of p-xylene as a tar model compound to minimize the unwanted byproduct formation - Faisal Saleem; Muhammad Farooq; Azam Saeed; Shehzad Mustafa; Zaeem Bin Babar; Abdul Rehman; Syed Waqas Ahmad; Kui zhang; Adam Harvey (Fuel, 2026)

Sediment transport modeling of trenching activities: a case study for the Safaniya coastal waters in the Arabian Gulf - Abdul Azeez Saleem; Akurathi V. S. Chaitanya; Salim Lateef; Jiya Albert; Muhammad Shafeeque; Karuppasamy P. Manikandan; Thadickal V. Joydas; Mohamed Asharaf; Luai M Alhems; Ali M. Qasem; Sabique Langodan; Diego Lozano-Cortés (Ocean Dynamics, 2026)

Environmental resistomes and antimicrobial resistance: integrating the One Health framework - Kainat Raziq; Ramish Saleem; Saba Zafar; Tayyaba Sanaullah; Muhammad Muzammil Nazir; Umm E. Ummara; Asim Abbasi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Ameliorating effect of veratric acid against mercury-induced neurologic deficit and reproductive toxicity in female rats - Saira Saeed; Qurat-Ul-Ain; Ammara Saleem; Muhammad Imran Khan; Kanwal Akhtar; Aslam Khan; Muhammad Furqan Akhtar; Amir Bouallegue; Mohammed Bourhia; Sultan F. Kadasah (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Investigating the Wound Healing Potential of CuCO3 Nanoparticles in Alloxan-Induced Diabetic Albino Mice: An Experimental and In Silico Approach - Muhammad Saqib Rafiq; Jabbir Ali Khan; Ashfaq Ahmad Shah Bukhari; Samra Shafqat; Ahmad Waheed; Muhammad Yasir Abbas; Muhammad Waseem Aslam; Imran Ibrahim Shaikh; Khalid S. Almaary; Muhammad Saleem Khan (Biological Trace Element Research, 2025)

Halotolerant PGPRs attenuate salinity stress in maize through differential expression of stress-related genes and regulated Na+/K+ homeostasis - Tahira Yasmeen; Muhammad Saleem Arif; Aqeel Ahmad; Muhammad Usman; Mohsin Tariq; Waqas Haider; Afira Syrish (South African Journal of Botany, 2025)

Seismically induced soft-sediment deformation in alluvial fans: mechanisms and implications for geological evolution of the Ordos Basin (China) - Ahmer Bilal; Renchao Yang; Shaojie Chen; Nils Lenhardt; Muhammad Saleem Mughal; George Kontakiotis (Journal of Asian Earth Sciences, 2025)

Effect of dietary proteins on mayonnaise techno-functionality and rheology: A review - Wahab Ali Khan; Muhammad Waseem; Iqra Yasmin; Syed Abdul Wadood; Aiza Qamar; Muhammad Rizwan Javed; Muhammad Saleem; Crossby Osei Tutu (Food and Humanity, 2025)

Engineered TM(3d)-O(2p)-RE(4f) gradient orbital with coupled adsorption evolution and lattice oxygen mechanism towards robust oxygen evolution - Yiting Hao; Zhentao Yang; Mei Liu; Kai Zhang; Hongyu Wang; Muhammad Hassaan Saleem; Guihua Liu; Xiaohang Du; Jingde Li (Chemical Engineering Journal, 2025)

Synergistic Sustainable Strategies for Microplastic Pollution Eradication by Hedgehog − Shaped Polyoxometalate − Ionic Liquids Supported Magnetic Biochar - Hameed Ullah; Tahani Rahil Aldhafeeri; Inas A. Ahmed; Khurram Shahzad Munawar; Shahid Hussain; Nadeem Nawaz; Uzma Saleem; Muhammad Sohail; Hafiz Muhammad Asif (Water, Air, & Soil Pollution, 2025)

Correction: Sepsis-related immune signature C3 in endometrial carcinoma: implications for prognosis, tumor progression through bioinformatics and experimental validation - Kulsoom; Wajahat Ali; Saleem Ahmad; Irfan Ali Khan; Tanveen Kaur Soni; Asia Masood; Muhammad Omer Iqbal; Valisher Sapayev Odilbek uglu; Mukhayya Xusinovna Djumaniyazova; Anas Sameed Cholavaram; Mubaraq Arisekola Abdulrahmon (Molecular Biology Reports, 2025)

Sepsis-related immune signature C3 in endometrial carcinoma: implications for prognosis, tumor progression through bioinformatics and experimental validation - Kulsoom; Wajahat Ali; Saleem Ahmad; Irfan Ali Khan; Tanveen Kaur Soni; Asia Masood; Muhammad Omer Iqbal; Valisher Sapayev Odilbek uglu; Mukhayya Xusinovna Djumaniyazova; Anas Sameed Cholavaram; Mubaraq Arisekola Abdulrahmon (Molecular Biology Reports, 2025)

Manure-enriched Acidic Phosphate Fertilizer Improves Paddy Yield Over the Conventional Phosphate Fertilizers on a Calcisol - Ayesha Siddique; Muhammad Akhtar; Muhammad Saleem; Tahir Hussain Awan; Asif Naeem (Journal of Soil Science and Plant Nutrition, 2025)

Rosa moschata leaf extract modulates complete freund’s adjuvant-induced polyarthritis in Wistar rats via regulation of pro-inflammatory and inflammatory biomarkers - Amr S. Abouzied; Uzma Saleem; Maryam Farrukh; Umme Farwa; Areej M. Alsolami; Fatima A. Jaber; Tourki A. S. Baokbah; Ibrahim Aljaezi; Nouf Abdullah Alharbi; Muhammad Ajmal Shah; Ana Sanchez Silva; Norah K. Algarzae (Inflammopharmacology, 2025)

Mechanistic insight into inflammatory and oxidative stress ameliorating attributes of Atriplex crassifolia 70% ethanol extract against complete Freund’s adjuvant-induced arthritis - Jawaria Khurshid; Anam Iftikhar; Hamza Ahmad Odeibat; Eman Hassan Alshehri; Kiran Aslam; Maria Jaleel; Aymun Jawed; Muhammad Khalid Saeed; Rodney Luwor; Taha Muhammad; Mohammad Saleem; Mohamed Farouk Elsadek (Inflammopharmacology, 2025)

Sedimentology and biostratigraphy of the Cretaceous–Paleocene successions in Northern Pakistan: evidence from the Hazara, Kala Chitta, Potwar, and Kohat Basins - Syed Kamran Ali; Hafiz Sohaib Bashir; Asim Qadir; Muhammad Saleem Mughal; Khurram Iqbal; Abrar Niaz; Khawaja Umair Majeed (Carbonates and Evaporites, 2025)

Dolomitized stromatolites during regressive-transgressive cycles in the Cambrian Abbottabad Formation, Pakistan: depositional environment, sequence stratigraphic significance, and paleogeographic implications - Syed Kamran Ali; George Kontakiotis; Tariq Mahmood; Muhammad Saleem Mughal; Hammad Tariq Janjuhah; Ahmer Bilal; Evangelia Besiou; Assimina Antonarakou (Carbonates and Evaporites, 2025)

Chlorophyll-a modulation in the Arabian Gulf using two decades of merged ocean-color data - Muhammad Shafeeque; Abdul Azeez Saleem; Akurathi V. S. Chaitanya; C. P. Abdulla; Salim Lateef; Jiya Albert (Frontiers in Marine Science, 2025)
Introduction The Arabian Gulf (Gulf) is a dynamic marine ecosystem in which phytoplankton productivity, indicated by Chlorophyll- a (Chl- a ), is strongly affected by environmental and climatic variables. Understanding the spatiotemporal variability of Chl- a and its driving environmental factors is critical for assessing primary productivity and ecosystem dynamics of the Gulf. Methods This study investigated the long-term Chl- a variability and its dynamic response to environmental variables in the Gulf using two decades (2003 to 2023) of Chl- a data from merged multi-sensor Ocean Colour Climate Change Initiative. We adopted an integrated approach that includes climatology, multivariate statistical analysis, interannual variability and trend analysis to evaluate Chl- a variability and identify its dominant drivers. Results Seasonal climatology exhibited a marked winter bloom driven by convective mixing and nutrient replenishment, followed by a summer decline due to strong stratification. Box average analysis using correlogram and principal component analysis for selected regions revealed distinct regional patterns, with the northern and central Gulf showing higher variability. The results further highlighted sea surface temperature (SST), sea surface salinity, photosynthetically available radiation and wind speed as primary drivers of Chl- a variability in the Gulf. The interannual variability of Chl- a peaks along the central eastern Gulf in winter and central western Gulf during summer, highlighting regional heterogeneity in phytoplankton dynamics. Long-term spatial trend analysis of Chl- a , net primary productivity (NPP) and SST indicated overall decreasing trend in Chl- a and NPP, particularly along the north and eastern coasts of the Gulf; and warming SST in the northern and central Gulf. Discussion The results indicate the requirement of further research on the complex interplay between physical and biogeochemical factors, and anthropogenic influences on Chl- a distribution, which can help future monitoring and predictive ecosystem models for the Gulf under changing climate conditions.

Fluorescence spectroscopy as a tool for differentiating methicillin resistance in clinical isolates of Staphylococcus aureus - Rabia Anjum; Sana Imtiaz; Tahseen Rafaqat; Naeem Akhtar; Muhammad Saleem; Muhammad Umar (Journal of Fluorescence, 2025)

Sustainable hybrid constructed wetland-biological trickling filter system for simultaneous removal of antibiotics and heavy metals: Performance, mechanisms, and microbial insights - Arshad Ameen; Yu Zheng; Qian Wang; Yuanyuan Li; Saleem Ullah Saleem; Muhammad Amjad Saleem; Waqas Niaz; Hannan Ahmad Anjum; Fengmin Li (Journal of Water Process Engineering, 2025)

Recent progress in biomass polymer based hydrogel membranes for adsorption and photocatalytic pollutants removal: fabrication, challenges and future perspectives - Muhammad Usman Hameed; Luqman Ali; Ayesha Ahmad; Pei Zhang; Saleem Raza; Sikandar Khan; Wei-Ren Liu; Zainab Amjad (Desalination, 2025)

Projecting future climate extremes in the glacier-fed upper indus basin using machine learning based downscaling of CMIP6 GCMs - Muhammad Amjad Saleem; Muhammad Shoaib; Sarfraz Hashim; Muhammad Shoaib; Hafiz Umar Farid; Muhammad Ismail; Mubashir Ali Ghaffar; Ahmad Mujtaba; Jinwook Lee; Muhammad Azhar Inam; Arshad Ameen (Theoretical and Applied Climatology, 2025)

Fabrication of bergapten loaded microneedle patch and assessment of its anti-arthritic potential against complete Freund’s adjuvant induced arthritis in Wistar rat - Qadeer Ahmad; Ammara Saleem; Zulcaif Ahmad; Muhammad Furqan Akhtar (Inflammopharmacology, 2025)

Improvement in swell and consolidation behavior of sheard clay using glass powder and polypropylene fibers as additives - Syed Zishan Ashiq; Babar Naseem Khan Raja; Syed Minhaj Saleem Kazmi; Muhammad Junaid Munir; Muhammad Hassan (Innovative Infrastructure Solutions, 2025)

Evaluating soil health and aggregation potential in dryland soils under diverse land uses in semiarid Pakistan - Abdul Wahab; Kashif Ali Kubar; Muhammad Shaaban; Zia-ul-hassan; Inayatullah Rajpar; Allah Wadhayo Gandahi; Saleem Maseeh Bhatti; Muhammad Afzal Chhajro; Qambar Baloch (Environmental Monitoring and Assessment, 2025)

Evaluating citric and oxalic acids as sustainable chelating agents for heavy metal remediation and phytoextraction efficiency in contaminated soils using maize (Zea mays) - Ojone Anyebe; Fatihu Kabir Sadiq; Abdulalim Ahovi Sadiq; Khalid S. Almaary; Hafiz Muhammad Saleem Akhtar (Clean Technologies and Environmental Policy, 2025)

Microplastics in two commercial marine fish species: A pilot study from the Arabian Sea - Nabia Saleem Khan; Imrana Niaz Sultan; Afrasiab Khan Tareen; Muhammad Waseem Khan (Environmental Monitoring and Assessment, 2025)

Diversity of arthropods fauna in correlation to abiotic factors in wheat crop - Dilbar Hussain; Bushra Khalid; Muhammad Asrar; Usama Saleem; Wafa Abdullah Hamad Alkherb; Muhammad Saleem; Hina Anwar; Saddam Hussain; Muhammad Sohail Qadir; Mubshar Saleem; Khalid Ali Khan; Hamed A. Ghramh; et al. (International Journal of Tropical Insect Science, 2025)

DFT, GC-MS analysis and biological evaluation of Limbarda crithmoides L. Dumort essential oil; an important edible halophyte grown in Pakistan - Muhammad Iltaf; Shah Iram Niaz; Muhammad Kashif Majeed; Muhammad Saleem; Mubarak Shah; Muhammad Ali; Syed Shakeel Abbas; Adnan Amin (Natural Product Research, 2025)

Design and development of industrial prototype of spot specific orchard sprayer using ultrasonic sensing system and advanced pressure control mechanism - Arshed Ahmed; Shoaib Rashid Saleem; Muhammad Naveed Tahir; Shahram Hamza Manzoor; Qamar Zaman; Zhao Zhang; Rashed Ahmed (Computers and Electronics in Agriculture, 2025)

Genome-wide identification, characterization and expression analysis of CsC3H gene family in cucumber (Cucumis sativus L) under various abiotic stresses - Saleem Uddin; Sadia Gull; Hafiz Athar Hussain; Umer Mahmood; Muhammad Qasim; Farah Kamal; Abdel-Rhman Z. Gaafar; Saltanat Aghayeva; Rashid Iqbal; Xiaohong Yang (Plant Science, 2025)

Machine learning-based streamflow projections in the upper indus basin under CMIP6 climate scenarios - Muhammad Amjad Saleem; Muhammad Shoaib; Sarfraz Hashim; Muhammad Shoaib; Hafiz Umar Farid; Mubashir Ali Ghaffar; Muhammad Ismail; Arshad Ameen; Jinwook Lee; Muhammad Azhar Inam; Changhyun Jun (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

DFT investigation of pristine and li-functionalized TiS2 monolayers for toxic gas sensing applications - Zunaira Saleem; Saleh S. Alarfaji; Humaira Shaheen; Abdul Majid; Muhammad Isa Khan (Journal of Environmental Chemical Engineering, 2025)

Enhancing rice crop resistance against brown plant hopper infestation through the foliar application of sodium nitroprusside - Muhammad Farooq; Dan-Dan Zhao; Saleem Asif; Jae-Ryoung Park; Mohamed H. Helal; Rashid Iqbal; Zakirullah Khan; Kyung-Min Kim (Plant Molecular Biology, 2025)

Molecular Insights into NAC Transcription Factors: Key Regulators of Plant Response to Metal Stress - Sarah Bouzroud; Mohammad Reza Fayezizadeh; Susmita Das; Mohammad Sarraf; Muhammad Hamzah Saleem; Sezai Ercisli; Iman Mirmazloum; Mirza Hasanuzzaman (Journal of Plant Growth Regulation, 2025)
Plants are often exposed to environmental constraints and abiotic stresses such as heavy metal(loid)s that can severely impair plant growth, development, and productivity. Metal stress triggers a cascade of molecular, physiological, and biochemical-induced responses, often resulting in cellular damages and growth arrest. To counter this, plants have evolved efficient strategies that either restrict metal uptake or facilitate its detoxification and sequestration within specific cellular compartments. Transcription factors control the activation/regulation of the expression of stress-inducible genes. Of these, NAC (NAM, ATAF1/2, and CUC2) transcription factors emerged as key regulators of plant metal stress response. NACs alleviate oxidative damage by inducing the expression of antioxidant enzymes such as peroxidase (POD), catalase (CAT), and superoxide dismutase (SOD). They are also involved with phytohormone signaling pathways and regulated endogenous levels of key plant hormones, in order to fine-tune plant stress responses. Aside from their function in detoxification and redox homeostasis, NAC are also implicated in broader developmental processes and stress signaling pathways, which strongly suggests their intricate role in plant tolerance, thereby offering a promising path for the development of stress-tolerant crops, especially in regions suffering from increasing soil contamination and decreasing agricultural productivity. This review illustrates a particular profile of metal stress and its potential for plant development and growth with special focus on NAC TFs involvement in the set of plant defense and detoxification mechanisms. Understanding the underpinning molecular mechanisms will provide a solid foundation for future biotechnological applications for the support of crop growth in adverse environments.

Assessing alkaline battery waste toxicity in Nile tilapia (Oreochromis niloticus): integrating physiological biomarker analysis with molecular docking insights - Ahmad Waheed; Habiba Zafar; Hina Naz; Jabbir Ali Khan; Samra Shafqat; Muhammad Saleem Khan; Muhammad Wajid (Ecotoxicology, 2025)

Synthesis, characterization, and advanced sustainable applications of copper oxide nanoparticles: a review - Muhammad Hamzah Saleem; Ujala Ejaz; Meththika Vithanage; Nanthi Bolan; Kadambot H. M. Siddique (Clean Technologies and Environmental Policy, 2025)

Production Technologies for Recombinant Antibodies: Insights into Eukaryotic, Prokaryotic, and Transgenic Expression Systems - Muhammad Zafar Saleem; Ghulam Zahra Jahangir; Ammara Saleem; Asma Zulfiqar; Khalid Ali Khan; Sezai Ercisli; Baber Ali; Muhammad Hamzah Saleem; Aroona Saleem (Biochemical Genetics, 2025)

From metabolic dysregulation to neurodegenerative pathology: the role of hyperglycemia, oxidative stress, and blood-brain barrier breakdown in T2D-driven Alzheimer’s disease - Ahmad Raza; Shafaq Saleem; Samar Imran; Sarah Rahman; Muhammad Haroon; Azeen Razzaq; Ahmad Hussain; Javed Iqbal; Brijesh Sathian (Metabolic Brain Disease, 2025)
Type 2 Diabetes (T2D) and Alzheimer’s Disease (AD) share common risk factors that can be seen through T2D nearly doubling an individual’s likelihood of developing AD. Some AD patients show signs of metabolic dysfunction as well. This review focuses on the potential mechanisms associated with these two diseases, like insulin resistance, inflammation, oxidative damage, mitochondrial injury, and cell death. One of the notable elements in this connection is the “brain insulin resistance,” most frequently named as “type 3 diabetes,” which impairs glucose metabolism and facilitates amyloid beta (Aβ) plaque synthesis while reducing the action of insulin-degrading enzyme (IDE). Moreover, the overactivity of glycogen synthase kinase-3 beta (GSK-3β) also triggers taurine protein pathology. Raised concentrations of glucose in blood can produce advanced glycation end products (AGEs), which further exacerbate neuroinflammation in tandem with the mitigation of neurotoxic Aβ oligomers. Inflammation and subsequent damage to mitochondria lead to the dissolution of synapses. Current vascular insults include the breakdown of the blood-brain barrier (BBB) and decreased brain perfusion, along with other contributory factors to conditions conducive to neurotoxicity. Recently, novel therapies are emerging, including GLP-1 agonists, intranasal insulin, and mitochondrial antioxidants, that show surprising results for treating both conditions, but on the contrary, bioavailability and the timing of interventions remain a big challenge in the management of these diseases. Eventually, further research should center on understanding the mechanisms of integration along with the development of molecular biology, neuroimaging, and outcome-driven treatment strategies. Comprehensive strategies that exist between T2D-AD for integration and preservation of brain and metabolic health are addressed in this review. Graphical abstract

Integrated study of the deformed phosphorite dolomite of the Early Cambrian Sirban formation in the Lesser Himalayas, Pakistan - Khawaja Umair Majeed; Muhammad Saleem Mughal; Xijuan Tan; Sara Criniti; Massimo Civitelli; Muhammad Rustam Khan; Shoukat Hussain Khan; Salvatore Critelli (Acta Geochimica, 2025)

Structural and functional insights into Jasmonate ZIM-domain 2 (GhJAZ2) interactions in cotton fiber development via Jasmonic acid signaling - Muhammad Sulyman Saleem; Sultan Habibullah Khan; Zunaira Afzal Naveed (Plant Gene, 2025)

A morphological insight into degradation of polyethylene-based plastic waste via SEM and AFM - Mahnoor Shireen; Fateeha Tariq; Muhammad Saleem; Qaiser Mahmood (Next Research, 2025)

Phycocyanin as a sustainable future resource: A review on recent advancements, fundamental challenges, opportunities and applications - Haider Ali; Rashid Iftikhar; Muhammad Ali Inam; Muhammad Umer Abbas; Sahar Saleem; Faras Ahmad Shahbaz; Humayun Nadeem; Aleena Tahir; M. Momin (Bioresource Technology Reports, 2025)

Alleviating Microplastic and Cadmium Stress in Rice (Oryza sativa L.), Role of Molybdenum Disulfide, Zinc Oxide, and Selenium–Nanoparticles in Morpho–Physio–Biochemical Traits - Hiba Shaghaleh; Yousef Alhaj Hamoud; Muhammad Hamzah Saleem; Hosam O. Elansary; Eman A. Mahmoud (Journal of Soil Science and Plant Nutrition, 2025)

The Role of Silver Nanoparticles and Bacillus subtilis in Modulating Morpho–Physio–Biochemical Responses in Wheat (Triticum aestivum L.) Under Arsenic Stress - Mohammad K. Okla; Sadia Javed; Muhammad Faran Tahir; Ibrahim A. Saleh; Muhammad Anas; Muhammad Hamzah Saleem; Temoor Ahmed; Abdulrahman Abdullah Alatar; Bandar M. AlMunqedhi; Shafaqat Ali (Journal of Soil Science and Plant Nutrition, 2025)
Soil contamination with toxic heavy metals [such as arsenic (As)] is becoming a serious global problem because of the rapid development of the social economy. Although plant growth-promoting rhizo-bacteria (PGPR) and nanoparticles (NPs) are the major protectants to alleviate metal toxicity, the study of these chemicals in combination to ameliorate the toxic effects of As is limited. Therefore, the present study was conducted to investigate the effects of different levels of Bacillus subtilis (5 and 10 mg L –1 ) and silver (Ag)–NPs (10 and 20 mg kg –1 ) on morpho-physiological and antioxidative defense attributes, which was spiked with different levels of As [0 mM (i.e., no As), 100, and 200 mg kg –1 ] in wheat ( Triticum aestivum L.) seedlings. Results from the present study showed that the increasing levels of As in the soil significantly ( P < 0.05) decreased plant growth and biomass, photosynthetic pigments, gas exchange attributes, sugars, and nutritional contents from the roots and shoots of the plants. In contrast, increasing levels of As in the soil significantly ( P < 0.05) increased oxidative stress indicators in term of malondialdehyde (MDA), hydrogen peroxide (H 2 O 2 ), and electrolyte leakage (EL), and also increased organic acid exudation patter in the roots of T. aestivum . The negative impact of As toxicity can overcome the application of B . subtilis and Ag − NPs, which ultimately increased plant growth and biomass by capturing the reactive oxygen species (ROS), and decreased oxidative stress in T. aestivum by decreasing the As contents in the roots and shoots of the plants. Research findings, therefore, suggest that the combined application of B . subtilis and Ag − NPs can ameliorate As toxicity in T. aestivum , resulting in improved plant growth and composition under metal stress, as depicted by balanced exudation of organic acids. Graphical Abstract

Exogenous Zinc Alleviates Post-Anthesis Heat Stress by Improving the Defense Mechanism and Leaf Physiology of Bread Wheat - Muhammad Sarwar; Muhammad Farrukh Saleem; Aleena Anwar; Hassaan Ahmad; Basharat Ali; Muhammad Shahid; Abeer Hashem; Ajay Kumar; Elsayed Fathi Abd-Allah (Journal of Soil Science and Plant Nutrition, 2025)

Contrasting Growth Patterns, Root Trait Plasticity, Phosphorus Uptake, and Antioxidant Responses in Maize Hybrids under Water and Phosphorus Deficiency - Hafiz Athar Hussain; Qingwen Zhang; Qurat ul Ain; Saddam Hussain; Saleem Uddin; Rubab Zahra Naqvi; Rana Muhammad Atif; Muhammad Ahmad; Asma Imran (Journal of Soil Science and Plant Nutrition, 2025)

Retraction Note: Polystichum braunii extracts inhibit Complete Freund’s adjuvant-induced arthritis via upregulation of I-κB, IL-4, and IL-10, downregulation of COX-2, PGE2, IL-1β, IL-6, NF-κB, and TNF-α, and subsiding oxidative stress - Ammara Saleem; Mohammad Saleem; Muhammad Furqan Akhtar; Muhammad Shahzad; Shah Jahan (Inflammopharmacology, 2025)

Covalently grafting cationized sericin to silk fabric for achieving economical salt-free dyeing and antibacterial property and minimizing strength loss - Muhammad Asad Saleem; Zihao Jin; Mingbo Ma (Clean Technologies and Environmental Policy, 2025)

Bioactivity of 2-(3,4-Dihydroxyphenyl)-5,7-dihydroxy-2,3-dihydrochromen-4-one from pistacia chinensis on ENPP1 and aldose reductase - Abdur Rauf; Saima Naz; Zuneera Akram; Muhammad Saleem; Taghrid S. Alomar; Najla AlMasoud; Giovanni Ribaudo (Natural Product Research, 2025)

A tetrahydropyrimidine derivative demonstrates neuroprotection against ketamine-induced schizophrenia through moderating oxidative and inflammatory markers - Tayyaba Tahir; Qurat-Ul-Ain; Ammara Saleem; Shahnaz; Muhammad Imran Khan; Kanwal Akhtar; Irfan Hamid; Rabia Iqbal; Zulcaif Ahmad; Muhammad Furqan Akhtar (Metabolic Brain Disease, 2025)

TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Seed Pre-treatment with Thiourea Improves Physiological and Metabolic Adaptation to Booting Stage Salinity in Wheat - Azka Saleem; Mehwish Rubab; Maria Abubakar; Ali Raza; Amnah M. Alamri; Hesham F. Alharby; Hameed Alsamadany; Yahya M. Alzahrani; Muhammad Waqas; Hafeez ur Rehman (Journal of Crop Health, 2025)

How Does Corporate Governance Deviance Impact Sustainability in Family Firms? A Stakeholder Perspective - Irfan Saleem; Muhammad Naeem; Muhammad Haseeb; Hao Ji; Said Al Fazari (Circular Economy and Sustainability, 2025)

Evaluation of entomopathogenic fungi and nematode species for eco-friendly management of fall armyworm, Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) - Usama Saleem; Muhammad Asrar; Dilbar Hussain; Faisal Hafeez; Muhammad Sohail Qadir (International Journal of Tropical Insect Science, 2025)

Individual and combinatorial application of indole−3−acetic acid and salicylic acid in barley (Hordeum vulgare L.): Assessing morpho−physio−biochemical responses under copper stress - Arwa Abdulkreem AL-Huqail; Aishah Alatawi; Suliman Mohammed Suliman Alghanem; Muhammad Faran Tahir; Muhammad Anas; Muhammad Hamzah Saleem; Hosam O Elansary; Eman A. Mahmoud (South African Journal of Botany, 2025)

Spectrum of BRCA1/2 pathogenic variants in Southern and Western Asia-a systematic review - Samra Khan; Ikram A. Burney; Mahrukh Nasir; Humaira Saleem; Muhammad Irfan; Muhammad Shakeel; Ishtiaq Ahmad Khan (Mutation Research - Reviews in Mutation Research, 2025)

Scalable interlinked hierarchical porous biochar-nanosheets for efficient removal of thallium from aquatic environment - Haitao Ren; Zainab Amjad; Atif Saleem; Muhammad Usman; Kukybayeva Dina; Muhammad Haris; Junkang Guo (Journal of Hazardous Materials, 2025)

Exploring single-atom catalysis for hydrogen evolution and storage: A DFT insight into first-row transition metal-porphyrin complexes (Porph@TMs) - Faheem Abbas; Saleem Nawaz Khan; Sadaf Bibi; Mariyum Yousaf; Francis Enujekwu; Muhammad Salman Khan; Sami Ullah; Mohammed Ali Assiri (Gas Science and Engineering, 2025)

Place attachment and residential water conservation: Application of an extended Theory of Planned Behaviour in Australia's Northern Territory - Charles Baah; Muhammad A. Saleem; Steven Greenland; Emmanuel S. Tenakwah; Debajyoti Chakrabarty (Environmental Development, 2025)

High-toughness design of micron-sized silicon/carbon composite as practical anode for lithium-ion batteries - Yiting Hao; Xiongbin Yang; Yingzhe Gao; Muhammad Hassaan Saleem; Jingde Li; Changcheng Wu; Guihua Liu (Chemical Engineering Journal, 2025)

Omics Technologies: Unraveling Abiotic Stress Tolerance Mechanisms for Sustainable Crop Improvement - Muhammad Hamzah Saleem; Sana Noreen; Izwa Ishaq; Ammara Saleem; Khalid Ali Khan; Sezai Ercisli; Muhammad Anas; Awais Khalid; Temoor Ahmed; Ammara Hassan; Shah Fahad (Journal of Plant Growth Regulation, 2025)

Carbapenem Resistant Serratia marcescens Harboring blaOXA-48, armA and aac(6′)-Ib-cr Genes: The First Baseline Study from Pakistan - Amna Kausar; Muhammad Sohail; Mohsin Khurshid; Hafiz Ghulam Murtaza Saleem (Current Microbiology, 2025)

Turn-On-Fluorescence Sensor and Solid Sensory Chip for Cyanide Detection - Muhammad Zahid; Nadeem Raza; Samuel Bonne; Mostafa E. Salem; Negin G. Niksirat; Muhammad Zeshan; Muhammad Rafiq; Jian Zhang; Muhammad Saleem (Journal of Fluorescence, 2025)

Evaluating the effect of land use land cover changes on soil moisture index and vegetation indices using multi-spectral satellite data - Muhammad Zaib Arshad; Zafar Iqbal; Muhammad Saeed; Muhammad Saleem; Rizwan Mansha; M Abdullah-Al-Wadud; Aqil Tariq (Journal of Earth System Science, 2025)

Machine learning-based detection and quantification of red blood cells in Cholistani cattle: A pilot study - Sami Ul Rehman; Sania Fayyaz; Muhammad Usman; Mehreen Saleem; Umer Farooq; Asjad Amin; Mushtaq Hussain Lashari; Musadiq Idris; Haroon Rashid; Maryam Chaudhary (Research in Veterinary Science, 2025)

Restoring wheat productivity and nutrient balance under cadmium stress through reducing toxicity, metal uptake, and oxidative damage using selenium nanoparticles - Ayesha Jamil Abbasi; Muhammad Anas; Minhas Elahi; Amjid Khan; Waseem Ahmed Khattak; Muhammad Hamzah Saleem; Shah Fahad; Hosam O. Elansary; Eman A. Mahmoud; Temoor Ahmed; Umar Masood Quraishi (Journal of Trace Elements in Medicine and Biology, 2025)

Correction: Role of ZnSO4 in Modulating Physiochemical Traits and bZIP Genes Expression in Rice Varieties Grown in Zinc-Deficient Soil - Bushra Rehman; Asma Zulfiqar; Muhammad Zafar Saleem; Maqsood Ul Hussan; Manzer H. Siddiqui; Sadam Hussain (Journal of Soil Science and Plant Nutrition, 2025)

Role of ZnSO4 in Modulating Physiochemical Traits and bZIP Genes Expression in Rice Varieties Grown in Zinc-Deficient Soil - Bushra Rehman; Asma Zulfiqar; Muhammad Zafar Saleem; Maqsood Ul Hussan; Manzer H. Siddiqui; Sadam Hussain (Journal of Soil Science and Plant Nutrition, 2025)

Individual and Combinatorial Applications of Arbuscular Mycorrhizal Fungi and Plant Growth-Promoting Rhizobacteria Increase Morpho-Physio-Biochemical Responses in Rice (Oryza sativa L.) under Cadmium Stress - Arwa Abdulkreem AL-Huqail; Aishah Alatawi; Sadia Javed; Muhammad Faran Tahir; Muhammad Anas; Muhammad Hamzah Saleem; Temoor Ahmed; Mohammed O. Alshaharni; Eman Fayad; Khalid Ali Khan; Awais Khalid; Shafaqat Ali; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Fodder Quality, Morphological and Biochemical Characteristics of Mombasa Grass (Megathyrsus maximus) Under Differently Primed Seeds - Muhammad Abdullah Saleem; Asif Iqbal; Umair Gull; Muhammad Iqbal (Journal of Crop Health, 2025)

First Insights on Sowing Time and Cultivar Selection of Sweet Corn for Optimal Yield and Shelf Life Under Agro-Climatic Conditions of Multan - Iqra Zakir; Shakeel Ahmad; Muhammad Shahzad Saleem; Sajjad Hussain; Halima Nawaz; Talaat Ahmed; Muhammad Fasih Khalid (International Journal of Plant Production, 2025)

Amelioration of Freund’s adjuvant-induced polyarthritis by Diosmin-loaded nanoparticles in Wistar rats; a mechanistic study - Hamna Mehmood; Ammara Saleem; Muhammad Furqan Akhtar; Aisha Mobashar (Inflammopharmacology, 2025)

Identification and Characterization of Evolutionary Conserved Muskmelon Non-coding miRNAs and Their Target Proteins - Abdul Ghaffar; Naqeebullah khan; Muhammad Zafar Saleem; Irshad Ali; Attiq Ur Rehman; Waheed Ahmed Shah; Samiullah (Biochemical Genetics, 2025)

Energy bandgap tuning of Sr-doped ZnO nanoparticles for photodegradation of azo dyes and antibacterial applications - Hufsa Ahmad; Abu Bakar Siddique; Saima Zaheer; Rabia Sattar; Azhar Abbas; Muhammad Amin; Rashad Al-Salahi; Hatem A. Abuelizz; M. Zubair Saleem (Journal of Water Process Engineering, 2025)

Carrageenan based edible coating modulates oxidative stress and delays cell wall polysaccharides disassembly in harvested grapefruit - Sajid Ali; Sidra Riaz; Hafiz Umer Javed; Ahmad Sattar Khan; Maratab Ali; Safina Naz; Hasan Sardar; Muhammad Shahzad Saleem (Journal of Stored Products Research, 2025)

Investigating the interaction of breed and seasonality on milk quality parameters in different dairy cow breeds - Hafiz Muhammad Jawad Saleem; Qamar Abbas Syed; Sumayah Abbas; Muhammad Azeem; Saba Anwar; Ali Hassan (Food and Humanity, 2025)

Amelioration of pain and adjuvant-induced arthritis by syringic acid via modulation of behavioral parameters and inflammatory mediators i.e. TNF-α, Interleukins, MCP-1, NF-kB and COX-2 - Noviara Saleem; Syed Atif Raza; Alamgeer; Muhammad Khalil-ur-Rehman; Rukhsana Anwar; Abrar Ahmed; Hafiz Muhammad Irfan (Inflammopharmacology, 2025)

Role of polyphenolics in the management of rheumatoid arthritis through intracellular signaling pathways: a mechanistic review - Uzma Saleem; Maryam Farrukh; Malik Saadullah; Rida Siddique; Humaira Gul; Aqsa Ahmad; Bushra Shaukat; Muhammad Ajmal Shah (Inflammopharmacology, 2025)

Rhizospheric bacterial strain Pseudomonas putida and fungal strain Penicillium chrysogenum alleviate Fusarium wilt of tomato by improving key growth attributes - Hassaan Ateeb Ahmad; LNU Farhana; Urooj Haroon; Hira Saleem; Maryam Anar; Mahnoor Akbar; Kanwal Abbasi; Abdul Rehman; Mohammad Sameer Zubair; Asif Kamal; Hassan Javed Chaudhary; Rattandeep Singh; et al. (European Journal of Plant Pathology, 2025)

Efficacy of ascorbic acid coated quantum dots in alleviating lead-induced oxidative damage and enhancing growth parameters in rice (Oryza sativa L.) for sustainable cultivation - Aliza Falak; Muhammad Anas; Amjid Khan; Alvina Hayat; Zeenat Shaheen; Muhammad Hamzah Saleem; Shah Fahad; Umar Masood Quraishi (Journal of Trace Elements in Medicine and Biology, 2025)

Recent progress in 2D-MXene-based membranes for water treatments; fabrication, properties, and advanced desalination application - Muhammad Usman Hameed; Zainab Amjad; Basem Al Alwan; Atef El Jery; Hassan M.A. Hassan; Luqman Ali; Ayesha Ahmad; Sikandar Khan; Saleem Raza (Desalination, 2025)

Immunomodulatory properties of a methanolic extract of Ficus lyrata mitigate inflammation in Complete Freund’s Adjuvant-induced arthritis - Anam Iftikhar; Mohammad Saleem; Syed Atif Raza; Adrian Achuthan; Rodney Luwor; Taha Muhammad; Umair Majeed (Inflammopharmacology, 2025)

Retraction Note: Evaluation of toxicity potential of cobalt in wheat irrigated with wastewater: health risk implications for public - Fu Chen; Zafar Iqbal Khan; Asma Zafar; Jing Ma; Muhammad Nadeem; Kafeel Ahmad; Shehzadi Mahpara; Kinza Wajid; Humayun Bashir; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq; et al. (Environmental Science and Pollution Research, 2025)

Unveiling the microplastics degradation and its transformative effects on soil nutrient dynamics and plant health – A systematic review - Abdul Rehman; Shan Zhong; Daolin Du; Xiaojun Zheng; Muhammad Saleem Arif; Samra Ijaz; Muhammad Raza Farooq (Sustainable Production and Consumption, 2025)

Enhanced microwave absorption and improved broadband with synergistic effect of nest like self-assembly of CoFe2O4/Co3O4 heterostructured composites - M. Zeeshan Ashfaq; Aamna Ashfaq; Xingxing Cheng; Hongyu Gong; Adil Saleem; Rashid Iqbal; Muhammad Sajjad; Junbin Lu; M. Mamoor; Muhammad K. Majeed (Chemical Engineering Journal, 2025)

Unraveling phase-dependent variations of viral community, virus-host linkage, and functional potential during manure composting process - Zhengyuan Zhou; Songfeng Liu; Muhammad Saleem; Fei Liu; Ruiwen Hu; Hualong Su; Da Dong; Zhiwen Luo; Yongjie Wu; Yan Zhang; Zhili He; Cheng Wang (Bioresource Technology, 2025)

Genomic selection, gene editing, and reproductive biotechnology: a triad for the improvement of native buffalo breeds in a developing country perspective like Pakistan - Raja Danish Muner; Muhammad Moaeen-ud-Din; Ali Haider Saleem; Qudrat Ullah; Ghulam Abbas; Babar Maqbool; Masroor Ellahi Babar; Yanzhen Bi; Farhan Farooq (Tropical Animal Health and Production, 2025)

Combating Mercury Stress in Spinach (Spinacia oleracea L.) with Zinc Oxide and Providencia Vermicola, Assessing Changes in Defense Mechanism and Organic Acid Exudation Patterns - Arwa Abdulkreem AL-Huqail; Aishah Alatawi; Sadia Javed; Muhammad Anas; Muhammad Hamzah Saleem; Awais Khalid; Khalid Ali Khan; Shafaqat Ali (Journal of Soil Science and Plant Nutrition, 2025)

Qualitative Traits of Heat Stressed Bread Wheat (Triticum aestivum L.) were Improved by Exogenous Potassium Signaling - Muhammad Shahid; Muhammad Farrukh Saleem; Amna Saleem; Muhammad Sarwar; Abdul Shakoor; Khalid Mahmood; Shakeel Ahmad Anjum (Journal of Soil Science and Plant Nutrition, 2025)

RETRACTED ARTICLE: Assessment of genetic diversity in cotton genotypes using simple sequence repeat (SSR) markers: insights from interspecific and intraspecific variations - Muhammad Arslan; Akash Fatima; Fatima Javeria; Sehrish Ijaz; Umair Riaz; Gulnaz Saleem; Mounir M. Bekhit; Milad A. Mezher; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

Study of detoxification enzymes in Bemisia tabaci (Hemiptera: Aleyrodidae) populations collected from four districts of Punjab, Pakistan - Sabeen Asghar; Dilbar Hussain; Muhammad Saleem; Muhammad Asrar; Farhat Jabeen (International Journal of Tropical Insect Science, 2025)

Unfolding the role of silicon dioxide nanoparticles (SiO2NPs) in inducing drought stress tolerance in Hordeum vulgare through modulation of root metabolic, nutritional, and hormonal profiles - Nadiyah M. Alabdallah; Khansa Saleem; Aisha Saud Al-Shammari; Saleha S. AlZahrani; Ali Raza; Muhammad Ahsan Asghar; Hafiz Hassan Javed; Jean Wan Hong Yong (South African Journal of Botany, 2025)

Synthesis and doping of alkali metals on MOF-74 for CO2 and CH4 pure and binary mixtures adsorption - Sami Ullah; Mohamad Azmi Bustam; Muhammad Sagir; Muhammad Rafi Raza; Saleem Nawaz; Mohammed Ali Assiri; Abdullah G. Al-Sehemi; Ahmad Mukhtar; Chong Li Feng; Muhammad Ayoub (Gas Science and Engineering, 2025)

Modeling and analysis of a carbon capturing system in forest plantations engineering with Mittag–Leffler positive invariant and global Mittag–Leffler properties - Muhammad Umer Saleem; Muhammad Farman; Rabia Sarwar; Parvaiz Ahmad Naik; Perwasha Abbass; Evren Hincal; Zhengxin Huang (Modeling Earth Systems and Environment, 2025)

Microbial Interactions and Bacterial Responses to Metal Stress in Plants: Mechanisms, Adaptations, and Applications for Sustainable Agriculture - Muhammad Anas; Aliza Falak; Sameel Hassan; Waseem Ahmed Khattak; Muhammad Hamzah Saleem; Khalid Ali Khan; Awais Khalid; Shah Fahad (Journal of Crop Health, 2025)

Symbiotic Synergy: Unveiling Plant-Microbe Interactions in Stress Adaptation - Muhammad Anas; Awais Khalid; Muhammad Hamzah Saleem; Khalid Ali Khan; Waseem Ahmed Khattak; Shah Fahad (Journal of Crop Health, 2025)

Evaluation of Genotype × Environment Interaction and Yield Stability of Cotton (Gossypium hirsutum L) Genotypes Under Heat Stress Conditions - Iram Sharif; Saba Aleem; Jamshaid Ali Junaid; Muqadas Aleem; Khazina Jamshaid; Huma Saleem; Muhammad Rizwan; Shahid Munir Chohan; Saqib Sohail; Saba Akram; Muhammad Zeeshan; Ghulam Sarwar (Journal of Crop Health, 2025)

Exploring environmentally stable and novel genetic factors influencing rice grain shape and yield attributes - Sadia Gull; Zulqarnain Haider; Houwen Gu; Saleem Uddin; Muhammad Qasim; Rana Ahsan Raza Khan; Adil Altaf; Sajid Fiaz; Mona S. Alwahibi; Mohamed S. Elshikh; Rashid Iqbal; Jun Miao; et al. (Euphytica, 2025)

Retraction Note: The integrin facilitated internalization of fibronectin-functionalized camptothecin-loaded DNA-nanofibers for high-efficiency anticancer effects - Mirza Muhammad Faran Ashraf Baig; Wing-Fu Lai; Saba Ashraf; Ammara Saleem; Muhammad Furqan Akhtar; Reyaj Mikrani; Muhammad Naveed; Farhan Siddique; Abdoh Taleb; Jahanzeb Mudassir; Ghulam Jilany Khan; Muhammad Tayyab Ansari (Drug Delivery and Translational Research, 2025)

Retraction Note: Assessment of Titanium Dioxide Nanoparticles (TiO2-NPs) Induced Hepatotoxicity andAmeliorative Effects of Cinnamomum cassia in Sprague–Dawley Rats - Muhammad Shakeel; Farhat Jabeen; Rehana Iqbal; Abdul Shakoor Chaudhry; Sadia Zafar; Muhammad Ali; Muhammad Saleem Khan; Adeel Khalid; Samina Shabbir; Muhammad Saleem Asghar (Biological Trace Element Research, 2025)

Metazoan parasites associated with marine mollusks inhabiting the China Seas: a review - Xin Du; Jing Sun; Huidong Ju; Zhen Xu; Xiaoli Tang; Xuedan Fang; Muhammad Saleem Chang (Frontiers in Marine Science, 2025)
Parasites in mollusks are often neglected by humans, while some species were reported to be harmful to economic mollusks and caused production decrease. Metazoan parasites of mollusk studies from the China Seas started relatively later than other countries. To promote long-term studies on the distribution and diversity of metazoan parasites of mollusks from the China Seas, a comprehensive review has been carried out based on the available literature. The purpose of this study was to perform a critical review about the metazoan parasites associated with mollusks that are useful for the discovery of new metazoans. This publication summarizes information on metazoan parasites of Chinese mollusks from 1932 to 2024. The information is presented and contains 128 species of parasites, distributed among the higher taxa as follows: Turbellaria (2 species), Trematoda (34 species), Cestoda (1 species), Annelida (38 species), Arthropoda (48 species), Porifera (2 species), Cnidaria (1 species), and Mollusca (2 species). Many records of parasites not identified to the species level are also included. Collectively, this review provides a synopsis of the known metazoan parasites of mollusks from the China Seas, as well as presents the known relationship between metazoan parasites and the mollusks, which will broaden our knowledge on the metazoan parasites of mollusks. It is important as it highlights the lack of metazoan parasite studies done in the China Seas and the need for more parasite biodiversity work.

Investigating Bemisia tabaci (Hemiptera: Aleyrodidae) resistance mechanisms: a comprehensive analysis of variable responses to selective insecticides - Dilbar Hussain; Muhammad Saleem; Muhammad Sohail Qadir; Kanwal Hanif; Faisal Hafeez; Usama Saleem; Muhammad Jawad Saleem; Muhammad Bilal Bin Iqbal; Muhammad Zubair (International Journal of Tropical Insect Science, 2025)

Development of sustainable high-performance desert sand concrete: Engineering and environmental impacts of compression casting - Syed Minhaj Saleem Kazmi; Muhammad Junaid Munir; Yu-Fei Wu (Resources, Conservation and Recycling, 2025)

Identifying multidrug-resistant organisms in diabetic foot ulcers: a study of risk factors and antimicrobial resistance genes - Mohd Saleem; Soha Abdallah Moursi; Tahani Nasser Almofeed Altamimi; Alharbi Mohammed Salem; Alwaleed Mohammad Alaskar; Sahar Adly Hassan Hammam; Ehab Rakha; Syed Muhammad Ozair Ilyas; Hamoud Abdulmohsin Al-Malaq; Metab Nasser Alshammari; Azharuddin Sajid Syed Khaja (World Journal of Microbiology and Biotechnology, 2025)

A nature-inspired and noise-assisted feature extraction integrating spatiotemporal attention-based sequence2sequence for multivariate wind speed prediction - Muhammad Sibtain; Xianshan Li; Snoober Saleem; Qurat-ul-Ain; Qiang Shi; Fei Li; Halit Apaydin (Stochastic Environmental Research and Risk Assessment, 2025)

Olive oil and castor oil-based self-nanoemulsifying drug delivery system of flurbiprofen can relieve peripheral pain and inflammation through reduction of oxidative stress and inflammatory biomarkers: a comprehensive formulation and pharmacological insights - Mazaghul Basar; Muhammad Imran Khan; Muhammad Furqan Akhtar; Fareeha Anwar; Ammara Saleem; Asadullah Madni; Zulcaif Ahmad; Ali Sharif; Bushra Akhtar; Uzma Shakoor; Aslam Khan (Inflammopharmacology, 2025)

Down-regulation of interlinked inflammatory signalling cascades by ethanolic extract of Suaeda fruticosa Forssk. ex J.F. Gmel. attenuated in vivo inflammatory and nociceptive responses - Muhammad Fiaz; Mohamed Farouk Elsadek; Khalid S. Al-Numair; Shafqat Rasul Chaudhry; Mohammad Saleem; Kashif ur Rehman Khan; Ashwaq Hamid Salem Yehya; Muhammad Asif (Inflammopharmacology, 2025)

RETRACTED ARTICLE: Esculin-loaded nanoparticles ameliorate adjuvant-induced polyarthritis via subduing inflammatory and oxidative stress biomarkers in Wistar rats - Mehak Fatima; Ammara Saleem; Muhammad Furqan Akhtar; Kanwal Akhtar; Muhammad Imran Khan (Inflammopharmacology, 2025)

Correction: Symmetrical Ligand’s Fabricated Porous Silicon Surface Based Photoluminescence Sensor for Metal Detection and Entrapment - Muhammad Saleem; Abrar Hussain; Salah Uddin Khan; Sajjad Haider; Ki Hwan Lee; Sang Hyun Park (Journal of Fluorescence, 2024)

Correction: Synthesis, Invitro Cytotoxic Activity and Optical Analysis of Substituted Schiff Base Derivatives - Muhammad Saleem; Abrar Hussain; Muhammad Hanif; Hufsa Ahmad; Salah Uddin Khan; Sajjad Haider; Muhammad Rafiq; Rizwan Nasir Paracha; Sang Hyun Park (Journal of Fluorescence, 2024)

Correction: Ratiometric Fluorescence and Chromogenic Probe for Trace Detection of Selected Transition Metals - Muhammad Saleem; Abrar Hussain; Muhammad Rauf; Salah Uddin Khan; Sajjad Haider; Muhammad Hanif; Muhammad Rafiq; Sang Hyun Park (Journal of Fluorescence, 2024)

Exploring the chemistry of waste eggshells and its diverse applications - Laiba Iftikhar; Iqbal Ahmad; Muhammad Saleem; Aamir Rasheed; Amir Waseem (Waste Management, 2024)

The role of selenium and biochar nanoparticles in alleviating cadmium stress in wheat (Triticum aestivum L.) examined via morphophysiological traits and organic acid exudation patterns - Mohammad K. Okla; Sahar Mumtaz; Sadia Javed; Muhammad Hamzah Saleem; Ibrahim A. Saleh; Naser Zomot; Yasmeen A. Alwasel; Mostafa A. Abdel-Maksoud; Muhammad Adnan; Shafaqat Ali (South African Journal of Botany, 2024)

Mechanistic insight into interactive effect of microplastics and arsenic on growth of rice (Oryza sativa L.) and soil health indicators - Muhammad Kashif Irshad; Muhammad Aqeel; Saba Saleem; Wasim Javed; Ali Noman; Min Woo Kang; Noreen Khalid; Sang Soo Lee (Science of The Total Environment, 2024)

Individual and combinatorial application of nanosilica and carbon nanoparticles alleviate nickel stress in barley (Hordeum vulgare L.): Impacts on gene expression, AsA − GSH cycle, cellular fractionation, and proline metabolism - Zhanbin Luo; Manar Fawzi Bani Mfarrej; Muhammad Hamzah Saleem; Jing Ma; Ibrahim A. Saleh; Mostafa A. Abdel-Maksoud; Adel M. Zakri; Fu Chen; Leobardo Manuel Gómez Oliván (Science of The Total Environment, 2024)

Adaptive mechanisms of wheat cultivars to lead toxicity through enhanced oxidative defense, ionomic redistribution, and anatomical modifications - Muhammad Anas; Muhammad Saad Bashir; Khadija Saleem; Atika Noor; Umar Masood Quraishi (Journal of Plant Physiology, 2024)

Do the theories of planned behaviour and protection motivation provide probabilistic sufficient and necessary conditions for residential water conservation? Combined use of PLS-SEM and NCA - Charles Baah; Muhammad A. Saleem; Steven Greenland; Emmanuel S. Tenakwah; Debajyoti Chakrabarty (Journal of Environmental Management, 2024)

Utilizing Cinnamomum verum (a culinary spice), as a functional food ingredient ameliorating hypercholesterolemia: In-vivo, in-vitro, and in-silico multi-model analysis - Mahnoor Bano; Muhammad Khurram Waqas; Talha Ali Chohan; Fakhra Batool; Aamir Mushtaq; Yahya I. Asiri; Mohd. Zaheen Hassan; Md Ali Mujtaba; Md. Khalid Anwer; Muhammad Irfan Sidique; Ayesha Riaz; Umair Khurshid; et al. (Food Bioscience, 2024)

Characterisation of the essential oil from Iphiona grantioides and investigation of its antibacterial and antioxidant properties - Shah Iram Niaz; Muhammad Ali; Muhammad Saleem; Rubina Qaisrani; Kamran Safdar; Malik Muhammad Akram; Abdur Rauf; Maqbool Ahmad; Sanaullah Abbasi; Taghrid S. Alomar; Najla AlMasoud; Giovanni Ribaudo (Natural Product Research, 2024)

Earthworms as Catalysts for Climate-Resilient Agriculture: Enhancing Food Security and Water Management in the Face of Climate Change - Muhammad Danish Toor; Abdul Basit; Benedict Okorie; Dibyajyoti Nath; Muhammad Mughees Ud Din; Pawan Kumar Verma; Saleem Sajjad; Izhar Ullah; Hany N. Yousef; Heba I. Mohamed (Water, Air, & Soil Pollution, 2024)

Interactive use of biochar and chemical fertilizer for improving nutrient availability and crop growth in rainfed area - Saddam Hussain; Rifat Hayat; Saleem Ullah; Muhammad Ashraf; Rebwar Nasir Dara; Muhammad Adeel Ashraf; Sami Ullah Khan; Muyassar Norberdiyeva; Manish Gupta; M. Ijaz Khan (Rendiconti Lincei. Scienze Fisiche e Naturali, 2024)

Biological role and regulation of circular RNA as an emerging biomarker and potential therapeutic target for cancer - Ayman Saleem; Muhammad Umer Khan; Tazeen Zahid; Iqra Khurram; Muhammad Usman Ghani; Inam Ullah; Rakhtasha Munir; Daniela Calina; Javad Sharifi-Rad (Molecular Biology Reports, 2024)

Correction: Examining Adaptive Responses of Foeniculum vulgare to Elevated Sodium and Chloride Stress in the Root Zone - Noreen Akhter; Rimsha Nafees; Ali Noman; Muhammad Aqeel; Naila Hadayat; Noreen Khalid; Abida Kausar; Mohammed O. Alshaharni; Muhammad Muslim Shahnaz; Arsal Saleem; Maryam M. Alomran (Journal of Soil Science and Plant Nutrition, 2024)

Examining Adaptive Responses of Foeniculum vulgare to Elevated Sodium and Chloride Stress in the Root Zone - Noreen Akhter; Rimsha Nafees; Ali Noman; Muhammad Aqeel; Naila Hadayat; Noreen Khalid; Abida Kausar; Mohammed O. Alshaharni; Muhammad Muslim Shahnaz; Arsal Saleem; Maryam M. Alomran (Journal of Soil Science and Plant Nutrition, 2024)

Sedimentology, diagenesis and sequence stratigraphy of the Early–Middle Eocene Chorgali Formation in the Hazara sub-Basin, Northwest Himalayas, Pakistan - Emad Ullah Khan; Shadab Khan; Syed Muhammad Wasim Sajjad; Maryam Saleem; Muhammad Ilyas; Saif Ullah Khan (Carbonates and Evaporites, 2024)

Retraction Note: Assessment of Waterborne Amine-Coated Silver Nanoparticle (Ag-NP)-Induced Toxicity in Labeo rohita by Histological and Hematological Profiles - Muhammad Saleem Khan; Naureen Aziz Qureshi; Farhat Jabeen; Muhammad Shakeel; Muhammad Saleem Asghar (Biological Trace Element Research, 2024)

Effect of green synthesized silver nanoparticles on growth and physiological responses of pearl millet under salinity stress - Zakir Ullah; Syed Inzimam Ul Haq; Abd Ullah; Muhammad Ahsan Asghar; Mahmoud F. Seleiman; Khansa Saleem; Fanjiang Zeng; Noor Us Sama; Khalid Kamran; Sheraz Ahmad (Environment, Development and Sustainability, 2024)

Nutritional composition assessment and antimicrobial activity of Catostylus perezi , jellyfish blooms along the coast of Pakistan: an awareness to avoid food neophobia in Pakistan - Muhammad Naveed; Malik Wajid Hussain Chan; Sadar Aslam; Fenghuan Wang; Anas Sajjad; Asad Ullah; Nida Saleem; Muhammad Samee Haider; Victoria Arija (Natural Product Research, 2024)

Phosphorus sources enhance barley growth and mitigate lead stress via antioxidant responses, proline metabolism, and gene expression - Manar Fawzi Bani Mfarrej; Sadia Javed; Rafa Almeer; Rawidh Alsaidalani; Mohamed Kamel; Muhammad Hamzah Saleem; Shafaqat Ali (South African Journal of Botany, 2024)

A multi-sensor drought index for improved agricultural drought monitoring and risk assessment in the heterogeneous landscapes of the China–Pakistan Economic Corridor (CPEC) - Muhammad Ismail; Yi Li; Ben Niu; Mubashir Ali Ghaffar; Muhammad Amjad Saleem; Kadambot H.M. Siddique (Atmospheric Research, 2024)

Nutritional and medicinal plants as potential sources of enzyme inhibitors toward the bioactive functional foods: an updated review - Hammad Saleem; Anam Yaqub; Rabiya Rafique; Tahir Ali Chohan; Durr-e-Shahwar Malik; Muhammad Imran Tousif; Umair Khurshid; Nafees Ahemad; Ramasamy Ramasubburayan; Kannan RR Rengasamy (Critical Reviews in Food Science and Nutrition, 2024)

Ascorbic acid-mediated enhancement of antioxidants and photosynthetic efficiency: A strategy for enhancing canola yield under salt stress - Nawishta Saleem; Sibgha Noreen; Muhammad Salim Akhter; Mohammed O. Alshaharni; Habib-ur-Rehman Athar; Fahad Mohammed Alzuaibr; Omar Mahmoud Al-zoubi; Seema Mahmood (South African Journal of Botany, 2024)

Recent progress in electro-Fenton technology for the remediation of pharmaceutical compounds in aqueous environments - Uzma Razzaq; Thanh-Binh Nguyen; Muhammad Usman Saleem; Van-Re Le; Chiu-Wen Chen; Xuan-Thanh Bui; Cheng-Di Dong (Science of The Total Environment, 2024)

Spatiotemporal analysis and clinico-epidemiological study for seroprevalence of canine leptospirosis - Muhammad Imran; Muhammad Hassan Saleem; Aneela Zameer Durrani; Ali Ahmad Sheikh (Veterinary Research Communications, 2024)

Fungal phthalimidines-chemodiversity, bioactivity and biosynthesis of a unique class of natural products - Fayrouz El Maddah; Mamona Nazir; Rabbia Ahmad; Sobia Khurshid; Muhammad Saleem; Benjamin Libor (Phytochemistry Reviews, 2024)
A wide range of natural products important for the engineering and drug design of pharmaceuticals comprise largely of nitrogen-based heterocycles. Fungal natural products have proven to be a rich source of the industrially-important molecules, many of which are promising drug leads. Although, natural products containing a phthalimidine core tends not to be given distant classification, but compounds containing these structures exhibit antimicrobial, anthelmintic, antimalarial and insecticidal activities, and are among the potential target for discovering new drug candidates. Intriguingly, these are primarily isolated from fungal sources and to a very lesser extent from plants or bacteria. This review surveys fungal-derived phthalimidine metabolites published until the end of 2022, isolated from both terrestrial and aquatic or marine sources with emphasis on their unique chemistry, bioactivities, biogenesis and taxonomic classification. Their unique chemistry and diverse bioactivities (including antiviral, antiproliferative, antioxidant and antimicrobial) provide a chemical library with high medicinal potential, representing a treasure trove for synthetic chemists. Graphical Abstract

Correction: Seed Priming with Iron Oxide Nanoparticles Ameliorates As Toxicity by Decreasing Organic Acid Exudation Pattern and Modulating Specific Gene Expression in Rapeseed (Brassica napus L.) - Rana M. Alshegaihi; Manar Fawzi Bani Mfarrej; Aishah Alatawi; Khairiah Mubarak Alwutayd; Salem Albalawi; Saba Saleem; Muhammad Hamzah Saleem; Wajiha Sarfraz; Shafaqat Ali; Amany H. A. Abeed (Journal of Plant Growth Regulation, 2024)

Seed Priming with Iron Oxide Nanoparticles Ameliorates As Toxicity by Decreasing Organic Acid Exudation Pattern and Modulating Specific Gene Expression in Rapeseed (Brassica napus L.) - Rana M. Alshegaihi; Manar Fawzi Bani Mfarrej; Aishah Alatawi; Khairiah Mubarak Alwutayd; Salem Albalawi; Saba Saleem; Muhammad Hamzah Saleem; Wajiha Sarfraz; Shafaqat Ali; Amany H. A. Abeed (Journal of Plant Growth Regulation, 2024)

Gingerol nanoparticles attenuate complete Freund adjuvant-induced arthritis in rats via targeting the RANKL/OPG signaling pathway - Rida Siddique; Faqir Muhammad; Muhammad Naeem Faisal; Bushra Akhtar; Ammara Saleem; Shaneel Kousar; Ali Sharif; Muhammad Saeed; Safwan Muhammad (Inflammopharmacology, 2024)

D﻿own-regulation of NF-κB signalling by methanolic extract of Viola odorata (L.) attenuated in vivo inflammatory and angiogenic responses - Farzana Andleeb; Mohamed Farouk Elsadek; Muhammad Asif; Khalid S. Al-Numair; Shafqat Rasul Chaudhry; Mohammad Saleem; Ashwaq Hamid Salem Yehya (Inflammopharmacology, 2024)

Investigation of therapeutic potential of the Il24-p20 fusion protein against breast cancer: an in-silico approach - Shahnila Qureshi; Nadeem Ahmed; Hafiz Muhammad Rehman; Muhammad Imran Amirzada; Fiza Saleem; Kainat Waheed; Afeefa Chaudhry; Iram Kafait; Muhammad Akram; Hamid Bashir (In Silico Pharmacology, 2024)

Can urea-coated fertilizers be an effective means of reducing greenhouse gas emissions and improving crop productivity? - Muhammad Umair Hassan; Huang Guoqin; Muhammad Saleem Arif; Muhammad Salman Mubarik; Haiying Tang; Huifang Xu; Binjuan Yang; Quan Zhou; Awais Shakoor (Journal of Environmental Management, 2024)

Impact of different range areas on behavior, welfare, and performance of Naked Neck chickens - Saba Zahid; Muhammad Usman; Hafiz Muhammad Ishaq; Muhammad Faizan Haider; Mian Mubashar Saleem; Usman Elahi; Murrawat Hussain; Hafiz Rao Abdul Latif; Kinza Saleem; Sohail Ahmad; Tarek Amin Ebeid (Tropical Animal Health and Production, 2024)

Uptake, Agglomeration, and Detoxification of Trace Metals and Metalloids in Plants - Babar Hussain; Aqleem Abbas; Aansa Rukya Saleem; Luqman Riaz; Shafeeq Ur Rahman; Shibin Liu; Shengyan Pu; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2024)

Coactive Application of Bacillus Mycoides PM35 and Calcium Oxide Nanoparticles Stimulate Gene Expression Responses in Maize (Zea Mays L.) under Chromium Stress - Arwa Abdulkreem AL-Huqail; Suliman Mohammed Suliman Alghanem; Sameera A. Alghamdi; Haifa Abdulaziz Sakit Alhaithloul; Sami Asir Al-Robai; Adel I. Alalawy; Fahad M. Alzuaibr; Abdulrahman Alasmari; Baber Ali; Muhammad Hamzah Saleem; Shah Fahad; Shafaqat Ali; et al. (Journal of Soil Science and Plant Nutrition, 2024)

Alleviating Drought Stress in Strawberry Plants: Unraveling the Role of Paclobutrazol as a Growth Regulator and Reducer of Oxidative Stress Induced by Reactive Oxygen and Carbonyl Species - Khansa Saleem; Muhammad Ahsan Asghar; Ali Raza; Kaiwen Pan; Abd Ullah; Hafiz Hassan Javed; Mahmoud F. Seleiman; Shakeel Imran; Sajid Mehmood Nadeem; Khurram Shehzad Khan; Junbo Du; Fei Xu; et al. (Journal of Plant Growth Regulation, 2024)

Fluorescence Spectroscopy Based Characterization of Pseudomonas Aeruginosa Suspension - Sana Imtiaz; Muhammad Saleem (Journal of Fluorescence, 2024)

The Cambrian sedimentology and reservoir properties of the hybrid Abbottabad Formation in the Kotli area, Sub-Himalaya, Pakistan: insights into the Proto-Tethys paleoenvironment - Syed Kamran Ali; Rafiq Ahmad Lashari; Ali Ghulam Sahito; George Kontakiotis; Hammad Tariq Janjuhah; Muhammad Saleem Mughal; Tariq Mahmood (Carbonates and Evaporites, 2024)

Role of ERG11 and MDR1 genes in cycloheximide and multidrug resistance in Candida species - Zill-e- Huma; Sidrah Saleem; Muhammad Imran; Syed Mohsin Raza; Kokab Jabeen; Faiqa Arshad (Brazilian Journal of Microbiology, 2024)

Fluorescence and Photophysical Properties of Anthracene and Phenanthrene in Water - Muhammad Farooq Saleem Khan; Mona Akbar; Jing Wu (Journal of Fluorescence, 2024)

Effects of Withania somnifera (L.) Dunal in acute pulmonary pathophysiology in a rat model of smoke-induced lung injury and role of IRS-1 and SOX-2 - Sana Saleem; Imran Mukhtar; Hanan Y. Aati; Humaira Muzaffar; Haseeb Anwar; Musaddique Hussain; Maqsood Ahmad; Muhammad Umair; Kashif-ur-Rehman Khan (South African Journal of Botany, 2024)

Biogenic iron oxide nanoparticles (Fe2O3 NPs) adeptly diminish leaf blight of Rosa chinensis by exhibiting higher expression of RcWRKY29 and increasing antioxidant enzymatic activities - Hira Saleem; Mahnoor Akbar; Maryam Anar; Hassan Javed Chaudhary; Muhammad Farooq Hussain Munis (South African Journal of Botany, 2024)

Long-term raw crop residue but not burned residue incorporation improved soil multifunctionality in semi-arid agroecosystems - Aqeel Ahmad; Muhammad Saleem Arif; Sher Muhammad Shahzad; Tahira Yasmeen; Awais Shakoor; Shahid Iqbal; Asam Riaz; Anjum Zahid; Stephen James Chapman (Soil and Tillage Research, 2024)

Multi-criteria decision-making techniques for groundwater potentiality mapping in arid regions: A case study of Wadi Yiba, Kingdom of Saudi Arabia - Nuaman Ejaz; Aftab Haider Khan; Muhammad Waqar Saleem; Amro Mohamed Elfeki; Khalil Ur Rahman; Sajjad Hussain; Safi Ullah; Songhao Shang (Groundwater for Sustainable Development, 2024)

Advances in Physiochemical and Molecular Mechanisms of Abiotic Stress Tolerance in Plants - Muhammad Hamzah Saleem; Manar Fawzi Bani Mfarrej; Khalid Ali Khan; Sezai Ercisli; Mohsen Mohamed Elsharkawy; Shah Fahad (Journal of Crop Health, 2024)

Microbiome analysis reveals alteration in water microbial communities due to livestock activities - Chang Xu; Sijia Lu; Yangji Cidan; Hongzhuang Wang; Guangming Sun; Muhammad Usman Saleem; Farid Shokry Ataya; Yanbin Zhu; Wangdui-Basang; Kun Li (Environmental Science and Pollution Research, 2024)

Synergistic effect of biochar with gypsum, lime, and farm manure on the growth and tolerance in rice plants under different salt-affected soils - Yousef Alhaj Hamoud; Talha Saleem; Muhammad Zia-ur-Rehman; Hiba Shaghaleh; Muhammad Usman; Muhammad Rizwan; Hesham F. Alharby; Amnah M. Alamri; Faisal Al-Sarraj; Nadiyah M. Alabdallah (Chemosphere, 2024)

Corrigendum to “Could soil microplastic pollution exacerbate climate change? A meta-analysis of greenhouse gas emissions and global warming potential” [Environ. Res. 252 (2024) 118945/ ER-23-14694R1] - Shahid Iqbal; Jianchu Xu; Muhammad Saleem Arif; Awais Shakoor; Fiona R. Worthy; Heng Gui; Sehroon Khan; Dengpan Bu; Sadia Nadir; Sailesh Ranjitkar (Environmental Research, 2024)

Could soil microplastic pollution exacerbate climate change? A meta-analysis of greenhouse gas emissions and global warming potential - Shahid Iqbal; Jianchu Xu; Muhammad Saleem Arif; Awais Shakoor; Fiona R. Worthy; Heng Gui; Sehroon Khan; Dengpan Bu; Sadia Nader; Sailesh Ranjitkar (Environmental Research, 2024)

Green synthesis, properties, and biomedical potential of gold nanoparticles: A comprehensive review - Zain Fatima; Ramsha Saleem; Rana Rashad Mahmood Khan; Maira Liaqat; Muhammad Pervaiz; Zohaib Saeed; Gulzar Muhammad; Muhammad Amin; Shahzad Rasheed (Biocatalysis and Agricultural Biotechnology, 2024)

Analyzing the Role of Changing Climate on the Variability of Intensity-Duration-Frequency Curve Using Wavelet Analysis - Syed Adnan Shah; Hamza Farooq Gabriel; Muhammad Waqar Saleem; Nuaman Ejaz; Songhao Shang; Deqiang Mao; Khalil Ur Rahman (Water Resources Management, 2024)

Bacteria-Based MnO Nanoparticles Alleviate Lead Toxicity in Tomato Seedling Through Improving Growth Attributes and Enhanced Gene Expression of Candidate Genes - Maryam Anar; Urooj Haroon; Asif Kamal; Kinza Tahir; Mahnoor Akbar; Farhana; Hira Saleem; Abdul Rehman; Hassan Javed Chaudhary; Muhammad Farooq Hussain Munis (Journal of Plant Growth Regulation, 2024)

Recent Development on Sensing Strategies for Small Molecules Detections - Muhammad Saleem; Muhammad Hanif; Muhammad Rafiq; Anser Ali; Hussain Raza; Song Ja Kim; Changrui Lu (Journal of Fluorescence, 2024)

Synthesis, Invitro Cytotoxic Activity and Optical Analysis of Substituted Schiff Base Derivatives - Muhammad Saleem; Abrar Hussain; Muhammad Hanif; Hufsa Ahmad; Salah Uddin Khan; Sajjad Haider; Muhammad Rafiq; Rizwan Nasir Paracha; Sang Hyun Park (Journal of Fluorescence, 2024)

Air pollution and climate change as grand challenges to sustainability - Afifa; Kashaf Arshad; Nazim Hussain; Muhammad Hamza Ashraf; Muhammad Zafar Saleem (Science of The Total Environment, 2024)

Florfenicol removal from veterinary pharmaceutical effluents: Tri-metallic zeolite 5A° for electrochemical oxidation and catalytic ceramic membrane separation - Amir Ikhlaq; Maryam Gull; Afnan Sajid; Khurram Saleem Joya; Muhammad Raashid; Osama Shaheen Rizvi; Zafar Masood; Salman Ahmed; Maryam Abid; Maham Hanif; Hafiz Abdul Aziz; Thamer Abdulhameed Al Johani; et al. (Journal of Environmental Chemical Engineering, 2024)

Methylotrophic bacteria from rice paddy soils: mineral-nitrogen-utilizing isolates richness in bulk soil and rhizosphere - Tabassum Yousaf; Fatima Saleem; Sahar Andleeb; Muhammad Ali; Muhammad Farhan Ul Haque (World Journal of Microbiology and Biotechnology, 2024)

Advancing Arsenic Toxicity Mitigation in Rice (Oryza sativa L.) with Rice Straw Biochar and Silicon: A Study on Morpho-Physio-Biochemical Responses - Khairiah Mubarak Alwutayd; Suliman Mohammed Suliman Alghanem; Dikhnah Alshehri; Muhammad Hamzah Saleem; Saddam Hussain; Baber Ali; Amany H. A. Abeed (Journal of Soil Science and Plant Nutrition, 2024)

Zinc Provisioned Enhancement of Manganese Use Efficiency Results in Differential Biomass and Grain Production in Two Rice Cultivars Grown in Clay Loam Soil - Faisal Nadeem; Rashid Mahmood; Muhammad Anwar-ul-Haq; Muhammad Sabir; Saifullah; Qingxu Ma; Chongwei Jin; Tayyaba Samreen; Muhammad Saleem Haider (Journal of Soil Science and Plant Nutrition, 2024)

Elevated Expression of YSL Genes and Enhanced Physiological Responses in Rice Subjected to Iron Application - Ammara Saleem; Asma Zulfiqar; Muhammad Zafar Saleem; Muhammad Hamzah Saleem; Shah Fahad (Journal of Plant Growth Regulation, 2024)

Evaluation of Bacillus spp. as biocontrol agents against chili leaf spot caused by Xanthomonas vesicatoria - Sadia Aziz; Saleem Akhtar Jamshed; Tariq Mukhtar; Gulshan Irshad; Shahzada Sohail Ijaz; Muhammad Usman Raja (Journal of Plant Diseases and Protection, 2024)

Sustainable production of bread wheat under terminal heat stress: an investigation of foliar selenium-mediated biochemical regulations in association with yield - Muhammad Shahid; Muhammad Farrukh Saleem; Amna Saleem; Muhammad Sarwar; Muhammad Aown Sammar Raza; Shakeel Ahmad Anjum; Arshad Hussain (Cereal Research Communications, 2024)

Effect of hydraulic retention time on wastewater treatment and microalgal growth at low light intensity - Ramsha Malik; Sahar Saleem; Muhammad Basharat; Muhammad Faraz Bhatti; Zeshan Sheikh (Algal Research, 2024)

Correction to: Fluorescence Spectroscopy Based Identification of Pseudomonas Aeruginosa and Escherichia Coli Suspensions - Sana Imtiaz; Muhammad Saleem (Journal of Fluorescence, 2024)

Morphological and molecular characterization of four Phytophthora species with the first report of Phytophthora lacustris from Pakistan - Muhammad Abdul Haq; Saleem Shahzad; Abdul Mubeen Lodhi; Abdul Qayoom Rajput (Plant Biosystems, 2024)

Unveiling the mechanisms of silicon-induced salinity stress tolerance in Panicum turgidum: Insights from antioxidant defense system and comprehensive metabolic and nutritional profiling - Nadiyah M. Alabdallah; Aisha Saud Al-Shammari; Khansa Saleem; Saleha S. AlZahrani; Ali Raza; Muhammad Ahsan Asghar; Abd Ullah; Muhammad Iftikhar Hussain; Jean Wan Hong Yong (South African Journal of Botany, 2024)

Assessment of water quality using entropy-weighted quality index, statistical methods and electrical resistivity tomography, Moti village, northern Pakistan - Umair Bin Nisar; Wajeeh ur Rehman; Saher Saleem; Kashif Taufail; Faizan ur Rehman; Muhammad Farooq; Siddique Akhtar Ehsan (Journal of Contaminant Hydrology, 2024)

Improving Multivariate Runoff Prediction Through Multistage Novel Hybrid Models - Muhammad Sibtain; Xianshan Li; Fei Li; Qiang Shi; Hassan Bashir; Muhammad Imran Azam; Muhammad Yaseen; Snoober Saleem; Qurat-ul-Ain (Water Resources Management, 2024)

Silicon and Titanium Dioxide Mitigate Copper Stress in Wheat (Triticum aestivum L.) Through Regulating Antioxidant Defense Mechanisms - Rana M. Alshegaihi; Muhammad Hamzah Saleem; Ammara Saleem; Baber Ali; Humera Aziz; Shah Fahad; Abed Alataway; Ahmed Z. Dewidar; Hosam O. Elansary (Journal of Plant Growth Regulation, 2024)

γ-Glutamyltranspeptidase (GGT) Sensitive Fluorescence Probes for Cancer Diagnosis; Brief Review - Muhammad Saleem; Muhammad Hanif; Muhammad Rafiq; Hussain Raza; Kim Song Ja; Changrui Lu (Journal of Fluorescence, 2024)

Efficacy of different blood meals for the mass rearing of Aedes aegypti (Diptera: Culicidae) population - Shahid Majeed; Muhammad Sufyan; Asim Abbasi; Muhammad Binyameen; Ramish Saleem; Wafa A. H. Alkherb; Shahla Faisal; Jamil Ijaz; Hira Hameed (International Journal of Tropical Insect Science, 2024)

Symmetrical Ligand’s Fabricated Porous Silicon Surface Based Photoluminescence Sensor for Metal Detection and Entrapment - Muhammad Saleem; Abrar Hussain; Salah Uddin Khan; Sajjad Haider; Ki Hwan Lee; Sang Hyun Park (Journal of Fluorescence, 2024)

Occurrence of natural enemies in maize and the predatory potential of selected arthropods against fall armyworm in Multan, Pakistan - Saleem Riaz; Muhammad Ishtiaq; Fawad Zafar Ahmad Khan; Ghulam Ali; Mirza Abid Mehmood; Muhammad Sohail Qamar Zaman (International Journal of Tropical Insect Science, 2024)

Fluorescence Spectroscopy Based Characterization of Flaxseed Oil - Muhammad Saleem; Naveed Ahmad (Journal of Fluorescence, 2024)

MAPK/NF-κB signaling mediates atrazine-induced cardiorenal syndrome and antagonism of lycopene - Fu-Wei Jiang; Jian-Ying Guo; Jia Lin; Shi-Yong Zhu; Xue-Yan Dai; Muhammad Asmat Ullah Saleem; Yi Zhao; Jin-Long Li (Science of The Total Environment, 2024)

Highly selective and effective oxidation of 5-hydroxymethylfurfural by Co-Ni based electrodeposited bimetallic oxide nanostructures - Ghazala Nawaz; Mahnoor Fatima; Zahoor Ahmad; Khurram Saleem Joya; Mohammed Ali Assiri; Syed Imran Abbas Shah; Farhat Yasmeen; Muhammad Naeem Khan (Fuel, 2024)

Bacillus safensis filtrate-based ZnO nanoparticles control black heart rot disease of apricot fruits by maintaining its soluble sugars and carotenoids - Farhana; Abu Bakr Umer Farooq; Urooj Haroon; Hira Saleem; Mahnoor Akbar; Maryam Anar; Muhammad Nawaz; Hassaan Ateeb Ahmad; Junaid Ahmed; Hassan Javed Chaudhary; Muhammad Farooq Hussain Munis (World Journal of Microbiology and Biotechnology, 2024)

Effect of different concentrations of resveratrol on nuclear maturation and in-vitro development competence of oocytes of Nili Ravi buffalo - Samar Wafa Kabeer; Amjad Riaz; Aziz Ul-Rahman; Rana Muhammad Shahbakht; Ahsan Anjum; Hafeez ur Rehman Ali Khera; Ali Haider; Faisal Riaz; Riffat Yasin; Muhammad Yaseen; Muhammad Saleem; Naheed Bano; et al. (Tropical Animal Health and Production, 2024)

Toxicological assessment of dietary exposure of polyethylene microplastics on growth, nutrient digestibility, carcass and gut histology of Nile Tilapia (Oreochromis niloticus) fingerlings - Muhammad Mahmood; Syed Makhdoom Hussain; Pallab K. Sarker; Shafaqat Ali; Muhammad Saleem Arif; Nadia Nazish; Danish Riaz; Nisar Ahmad; Bilal Ahamad Paray; Adan Naeem (Ecotoxicology, 2024)

Microorganism-mediated biodegradation for effective management and/or removal of micro-plastics from the environment: a comprehensive review - Hassan Zahid; Nimra Afzal; Muhammad Maaz Arif; Mahnoor Zahid; Samia Nawab; Malik Muhammad Qasim; Farhat Naseem Alvi; Sumbal Nazir; Ishrat Perveen; Naaz Abbas; Yasar Saleem; Sania Mazhar; et al. (Archives of Microbiology, 2024)

Retraction Note: Multifaceted role of natural sources for COVID-19 pandemic as marine drugs - Md.Mominur Rahman; Md.Rezaul Islam; Sheikh Shohag; Md.Emon Hossain; Muddaser Shah; Shakil khan shuvo; Hosneara Khan; Md.Arifur Rahman Chowdhury; Israt Jahan Bulbul; Md.Sarowar Hossain; Sharifa Sultana; Muniruddin Ahmed; et al. (Environmental Science and Pollution Research, 2024)

Ratiometric Fluorescence and Chromogenic Probe for Trace Detection of Selected Transition Metals - Muhammad Saleem; Abrar Hussain; Muhammad Rauf; Salah Uddin Khan; Sajjad Haider; Muhammad Hanif; Muhammad Rafiq; Sang Hyun Park (Journal of Fluorescence, 2024)

Does no-till crop management mitigate gaseous emissions and reduce yield disparities: An empirical US-China evaluation - Awais Shakoor; Elise Pendall; Muhammad Saleem Arif; Taimoor Hassan Farooq; Shahid Iqbal; Sher Muhammad Shahzad (Science of The Total Environment, 2024)

Depositional and diagenetic controls on reservoir properties of the lower Cambrian Khewra Sandstone, eastern salt range, Sub-Himalaya, Pakistan - Shoukat Husain Khan; Ying-Ming Sheng; Salvatore Critelli; Massimo Civitelli; Muhammad Saleem Mughal; Usman Basharat (Marine and Petroleum Geology, 2024)

Optimization of multi-stage micellar-enhanced flocculation process for removal of Levofloxacin hemihydrate in wastewater - Fiza Bukhtawar; Muhammad Usman; Atta Ul Haq; Muhammad Saeed; Atif Saleem (Journal of Water Process Engineering, 2024)

Identification and Annotation of the 21 Novel Sugar Cane (Saccharum officinarum) MicroRNA Clusters and Their Significant Biological, Molecular and Cellular Targets - Abdul Baqi; Samiullah; Muhammad Zafar Saleem; Muhammad Ayub; Shazia Saeed (Tropical Plant Biology, 2024)

Temporal profiling of physiological, histological, and transcriptomic dissection during auxin-induced adventitious root formation in tetraploid Robinia pseudoacacia micro-cuttings - Saleem Uddin; Muhammad Zeeshan Munir; Eduardo Larriba; José Manuel Pérez-Pérez; Sadia Gull; Tariq Pervaiz; Umer Mahmood; Zahid Mahmood; Yuhan Sun; Yun Li (Planta, 2024)

Vegetable Plant Canopy Inhibits Soil Urease Activity and Reduces NH3 Losses Under p-Phenylenediamine (PPD)-Coated Urea Application - Sarah Shakeel; Rashid Mahmood; Ammara Fatima; Faisal Nadeem; Sajid Ali; Muhammad Saleem Haider (Journal of Soil Science and Plant Nutrition, 2024)

A review on identification characters and IPM of wheat aphid by using non-conventional methods - Dilbar Hussain; Usama Saleem; Muhammad Asrar; Muhammad Saleem; Abdul Ghaffar; Saddam Hussain; Tayybah Shaheen; Mubshar Saleem (International Journal of Tropical Insect Science, 2024)

Fluorescence Spectroscopy Based Identification of Pseudomonas Aeruginosa and Escherichia Coli Suspensions - Sana Imtiaz; Muhammad Saleem (Journal of Fluorescence, 2024)

Correction to: Alleviation of cadmium toxicity in pea (Pisum sativum L.) through Zn−Lys supplementation and its effects on growth and antioxidant defense - Muhammad Hamzah Saleem; Abida Parveen; Shagufta Perveen; Naheed Akhtar; Fozia Abasi; Maria Ehsan; Habib Ali; Mohammad K. Okla; Ibrahim A. Saleh; Naser Zomot; Yasmeen A. Alwasel; Mostafa A. Abdel-Maksoud; et al. (Environmental Science and Pollution Research, 2024)

Emerging trends in wastewater treatment: Addressing microorganic pollutants and environmental impacts - Muhammad Hamzah Saleem; Manar Fawzi Bani Mfarrej; Khalid Ali Khan; Saif A. Alharthy (Science of The Total Environment, 2024)

Dietary solutions for aluminum embryotoxicity: A study in Danio rerio using spirulina and okra-spirulina diets - Erika Mariana García-Avalos; Leobardo Manuel Gómez-Oliván; María Dolores Hernández-Navarro; Muhammad Hamzah Saleem; Nely San Juan-Reyes; Gustavo Axel Elizalde-Velázquez; Karina Elisa Rosales-Pérez (Science of The Total Environment, 2024)

Foot and mouth disease (FMD) epidemiology in small ruminants by identifying antibodies for non-structural and structural proteins with a sequential screening approach: A cross-sectional study - Muhammad Shakeel Khaliq; Mobeen Sarwar; Farhat Nazir Awan; Halima Sadia; Aamir Saleem; Syed Abdul Khaliq; Muhammad Hassan Mushtaq; Mamoona Chaudhry; Abdul Rehman (Small Ruminant Research, 2024)

Utilizing thiourea-modified biochars to mitigate toxic metal pollution and promote mustard (Brassica campestris) plant growth in contaminated soils - Irfan Saleem; Samreen Riaz Ahmed; Altaf Hussain Lahori; Monika Mierzwa-Hersztek; Shella Bano; Ambreen Afzal; Maria Taj Muhammad; Madiha Afzal; Viola Vambol; Sergij Vambol; Zengqiang Zhang (Journal of Geochemical Exploration, 2024)

Novel active composite films based on carboxymethyl cellulose and sodium alginate incorporated with phycocyanin: Physico-chemical, microstructural and antioxidant properties - Hafiz Muhammad Saleem Akhtar; Ya Zhao; Li Li; Qilong Shi (Food Hydrocolloids, 2024)

Functionalized carbon 1D/2D nanomaterials for effective water desalination: Synthesis, applications and cost issues. An overview - Umar Noor; Muhammad Fayyaz Farid; Ammara Sharif; Amna Saleem; Zubair Nabi; Muhammad Furqan Mughal; Kiran Abbas; Toheed Ahmed (Desalination, 2024)

Theoretical and experimental explored tailored hybrid H+/O2– ions conduction: Bridged for high performance fuel cell and water electrolysis - Zuhra Tayyab; Sajid Rauf; Muhammad Bilal Hanif; Hafiz Imran Ahmad Qazi; Naveed Mushtaq; Martin Motola; Sining Yun; Chen Xia; Dmitry A. Medvedev; Muhammad Imran Asghar; Abdullah N. Alodhayb; Arshad Hussain; et al. (Chemical Engineering Journal, 2024)

An insights into emerging trends to control the threats of antimicrobial resistance (AMR): an address to public health risks - Ayesha Asghar; Aneeza Khalid; Zulqarnain Baqar; Nazim Hussain; Muhammad Zafar Saleem; Sairash; Komal Rizwan (Archives of Microbiology, 2024)

Nitric oxide reduces cadmium uptake in wheat (Triticum aestivum L.) by modulating growth, mineral uptake, yield attributes, and antioxidant profile - Muhammad Nawaz; Muhammad Hamza Saleem; Muhammad Rehan Khalid; Baber Ali; Shah Fahad (Environmental Science and Pollution Research, 2024)

Alleviation of cadmium toxicity in pea (Pisum sativum L.) through Zn−Lys supplementation and its effects on growth and antioxidant defense - Muhammad Hamzah Saleem; Abida Parveen; Shagufta Perveen; Naheed Akhtar; Fozia Abasi; Maria Ehsan; Habib Ali; Mohammad K. Okla; Ibrahim A. Saleh; Naser Zomot; Yasmeen A. Alwasel; Mostafa A. Abdel-Maksoud; et al. (Environmental Science and Pollution Research, 2024)

Combined exposure of PVC-microplastic and mercury chloride (HgCl2) in sorghum (Pennisetum glaucum L.) when its seeds are primed titanium dioxide nanoparticles (TiO2–NPs) - Arwa Abdulkreem AL-Huqail; Suliman Mohammed Suliman Alghanem; Haifa Abdulaziz Sakit Alhaithloul; Muhammad Hamzah Saleem; Amany H. A. Abeed (Environmental Science and Pollution Research, 2024)

Mitigating chromium toxicity in rice (Oryza sativa L.) via ABA and 6-BAP: Unveiling synergistic benefits on morphophysiological traits and ASA-GSH cycle - Khairiah Mubarak Alwutayd; Suliman Mohammed Suliman Alghanem; Rahaf Alwutayd; Sameera A. Alghamdi; Nadiyah M. Alabdallah; Rahmah N. Al-Qthanin; Wajiha Sarfraz; Noreen Khalid; Nayab Naeem; Baber Ali; Muhammad Hamzah Saleem; Sadia Javed; et al. (Science of The Total Environment, 2024)

Advances/Scope and prospects of g-C3N4 derived fascinating photocatalyst as a leading route towards solar energy adaption - Asif Hayat; Muhammad Sohail; Zeeshan Ajmal; Hala H. Abd El-Gawad; Djamel Ghernaout; Yas Al-Hadeethi; Saleem Raza; Yasin Orooji (Journal of Cleaner Production, 2024)

Synergistic effect of CuO and Sr doped g-C3N4 for CO2 photoreduction into hydrocarbon fuels - Adil Raza; Azhar Ali Haidry; Zhengjun Yao; Muhammad Farooq Saleem; Asma A. Alothman; Saikh Mohammad (Chemical Engineering Journal, 2024)

A comprehensive study on the synchronized outgoing longwave radiation and relative humidity anomalies related to global Mw ≥ 6.5 earthquakes - Munawar Shah; Muhammad Umar Draz; Tahir Saleem (Natural Hazards, 2024)

Coal fly ash supported Ag@Bi2WO6: A novel heterogeneous nanocomposite for effective sunlight driven photocatalytic degradation of dye - Muhammad Zubair Saleem; Nimra Nadeem; Muhammad Shahbaz; Nabil Al-Zaqri; Shahid Rasul; Saima Noreen; Muhammad Zahid; Imran shahid (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Performance comparison of a photosynthetic and mechanically aerated microbial fuel cell for wastewater treatment and bioenergy generation using different anolytes - Zia Ullah; Zeshan Sheikh; Waqas Qamar Zaman; Muhammad Zeeshan; Waheed Miran; Jiansheng Li; Muhammad Abdul Nasir Khan; Sahar Saleem; Shanza Shabbir (Journal of Water Process Engineering, 2023)

Vertical connectivity of microbiome and metabolome reveals depth-dependent variations across a deep cold-seep water column - Songfeng Liu; Ruiwen Hu; P.J. Strong; Muhammad Saleem; Zhengyuan Zhou; Zhiwen Luo; Yongjie Wu; Zhili He; Cheng Wang (Environmental Research, 2023)

Impact of different light intensities to Japanese quail eggs on hatching results and post-hatch performance - Shaheryar Ali; Shahid Sherzada; Muhammad Usman; Ehsaan Ullah Khan; Abd ur Rehman; Muhammad Faisal Riaz; Usman Elahi; Murrawat Hussain; Hafiz Rao Abdul Latif; Kinza Saleem; Sohail Ahmad (Tropical Animal Health and Production, 2023)

Effects of prenatal dichromatic light exposure on hatching results and post-hatch performance of Japanese quail - Muhammad Safwan; Shahid Mehmood; Shahid Sherzada; Muhammad Usman; Syed Ghulam Mohayud Din Hashmi; Shaheryar Ali; Abd ur Rehman; Muhammad Faisal Riaz; Usman Elahi; Murrawat Hussain; Hafiz Rao Abdul Latif; Kinza Saleem; et al. (Tropical Animal Health and Production, 2023)

Development of Aluminium (Al)-Tolerant Soybean Using Molecular Tools: Limitations and Future Directions - Adnan Rasheed; Anwar Ahmad Khan; Muhammad Nawaz; Athar Mahmood; Uzma Arif; Muhammad Umair Hassan; Javed Iqbal; Muhammad Hamzah Saleem; Basharat Ali; Shah Fahad (Journal of Plant Growth Regulation, 2023)

Appraisal of anti-arthritic potential of Coronopus didymus (L.) Sm. aqueous extract and its safety study in Wistar rats - Ammara Saleem; Huma Khalid; Muhammad Furqan Akhtar; Alam Zeb (Inflammopharmacology, 2023)

Curcuminoids-enriched extract and its cyclodextrin inclusion complexes ameliorates arthritis in complete Freund’s adjuvant-induced arthritic mice via modulation of inflammatory biomarkers and suppression of oxidative stress markers - Uzma Saleem; Zunera Chauhdary; Zunaira Bakhtawar; Jawaher Alqahtani; Maryam Farrukh; Ifat Alsharif; Tourki A. S. Baokbah; Muhammad Ajmal Shah; Renald Blundell; Pharkphoom Panichayupakaranant (Inflammopharmacology, 2023)

Attenuation of CFA-induced arthritis through regulation of inflammatory cytokines and antioxidant mechanisms by Solanum nigrum L. leaves extracts - Bazgha Gul; Rukhsana Anwar; Mohammad Saleem; Mobasher Ahmad; Muhammad Ihsan Ullah; Shahzad Kamran (Inflammopharmacology, 2023)

Curative potential of Populus ciliata Wall ex. Royle extract against adjuvant-induced arthritis and peripheral neuropathy in Wistar rats - Amna Tahir; Muhammad Furqan Akhtar; Ammara Saleem; Muhammad Naveed; Basiru Olaitan Ajiboye; Fareeha Anwar; Aslam Khan (Inflammopharmacology, 2023)

Transparency enhancement of supply chain capabilities through social media: a proposed hierarchical model - Sharfuddin Ahmed Khan; Muhammad Shujaat Mubarik; Syed Imran Zaman; Alessio Ishizaka; Kanwal Saleem (Environment, Development and Sustainability, 2023)

Inquiring the impact of rural–urban migration, construction sector, and agriculture irrigated land on environmental degradation: insights from urbanized Asian countries - Feng Guoru; Muhammad Haris Hanif; Usman Saleem Yousaf (Environmental Science and Pollution Research, 2023)

Unrivalled insight into potential biopharmaceutical application of Saussurea albescens (DC.) Sch.Bip.: Chemical profiling, antioxidant and enzyme inhibition activities and in silico studies - Muhammad Imran Tousif; Muhammad Saleem; Saba Tauseef; Mamona Nazir; Tahira Ruby; Reaz Uddin; Sharon Elaine D'souza; Muhammad Aleem Ashraf; Ghulam Mustafa Kamal; Jallat Khan; Gokhan Zengin (Biocatalysis and Agricultural Biotechnology, 2023)

Plant breeding for harmony between sustainable agriculture, the environment, and global food security: an era of genomics‐assisted breeding - Aqsa Hafeez; Baber Ali; Muhammad Ammar Javed; Aroona Saleem; Mahreen Fatima; Amin Fathi; Muhammad Siddique Afridi; Veysel Aydin; Mükerrem Atalay Oral; Fathia A. Soudy (Planta, 2023)

Deciphering the Impact of Acinetobacter sp. SG-5 Strain on Two Contrasting Zea mays L. Cultivars for Root Exudations and Distinct Physio-Biochemical Attributes Under Cadmium Stress - Saghir Abbas; Muhammad Tariq Javed; Muhammad Shahid; Kashif Tanwir; Muhammad Hamzah Saleem; Nabeel Khan Niazi (Journal of Plant Growth Regulation, 2023)

Fluorescence Spectroscopy for the Assessment of Microbial Load in UVC Treated Water - Sana Imtiaz; Shahzad Anwar; Laiq Zada; Hina Ali; M. Saeed Khurram; Azhar Saeed; Muhammad Saleem (Journal of Fluorescence, 2023)

Assessment of the phycosphere microbial dynamics of microbial community associated with red algae culture under different cultural conditions - Asadullah Gujar; Muhammmad Ahsan Asghar; Muneefah Abdullah Alenezi; Muhammad Saleem Kubar; Kashif Ali Kubar; Ali Raza; Khansa Saleem; Hafiz Hassan Javed; Abu Zar Ghafoor; Muhammad Iftikhar Hussain; Abd Ullah; Hongli Cui; et al. (Environment, Development and Sustainability, 2023)

The role of technological innovation, economic policy uncertainty, and poverty reduction in attaining environmental sustainability agenda: contextual evidence from developing South and East Asian Economies - Hummera Saleem; Muhammad Bilal Khan; Seyed Mohammadreza Mahdavian; Umar Nawaz Kayani (Environment, Development and Sustainability, 2023)

Occurrence and characterization of Alternaria alternata causing leaf spot of soybean (Glycine max) in Pakistan - Muhammad Ismail Buzdar; Nasim Ahmed; Muhammad Jawad Akbar Awan; Saleem. Ur-Rahman; Muhammad Abu Bakar Waqas; Ghulam Raza; Fathia Mubeen; Shahid Mansoor; Imran Amin (Journal of Plant Pathology, 2023)

Pharmacological and toxicological evaluation of methyl 4-hydroxy-2H-1,2-benzothiazine-3-carboxylate 1,1-dioxoide against haloperidol induced Parkinson like symptoms in animal model: In-vitro and in-vivo studies - Liaqat Hussain; Ina Masood; Matloob Ahmad; Muhammad Yasir Ali; Uzma Saleem; Musaddique Hussain; Syed Haroon Khalid; Zunera Chauhdary (Toxicology and Applied Pharmacology, 2023)

Reducing SDG complexity and informing environmental management education via an empirical six-dimensional model of sustainable development - Steven J. Greenland; Muhammad Saleem; Roopali Misra; Ninh Nguyen; Jon Mason (Journal of Environmental Management, 2023)

Fabrication of a novel nanocomposite (TiO2/WO3/V2O5) by hydrothermal method as catalyst for hazardous waste treatment - Umer Younas; Awais Ahmad; Aftab Islam; Faisal Ali; Muhammad Pervaiz; Aimon Saleem; Muhammad Waseem; Ahmed Muteb Aljuwayid; Mohamed A. Habila; Salman Raza Naqvi (Fuel, 2023)

Comparative evaluation of different moulting methods on productive performance, egg quality, and antibody response of leghorn hens - Amir Saeed; Shahid Mehmood; Muhammad Shahid Zahoor; Ehsaan Ullah Khan; Muhammad Usman; Syed Ghulam Mohayud Din Hashmi; Kinza Saleem; Sohail Ahmad (Tropical Animal Health and Production, 2023)

Administration of α-lipoic acid and silymarin attenuates aggression by modulating endocrine, oxidative stress and inflammatory pathways in mice - Adnan Karim; Fareeha Anwar; Uzma Saleem; Saniya Fatima; Tariq Ismail; Ahmad J. Obaidullah; Rana O. Khayat; Moneerah J. Alqahtani; Ifat Alsharif; Haroon Khan; Celia Vargas-De-La-Cruz; Muhammad Ajmal Shah (Metabolic Brain Disease, 2023)

Metabolomics Analysis Reveals Soybean Node Position Influence on Metabolic Profile of Soybean Seed at Various Developmental Stages - Dennis Takpah; Muhammad Ahsan Asghar; Ali Raza; Hafiz Hassan Javed; Abd Ullah; Xiangqing Huang; Khansa Saleem; Cong-Wei Xie; Xinli Xiao; Kyei Sarpong Clement; Muhammad Umer Farooq; Wenyu Yang; et al. (Journal of Plant Growth Regulation, 2023)

A systematic review of physiological signals based driver drowsiness detection systems - Adil Ali Saleem; Hafeez Ur Rehman Siddiqui; Muhammad Amjad Raza; Furqan Rustam; Sandra Dudley; Imran Ashraf (Cognitive Neurodynamics, 2023)

Sustainable production of bread wheat using laser land levelling and sowing methods as potent regulators of carbon sequestration, fuel consumption and water use in the arid environment of Bahawalpur, Pakistan - Muhammad Shahid; Muhammad Farrukh Saleem; Amna Saleem; Shakeel Ahmad Anjum; Arshad Hussain (Irrigation and Drainage, 2023)
Excessive use of water in wheat is associated with high fuel consumption and the emission of carbon dioxide into the environment. This study was conducted with the objectives to decrease water use and the associated fuel consumption and carbon dioxide emissions and to improve the productivity of wheat on a sustainable basis using LASER levelling and sowing methods as potent modulators of these adversities. The experiment was conducted in the research area of the Agronomic Research Station Bahawalpur over 3 years using a split‐plot experimental design and four replications. Treatments contained LASER levelling in the main plot (L 0 = no LASER levelling, L 1 = LASER levelling) and sowing methods in split plots (S 1 = broadcast, S 2 = ridge sowing and S 3 = drill sowing). Less water use, fuel consumption and emission of carbon dioxide were quantified under ‘LASER levelling’ and under ‘ridge sowing’ compared to other treatments. Regarding wheat crop productivity, the same treatment combination (LASER levelling and ridge sowing) resulted in more fertile tillers, grains per spike, 1000‐grain weight and grain yield. Therefore, we concluded that ‘LASER levelling’ and ‘ridge sowing’ have the potential to reduce the cost involved and environmental pollution (by reducing fuel consumption) and improve water use efficiency, grain yield and yield components of wheat compared to other treatments. Moreover, strong negative associations of water use, fuel consumption and carbon dioxide emissions with the grain yield of wheat were recorded.

Retraction Note: Attenuating effect of Prosopis cineraria against paraquat-induced toxicity in prepubertal mice, Mus musculus - Muhammad Furqan Akhtar; Muhammad Omer Mehal; Ammara Saleem; Ahmad El Askary; Mohamed M. Abdel-Daim; Fareeha Anwar; Muhammad Ayaz; Alam Zeb (Environmental Science and Pollution Research, 2023)

Potential application of melatonin in reducing boron toxicity in rice seedlings through improved growth, cell wall composition, proline, and defense mechanisms - Xinyu Li; Muhammad Kamran; Muhammad Hamzah Saleem; Abdullah Ahmed Al-Ghamdi; Fahad M. Al-Hemaid; Mohamed S. Elshikh; Shaopeng Zhao; Muhammad Riaz (Chemosphere, 2023)

Alleviation of arsenic toxicity-induced oxidative stress in lemon grass by methyl jasmonate - Khansa Saleem; Muhammad Ahsan Asghar; Hafiz Hassan Javed; Ali Raza; Mahmoud F. Seleiman; Abd Ullah; Altafur Rahman; Sufyan Iqbal; Aamir Hanif; Shakeel Imran; Sajid Mahmood Nadeem; Junbo Du; et al. (South African Journal of Botany, 2023)

Molecular weight of dissolved organic matter determines its interactions with microbes and its assembly processes in soils - Pengfa Li; Meng Wu; Ting Li; Alex J. Dumbrell; Muhammad Saleem; Lu Kuang; Lu Luan; Shuang Wang; Zhongpei Li; Jiandong Jiang (Soil Biology and Biochemistry, 2023)

Microplastic contamination from surface waters and commercially valuable fishes of Karachi Coast, Pakistan - Nazia Arshad; Muhammad Mansoor Alam; Mazliham Bin Mohd Su’ud; Sobia Imran; Tooba Siddiqui; Khadija Saleem; Adnan Bashir; Atia Batool (Regional Studies in Marine Science, 2023)

Enhancing thermal efficiency and durability of sintered clay bricks through incorporation of polymeric waste materials - Ertugrul Erdogmus; Mucahit Sutcu; Osman Gencel; Syed Minhaj Saleem Kazmi; Muhammad Junaid Munir; Pedro Munoz Velasco; Togay Ozbakkaloglu (Journal of Cleaner Production, 2023)

Ginsenosides in cancer: Targeting cell cycle arrest and apoptosis - Muhammad Ajmal Shah; Syed Muhammad Abuzar; Kainat Ilyas; Irtaza Qadees; Momna Bilal; Rimsha Yousaf; Roaa Mohammed Tahir Kassim; Azhar Rasul; Uzma Saleem; Maria Silvana Alves; Haroon Khan; Renald Blundell; et al. (Chemico-Biological Interactions, 2023)

Unprecedented wildfires in Canada and transboundary effects of carbon monoxide pollution - Awais Shakoor; Taimoor Hassan Farooq; Muhammad Saleem Arif; Sher Muhammad Shahzad (Natural Hazards, 2023)

Comprehensive insights into the regulatory mechanisms of lncRNA in alkaline-salt stress tolerance in rice - Obaid Ur Rehman; Muhammad Uzair; Muhammad Shahbaz Farooq; Bilal Saleem; Safira Attacha; Kotb A. Attia; Umer Farooq; Sajid Fiaz; Wael. H. El-Kallawy; Itoh Kimiko; Muhammad Ramzan Khan (Molecular Biology Reports, 2023)

Effect of heterologous platelet-rich plasma on liver and modulation of glucose metabolism and Wnt signalling pathways in diabetic mice - Amin Arif; Adil Farooq; Muddasir Hassan Abbasi; Muhammad Babar Khawar; Tasleem Akhtar; Humaira Allay Ali; Mehreen Anjum; Rabia Mehmood; Tayyaba Saleem; Nadeem Sheikh (Molecular Biology Reports, 2023)

Does Exogenous Selenium Elicited Biochemical Regulations Make Economic Improvements in Terminally Heat-Stressed Bread Wheat? An Evidence from Marginal Analysis - Muhammad Shahid; Muhammad Farrukh Saleem; Amna Saleem; Muhammad Sarwar; Bao-Luo Ma; Shakeel Ahmad Anjum; Arshad Hussain (Journal of Soil Science and Plant Nutrition, 2023)

Interactions of Metal‐Based Engineered Nanoparticles with Plants: An Overview of the State of Current Knowledge, Research Progress, and Prospects - Abdul Wahab; Asma Munir; Muhammad Hamzah Saleem; Mukhtar Iderawumi AbdulRaheem; Humera Aziz; Manar Fawzi Bani Mfarrej; Gholamreza Abdi (Journal of Plant Growth Regulation, 2023)

Phenolic Compounds as a Quality Determinant of Grapes: A Critical Review - Muhammad Shahab; Sergio Ruffo Roberto; Muhammad Adnan; Shah Fahad; Renata Koyama; Muhammad Hamzha Saleem; Jamal Nasar; Shah Saud; Shah Hassan; Taufiq Nawaz (Journal of Plant Growth Regulation, 2023)

Polyoxyethylene Lauryl Ether (Brij-35) and Poloxamer 407–Based Non-ionic Surfactant Vesicles for Dissolution Enhancement of Tacrolimus - Razia Hanif; Muhammad Imran Khan; Asadullah Madni; Muhammad Furqan Akhtar; Muhammad Farhan Sohail; Ammara Saleem; Mubashar Rehman; Sufyan Junaid Usmani; Aslam Khan; Athar Masood (Journal of Pharmaceutical Innovation, 2023)

Thermal Effects on the Quality Parameters of Extra Virgin Olive Oil Using Fluorescence Spectroscopy - Areeba Ansar; Naveed Ahmad; Mha Albqmi; Muhammad Saleem; Hina Ali (Journal of Fluorescence, 2023)

Quality Analysis of Canola and Mustard Oil Using Fluorescence Spectroscopy - Muhammad Saleem; Hina Ali; M. Bilal; Babar M. Atta; Naveed Ahmad (Journal of Fluorescence, 2023)

Effective citric acid and EDTA treatments in cadmium stress tolerance in pepper (Capsicum annuum L.) seedlings by regulating specific gene expression - Rana M. Alshegaihi; Manar Fawzi Bani Mfarrej; Muhammad Hamzah Saleem; Abida Parveen; Khawaja Shafique Ahmad; Baber Ali; Amany H.A. Abeed; Dikhnah Alshehri; Sameera A. Alghamdi; Suliman M.S. Alghanem; Javeed Ahmad Lone; Tarek M.A. Soliman; et al. (South African Journal of Botany, 2023)

Diosgenin, a steroidal sapogenin, arrests arthritis through modulation of inflammatory cytokines and oxidative stress biomarkers in Wistar rats - Maira Javed; Ammara Saleem; Muhammad Furqan Akhtar (Inflammopharmacology, 2023)

Anti-inflammatory mechanisms of eucalyptol rich Eucalyptus globulus essential oil alone and in combination with flurbiprofen - Bushra Arooj; Sajid Asghar; Mohammad Saleem; Syed Haroon Khalid; Muhammad Asif; Tahir Chohan; Ikram Ullah Khan; Hafiz Muhammad Zubair; Hafiza Sidra Yaseen (Inflammopharmacology, 2023)

Chrysin, a 5,7-dihydroxyflavone restrains inflammatory arthritis in rats via subsiding oxidative stress biomarkers and inflammatory cytokines - Afnan Afnan; Ammara Saleem; Muhammad Furqan Akhtar (Inflammopharmacology, 2023)

Phytochemical, biological, and in-silico analysis of Colutea armata Hemsl. & Lace: A possible source of bioactive natural compounds - Ayisha Khalid; Samina Afzal; Farhan Abbas; Iftikhar Afzal; Muhammad Iqbal; Sarfraz Ahmad; Siddique Akber Ansari; Hamad M. Alkahtani; Tahir Ali Chohan; Umair Khurshid; Hammad Saleem; Carlos Leonardo Cespedes-Acuna (South African Journal of Botany, 2023)

Seismic risk assessment and hotspots prioritization: a developing country perspective - Rehan Asad; Muhammad Qaiser Saleem; Muhammad Salman Habib; Nadeem Ahmad Mufti; Shaker Mahmood Mayo (Natural Hazards, 2023)

Hydrogen Peroxide Promotes Terminal Heat Stress Recovery in Wheat by Strengthening Leaf Physiological Functioning - Muhammad Sarwar; Muhammad Farrukh Saleem; Siraj Ahmed; Hamza Maqsood; Saddam Hussain; Muhammad Ashfaq Wahid; Muhammad Kashif Munir; Muhammad Zafar; Najeeb Ullah; Ali Khoddami (Journal of Plant Growth Regulation, 2023)

Unveiling the genomic potential of a novel thermostable glycoside hydrolases producing Neobacillus sedimentimangrovi UE25 - Uroosa Ejaz; Faizan Saleem; Rozina Rashid; Khwaja Ali Hasan; Muhammad Noman Syed; Muhammad Sohail (Antonie van Leeuwenhoek, 2023)

Principles and Applicability of Integrated Remediation Strategies for Heavy Metal Removal/Recovery from Contaminated Environments - Mohammed Alsafran; Muhammad Hamzah Saleem; Hareb Al Jabri; Muhammad Rizwan; Kamal Usman (Journal of Plant Growth Regulation, 2023)
Contamination of agricultural soils with heavy metals present lethal consequences in terms of diverse ecological and environmental problems that entail entry of metal in food chain, soil deterioration, plant growth suppression, yield reduction and alteration in microbial community. Metal polluted soils have become a major concern for scientists around the globe. In more recent times, armed with new knowledge and understanding, removal of heavy metals using different applications has emerged as a solution for waste treatment and contaminant remediation in water and soil. However, the description of metal toxicity to the plants and its removal and degradation from the soil is limited. There are a number of reports in the literature where PGP bacterial inoculation and various chelating agents improves metal accumulation and it’s detoxification in different plant parts without influencing plant growth. Therefore, there is a need to select some useful chemicals which possess the potential to improve plant growth as well as expedite the phytoremediation of metals. In this review, we have discussed the mechanisms possessed by different chelating agents to promote plant growth and phytoremediation of metals. We anticipate that this analysis of interconnected systems will lead to the discovery of new research fields.

Pterostilbene reduces the progression of atopic dermatitis via modulating inflammatory and oxidative stress biomarkers in mice - Yasmin Bangash; Ammara Saleem; Muhammad Furqan Akhtar; Fareeha Anwar; Bushra Akhtar; Ali Sharif; Muhammad Imran Khan; Aslam Khan (Inflammopharmacology, 2023)

Cassia absus-mediated upregulation of IL-4, IL-10 and downregulation of IL-1β, IL-6, TNF- α, NF-κB, IFN-γ in CFA-induced arthritis model - Bazgha Gul; Rukhsana Anwar; Mohammad Saleem; Afifa Noor; Muhammad Ihsan Ullah (Inflammopharmacology, 2023)

Adverse health effects and mechanisms of microplastics on female reproductive system: a descriptive review - Vishal Afreen; Kanza Hashmi; Rimsha Nasir; Ammara Saleem; Muhammad Imran Khan; Muhammad Furqan Akhtar (Environmental Science and Pollution Research, 2023)

Zinc oxide nanoparticles coated urea enhances nitrogen efficiency and zinc bioavailability in wheat in alkaline calcareous soils - Shaiza Amin; Tariq Aziz; Muhammad Zia-ur-Rehman; Ifra Saleem; Muhammad Rizwan; Ambreen Ashar; Hafiz Adnan Mussawar; Muhammad Aamer Maqsood (Environmental Science and Pollution Research, 2023)

Salt ion mediated changes in biochemical and anatomical characteristics of Brassica napus can be countered with Moringa Leaf extract - Noreen Akhter; Aqsa Noreen; Saima Saifullah; Ali Noman; Muhammad Muslim Shahnaz; Puleng M. Letuma; Abida Kausar; Maham Siddique; Mohamed Hashem; Saad Alamri; Omar Mahmoud Al-zoubi; Muhammad Saleem; et al. (South African Journal of Botany, 2023)

Superior leaf physiological performance contributes to sustaining the final yield of cotton (Gossypium hirsutum L.) genotypes under terminal heat stress - Muhammad Sarwar; Muhammad Farrukh Saleem; Najeeb Ullah; Asjad Ali; Brian Collins; Muhammad Shahid; Muhammad Kashif Munir; Sang-Min Chung; Manu Kumar (Physiology and Molecular Biology of Plants, 2023)

Improving the Spike Initiation and Flowering Stage Heat Tolerance in Bread Wheat Through Foliar Application of Potassium - Muhammad Shahid; Muhammad Farrukh Saleem; Amna Saleem; Muhammad Sarwar; Arshad Hussain (Journal of Plant Growth Regulation, 2023)

Performance assessment of gridded climatic data and modeling spatial accuracy ranking matrix for gridded precipitation using a new pixel-based approach: a district-wise case study of Punjab - Muhammad Usman Saleem; Mian Sohail Akram (Arabian Journal of Geosciences, 2023)

A comprehensive review on the botany, traditional uses, phytochemistry, pharmacology and toxicity of Anagallis arvensis (L).: A wild edible medicinal food plant - Hammad Saleem; Umair Khurshid; Muhammad Imran Tousif; Sirajudheen Anwar; Nasser A. Awadh Ali; Mohamad Fawzi Mahomoodally; Nafees Ahemad (Food Bioscience, 2023)

Effect of Metals or Trace Elements on Wheat Growth and Its Remediation in Contaminated Soil - Iqbal Hussain; Sunnia Afzal; Muhammad Arslan Ashraf; Rizwan Rasheed; Muhammad Hamzah Saleem; Aishah Alatawi; Farukh Ameen; Shah Fahad (Journal of Plant Growth Regulation, 2023)

Impact of background colorations on growth, movement behavior, and some body physiological factors of Nile tilapia, Oreochromis niloticus - Ahmad Waheed; Hina Naz; Muhammad Wajid; Muhammad Saleem Khan (Fish Physiology and Biochemistry, 2023)

Spatiotemporal characteristics of meteorological drought variability and trends (1981–2020) over South Asia and the associated large-scale circulation patterns - Irfan Ullah; Xieyao Ma; Jun Yin; Abubaker Omer; Birhanu Asmerom Habtemicheal; Farhan Saleem; Vedaste Iyakaremye; Sidra Syed; Muhammad Arshad; Mengyang Liu (Climate Dynamics, 2023)

Seed-borne Curvularia lunata deteriorating seed health and germination of soybean - Muhammad Ismail Buzdar; Muhammad Jawad Akbar Awan; Saleem Ur Rahman; Rubab Zahra Naqvi; Ghulam Raza; Shahid Mansoor; Imran Amin (Biologia, 2023)

Reproductive and metabolic toxic effects of polystyrene microplastics in adult female Wistar rats: a mechanistic study - Anam Saeed; Muhammad Furqan Akhtar; Ammara Saleem; Bushra Akhtar; Ali Sharif (Environmental Science and Pollution Research, 2023)

Sensitive or tolerant functional microorganisms under cadmium stress: suggesting potential specific interaction network characteristics in the rhizosphere system of karst potato - Fulin Zhao; Muhammad Saleem; Zhao Xie; Xiaoliao Wei; Tengbing He; Guandi He (Environmental Science and Pollution Research, 2023)

Algae extract delamination of molybdenum disulfide and surface modification with glycidyl methacrylate and polyaniline for the elimination of metal ions from wastewater - Saleem Raza; Muhammad Usman Hameed; Ehsan Ghasali; Asif Hayat; Yasin Orooji; Hongjun Lin; Ceren Karaman; Fatemeh Karimi; Nevin Erk (Environmental Research, 2023)

Molecular evidence of Ehrlichia canis, associated risk factors and hematobiochemical analysis in client owned and shelter cats of Pakistan - Syed Nazar Abbas; Muhammad Ijaz; Rao Zahid Abbas; Muhammad Hassan Saleem; Asim Khalid Mahmood (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

The curative and mechanistic acumen of curcuminoids formulations against haloperidol induced Parkinson’s disease animal model - Uzma Saleem; Sundas Khalid; Zunera Chauhdary; Fareeha Anwar; Muhammad Ajmal Shah; Ifat Alsharif; Ahmad O. Babalghith; Rana O. Khayat; Aishah E. Albalawi; Tourki A. S. Baokbah; Maryam Farrukh; Celia Vargas-De-La-Cruz; et al. (Metabolic Brain Disease, 2023)

Silicon Enhances Morpho–Physio–Biochemical Responses in Arsenic Stressed Spinach (Spinacia oleracea L.) by Minimizing Its Uptake - Muhammad Hamzah Saleem; Manar Fawzi Bani Mfarrej; Aishah Alatawi; Sahar Mumtaz; Muhammad Imran; Muhammad Arslan Ashraf; Muhammad Rizwan; Kamal Usman; Parvaiz Ahmad; Shafaqat Ali (Journal of Plant Growth Regulation, 2023)

Floating Treatment Wetlands (FTWs) is an Innovative Approach for the Remediation of Petroleum Hydrocarbons-Contaminated Water - Manar Fawzi Bani Mfarrej; Xiukang Wang; Muhammad Fahid; Muhammad Hamzah Saleem; Aishah Alatawi; Shafaqat Ali; Ghulam Shabir; Rehman Zafar; Muhammad Afzal; Shah Fahad (Journal of Plant Growth Regulation, 2023)

Manipulation of plant growth stimulants on plant morphology, phenology, and disease incident of Gossypium hirsutum L. under various thermal regimes - Muhammad Sarwar; Muhammad Farrukh Saleem; Basharat Ali; Muhammad Sagir; Muhammad Bilal Tahir; Muhammad Ashfaq Wahid; Muhammad Shahid; Theodore M. Mwamba; Bilal Ahmad Khan; Hamza Maqsood (Arabian Journal of Geosciences, 2023)

Sedimentological and Petrographical Characterization of the Cambrian Abbottabad Formation in Kamsar Section, Muzaffarabad Area: Implications for Proto-Tethys Ocean Evolution - Syed Kamran Ali; Rafiq Ahmad Lashari; Ali Ghulam Sahito; George Kontakiotis; Hammad Tariq Janjuhah; Muhammad Saleem Mughal; Ahmer Bilal; Tariq Mehmood; Khawaja Umair Majeed (Journal of Marine Science and Engineering, 2023)
The current sedimentological and petrographical research of the Abbottabad Formation has been carried out in order to understand the formation and evolution of the Proto-Tethys Ocean during the Cambrian on the northern margin of the Indian Plate. The Muzaffarabad region is located east of the Upper Indus Basin and the southern part of the Hazara Kashmir Syntaxis. The geological history of the region varies from the Precambrian to the recent period. The Cambrian Abbottabad Formation is well exposed along the Hazara Kashmir Syntaxis at the core of the 500-m-thick Muzaffarabad anticline. The Abbottabad Formation is an unconformity-bounded allo-stratigraphic unit. It has an unconformable lower contact with the Late Precambrian Dogra Formation and an unconformable upper contact with the Paleocene Hangu Formation. The Abbottabad Formation has been divided into four lithofacies, from bottom to top, namely, thinly interbedded dolomite and shale, cherty-stromatolitic dolomite, oxidized limonitic-brecciated zone, and quartzite, with significant lithological changes. Petrographic studies revealed four types of dolomites: fine crystalline dolomite (Dol. I), dolomitic cryptocrystalline chert (Dol. II), algal mat-stromatolitic dolomite (Dol. III), and intraclastic-dolo-grain stone (Dol. IV). The mineral composition of dolostone was analyzed using X-ray diffraction (XRD) and found to be consistent with previous petrographic studies. The dolomite mineral content decreased from base to top, while chert increased towards the top. Elemental weight percentages through energy dispersive X-ray (EDX) analysis show different elements constitute the minerals found in the dolostone, as confirmed by petrographic and XRD analysis. Using outcrop data, facies information, and geochemical data, a modified depositional model of the Abbottabad Formation was developed. During the Early Cambrian period, the formation was deposited in a shallow subtidal to supratidal setting of the Proto-Tethys Ocean. The top of this deposit marks the Cambrian–Paleocene boundary. Because of the progressively coarsening outcrop sequences, this formation seems to be at the very top of the Proto-Tethys Ocean’s shallow marine system.

Photocatalytic degradation and electrochemical energy storage properties of CuO/SnO2 nanocomposites via the wet-chemical method - Azam Khan; Inam Ullah; Afaq Ullah Khan; Bilal Ahmad; Khadijah Mohammedsaleh Katubi; Norah Salem Alsaiari; Muhammad Saleem; Mohd Zahid Ansari; Jianjun Liu (Chemosphere, 2023)

Microbial cell membrane properties and intracellular metabolism regulate individual level microbial responses to acid stress - Hui Wei; Xiaoran Shan; Lizhu Wu; Jiaen Zhang; Muhammad Saleem; Jiayue Yang; Ziqiang Liu; Xuan Chen (Soil Biology and Biochemistry, 2023)

Unraveling the mutualistic interaction between endophytic Curvularia lunata CSL1 and tomato to mitigate cadmium (Cd) toxicity via transcriptomic insights - Sajjad Asaf; Rahmatullah Jan; Muhammad Aaqil Khan; Lubna; Abdul Latif Khan; Saleem Asif; Saqib Bilal; Waqar Ahmad; Muhammad Waqas; Kyung-Min Kim; Ahmed AL-Harrasi; In-Jung Lee (Science of The Total Environment, 2023)

Photocatalytic stimulation of peroxymonosulfate by novel MoO3@ZrO2 with Z-scheme heterojunction for diclofenac sodium degradation - Ghulam Abbas Ashraf; Raqiqa Tur Rasool; Rafiqat Ul Rasool; Muhammad Farooq Saleem; Jazib Ali; Djamel Ghernaout; Muhammad Hassan; Ahmed Muteb Aljuwayid; Mohamed A. Habila; Hai Guo (Journal of Water Process Engineering, 2023)

Antagonistic impact on cadmium stress in alfalfa supplemented with nano-zinc oxide and biochar via upregulating metal detoxification - Hafiz Abdul Kareem; Muhammad Adeel; Muhammad Azeem; Muhammad Arslan Ahmad; Noman Shakoor; Mahmood Ul Hassan; Sana Saleem; Annie Irshad; Junpeng Niu; Zhipeng Guo; Ćupina Branko; Roman Hołubowicz; et al. (Journal of Hazardous Materials, 2023)

Polyetherimide membrane with tunable porous morphology for safe lithium metal-based batteries - Arshad Hussain; Andleeb Mehmood; Adil Saleem; Muhammad K. Majeed; Waseem Raza; Rashid Iqbal; Sajid Rauf; Ali Saad; Yonggui Deng; Geng Luo; Kai Zong; Liu Wei; et al. (Chemical Engineering Journal, 2023)

Sarcococca saligna ameliorated D-galactose induced neurodegeneration through repression of neurodegenerative and oxidative stress biomarkers - Uzma Saleem; Zunera Chauhdary; Sumera Islam; Aimen Zafar; Rana O. Khayat; Norah A. Althobaiti; Ghulam Mujtaba Shah; Mohammed Alqarni; Muhammad Ajmal Shah (Metabolic Brain Disease, 2023)

Antidepressant activity of phytochemicals of Mangifera indica seeds assisted by integrated computational analysis - Uzma Saleem; Shafa Iman; Bashir Ahmad; Muhammad Ajmal Shah; Shabana Bibi; Mohammed Alqarni; Muhammad Saad Khan; Ghulam Mujtaba Shah; Haroon Khan; Reem Hasaballah Alhasani; Norah A. Althobaiti; Aishah E. Albalawi (Metabolic Brain Disease, 2023)

Individual and Synergic Effects of Phosphorus and Gibberellic Acid on Organic Acids Exudation Pattern, Ultra-Structure of Chloroplast and Stress Response Gene Expression in Cu-Stressed Jute (Corchorus Capsularis L.) - Aishah Alatawi; Xiukang Wang; Muhammad Hamzah Saleem; Muhammad Mohsin; Muzammal Rehman; Kamal Usman; Shah Fahad; Manar Fawzi Bani Mfarrej; Daniel Ingo Hefft; Shafaqat Ali (Journal of Plant Growth Regulation, 2023)

Towards developing resistance to chickpea chlorotic dwarf virus through CRISPR/Cas9-mediated gene editing using multiplexed gRNAs - Muniba Abid Munir Malik; Muhammad Saleem Haider; Ying Zhai; Muhammad Azmat Ullah Khan; Hanu R. Pappu (Journal of Plant Diseases and Protection, 2023)

Quercetin-loaded chitosan nanoparticles ameliorate adjuvant-induced arthritis in rats by regulating anti-oxidant enzymes and downregulating pro- and inflammatory cytokines - Abdul Hannan; Bushra Akhtar; Ali Sharif; Fozia Anjum; Imran Pasha; Ahrar Khan; Muhammad Furqan Akhtar; Ammara Saleem (Inflammopharmacology, 2023)

Zeolite amendment reduces lead accumulation and improves growth and yield in tomato plants irrigated with sewage water - Rashid Jawad; Aamir Nawaz; Shaghef Ejaz; Sajid Ali; Muhammad Shahzad Saleem; Hafiz Mohkum Hammad (Environmental Science and Pollution Research, 2023)

The role of economic growth, information technologies, and globalization in achieving environmental quality: a novel framework for selected Asian countries - Hummera Saleem; Muhammad Bilal Khan; Seyed Mohammadreza Mahdavian (Environmental Science and Pollution Research, 2023)

A review of waste management approaches to maximise sustainable value of waste from the oil and gas industry and potential for the State of Qatar - Muhammad Shahbaz; Naim Rashid; Junaid Saleem; Hamish Mackey; Gordon McKay; Tareq Al-Ansari (Fuel, 2023)

How does dolomite application affect the greenhouse gases emissions from the terrestrial environment? – A global synthesis - Muhammad Umair Hassan; Maria Batool; Taimoor Hassan Farooq; Muhammad Saleem Arif; Muhammad Aamer; Muhammad Ahmed Waqas; Gadah Albasher; Maryium Sajjad; Awais Shakoor (Fuel, 2023)

Electrically conductive Pt-MOFs for acidic oxygen reduction: Optimized performance via altering conjugated ligands - Rashid Iqbal; Sajjad Ali; Adil Saleem; Muhammad K. Majeed; Arshad Hussain; Sajid Rauf; Abdul Rehman Akbar; Hu Xu; Liang Qiao; Wei Zhao (Chemical Engineering Journal, 2023)

Synthesis, Characterization, Optical Properties, Molecular Modeling and Urease Inhibition Analysis of Organic Ligands and Their Metal Complexes - Muhammad Saleem; Muhammad Hanif; Muhammad Rafiq; Mubashir Hassan; Tehreem Tahir (Journal of Fluorescence, 2023)

Multiple begomoviruses infecting soybean; a case study in Faisalabad, Pakistan - Saleem U. Rahman; Ghulam Raza; Muhammad Zubair; Nasim Ahmed; Leslie L. Domier; Nousheen Jamil; Shahid Mansoor; Imran Amin (Biologia, 2022)

New trends in immunocastration and its potential to improve animal welfare: a mini review - Sohail Ahmed; Xunping Jiang; Guiqiong Liu; Amber Sadiq; Umar Farooq; Teketay Wassie; Ali Haider Saleem; Muhammad Zubair (Tropical Animal Health and Production, 2022)

In Silico Dissection and Expression Analysis of Sucrose Synthase Gene Family in Sugarcane - Muhammad Noman; Iqra Siddique; Bilal Saleem; Saiqa Ilyas; Shaukat Ali; Muhammad Ramzan Khan (Sugar Tech, 2022)

Exogenous Selenium as a Potent Modulator of Antioxidants, Osmo-protectants, Lipid Peroxidation, and Wheat Grain Yield Under Terminal Heat Stress - Muhammad Shahid; Muhammad Farrukh Saleem; Amna Saleem; Haroon Zaman Khan (Journal of Soil Science and Plant Nutrition, 2022)

Diospyros malabarica (Desr.) Kostel fruits extract attenuated acute and chronic inflammation through modulation of the expression of pro- and anti-inflammatory biomarkers in rat models - Saba Zia; Mohammad Saleem; Muhammad Asif; Khalid Hussain; Beenish Zia Butt (Inflammopharmacology, 2022)

Pterostilbene improves CFA-induced arthritis and peripheral neuropathy through modulation of oxidative stress, inflammatory cytokines and neurotransmitters in Wistar rats - Ayesha Amin; Muhammad Furqan Akhtar; Ammara Saleem; Ali Sharif; Shahid Shah; Muhammad Imran Khan; Fareeha Anwar; Ghulam Abbas; Hafiz Muhammad Zubair; Muhammad Farhan Sohail (Inflammopharmacology, 2022)

Are globalization, urbanization, and energy consumption cause carbon emissions in SAARC region? New evidence from CS-ARDL approach - Muhammad Azam; Ijaz Uddin; Saleem Khan; Muhammad Tariq (Environmental Science and Pollution Research, 2022)

Amelioration of lead toxicity by ascorbic acid in sugarcane (Saccharum officinarum L.) under in vitro condition - Yasmeen Saleem; Aamir Ali; Shagufta Naz; Muhammad Jamil; Naima Huma Naveed (Environmental Science and Pollution Research, 2022)

Petrofacies and diagenesis of Thanetian Lockhart Limestone in the Upper Indus Basin (Pakistan): implications for the Ceno-Tethys Ocean - Ahmer Bilal; Renchao Yang; Aiping Fan; Muhammad Saleem Mughal; Yang Li; Muhammad Basharat; Muhammad Farooq (Carbonates and Evaporites, 2022)

Sedimentological and diagenetic analysis of Early Eocene Margalla Hill Limestone, Shahdara area, Islamabad, Pakistan: implications for reservoir potential - Haroon Aziz; Jabir Hussain; Muhammad Tariq; Muhsan Ehsan; Salman Khurshid; Saleem Khan; Waleed Anwar (Carbonates and Evaporites, 2022)

Selection for resistance to pirimiphos-methyl, permethrin and spinosad in a field strain of Sitophilus oryzae: resistance risk assessment, cross-resistance potential and synergism of insecticides - Tiyyabah Khan; Hafiz Azhar Ali Khan; Muhammad Saleem Haider; Waheed Anwar; Adnan Akhter (Environmental Science and Pollution Research, 2022)

Sedimentology and Diagenesis of the Early–Middle Eocene Carbonate Deposits of the Ceno-Tethys Ocean - Ahmer Bilal; Renchao Yang; Muhammad Saleem Mughal; Hammad Tariq Janjuhah; Muhammad Zaheer; George Kontakiotis (Journal of Marine Science and Engineering, 2022)
An integrated study based on field observation, petrography, and scanning electron microscopy (SEM) on the Early–Middle Eocene carbonate rocks has been carried out, which were deposited in the Ceno-Tethys Ocean. The study area of the Yadgaar Section lies on the eastern margin of the Upper Indus Basin, Pakistan. The Early–Middle Eocene Margalla Hill Limestone and Chorgali Formation act as reservoir rocks in other parts of the basin and are also present in the Yadgaar Section. The lack of comprehensive study in this area makes these reservoir rocks highly attractive for sedimentological evaluations and future exploration of hydrocarbons. The Early–Middle Eocene carbonate rocks are divided into nine microfacies: dolomicritic foraminiferal mudstone–wackestone microfacies (EMI); green algae dominated, mixed foraminiferal wackestone–packstone microfacies (EMII); ostracod, green algae and gypsum dominating mudstone–wackestone microfacies (EMIII); algae and mixed foraminiferal wackestone–packstone microfacies (EMIV); Nummulites dominating mudstone–wackestone microfacies (EMV); algal limestone mudstone microfacies (EMVI); Assilina bed wackestone–packstone microfacies (EMVII); micritized larger benthic foraminiferal wackestone–packstone microfacies (EMVIII); and algal limestone, mudstone microfacies (EMIX). The transgressive-regressive environment in the Ceno-Tethys Ocean leads to the deposition of these microfacies in the platform interior, open marine platform, platform edge, platform margin reef, toe of the slope apron, arid–humid platform interior, platform edge, open marine platform interior, and restricted marine platform interior, respectively. Initial post-depositional diagenetic stages are identified from the base to the top of the strata by their respective cement types, i.e., the base–lower middle part of the strata demonstrates an eogenetic sub-stage with the appearance of drusy cement, the middle section indicates a mesogenetic sub-stage by the appearance of blocky cement, while the top portion again reveals an eogenetic sub-stage of diagenesis by the presence of drusy and blocky types of cement. The ascending–descending hierarchy of cement generations is directly proportional to the grade of diagenesis from the base to the top of the carbonate strata. Variable diagenetic effects on the various microfacies also increase the secondary porosity range and enhance the reservoir characteristics of the Formations. The presence of foraminifera microfossils determined that these carbonate formations date from the Early–Middle Eocene.

Biopesticides and insect pest management - Kanwal Hanif; Muhammad Zubair; Dilbar Hussain; Sikander Ali; Muhammad Saleem; Hafiz Azhar Ali Khan; Tamsila Nazir; Muhammad Waqas ul Hassan (International Journal of Tropical Insect Science, 2022)

hPSC gene editing for cardiac disease therapy - Amina Saleem; Muhammad Khawar Abbas; Yongming Wang; Feng Lan (Pflügers Archiv - European Journal of Physiology, 2022)

Characterization of Corn Oil Using Fluorescence Spectroscopy - Saud Abdullah; Muhammad Asif; Hina Ali; Raheel Ali; Muhammad Saleem (Journal of Fluorescence, 2022)

Bisphenol S induced dysregulations in liver; iron regulatory genes and inflammatory mediators in male Wistar rats - Shazia Ghafoor; Muddasir Hassan Abbasi; Muhammad Babar Khawar; Asima Tayyeb; Tayyaba Saleem; Isbah Ashfaq; Nadeem Sheikh (Environmental Science and Pollution Research, 2022)

Damage assessment of stored grain pests against rice grains types and wheat - Muhammad Waqar Hassan; Mohsin Ali Hashmi; Ghulam Sarwar; Zahid Mehmood; Warda Saleem; Muhammad Aslam Farooqi (International Journal of Tropical Insect Science, 2022)

P-wave minimum 1D velocity model for central and northern Pakistan - Riaz Ahmed Soomro; Saleem Iqbal; Muhammad Ali Shah; Talat Iqbal (Journal of Seismology, 2022)

Tumor necrosis factor-alpha, prostaglandin-E2 and interleukin-1β targeted anti-arthritic potential of fluvoxamine: drug repurposing - Haseeb Ahsan; Mahnoor Ayub; Hafiz Muhammad Irfan; Muhammad Saleem; Irfan Anjum; Ihtisham Haider; Awais Asif; Syed Qamar Abbas; Syed Shams ul Hulassan (Environmental Science and Pollution Research, 2022)

Point prevalence survey to estimate antimicrobial use in a tertiary care university hospital in Pakistan using WHO methodology: findings and implications - Muhammad Sharif; Sana Aslam; Zikria Saleem (Infectious Diseases, 2022)

Review on integrated disease and pest management of field crops - Muneer Abbas; Muhammad Saleem; Dilbar Hussain; Muhammad Ramzan; Muhammad Jawad Saleem; Sohail Abbas; Niaz Hussain; Muhammad Irshad; Khalid Hussain; Ghulam Ghouse; Mudassar Khaliq; Zubeda Parveen (International Journal of Tropical Insect Science, 2022)

Molybdenum Role in Nitrogen Bioavailability of Wheat-Soil System Using the Natural 15N Abundance Technique - Mohamed G. Moussa; Xuecheng Sun; Shaimaa El-Tohory; Abdelkader Mohamed; Muhammad Hamzah Saleem; Muhammad Riaz; Zhihao Dong; Lingzhi He; Chengxiao Hu; Marwa A. Ismael (Journal of Soil Science and Plant Nutrition, 2022)

Characterization and Utilization of Cow Manure Biochar as Soil Amendment for the Management of Northern Corn Leaf Blight - Misbah Batool Zahra; Bakhtawar Fayyaz; Zill-E-Huma Aftab; Adnan Akhter; Tehmina Bahar; Waheed Anwar; Muhammad Saleem Haider (Journal of Soil Science and Plant Nutrition, 2022)

Correction to: Receptiveness of soil bacterial diversity in relation to soil nutrient transformation and canopy growth in Chinese fir monoculture influenced by varying stand density - Taimoor Hassan Farooq; Uttam Kumar; Yao Yan; Muhammad Saleem Arif; Awais Shakoor; Muhammad Tayyab; Paresh H. Rathod; Muhammad Mohsin Altaf; Pengfei Wu (Trees, 2022)

Hyperspectral monitoring of soil urease activity under different water regulation - Chenbo Yang; Meichen Feng; Lifang Song; Binghan Jing; Yongkai Xie; Chao Wang; Mingxing Qin; Wude Yang; Lujie Xiao; Jingjing Sun; Meijun Zhang; Xiaoyan Song; et al. (Plant and Soil, 2022)

Promising role of polymeric nanoparticles in the treatment of rheumatoid arthritis - Rida Siddique; Malik Hassan Mehmood; Muhammad Haris; Ammara Saleem; Zunera Chaudhry (Inflammopharmacology, 2022)

The role of green growth, green financing, and eco-friendly technology in achieving environmental quality: evidence from selected Asian economies - Hummera Saleem; Muhammad Bilal Khan; Seyed Mohammadreza Mahdavian (Environmental Science and Pollution Research, 2022)

Distribution and Bioaccumulation of Essential and Toxic Metals in Tissues of Thaila (Catla catla) from a Natural Lake, Pakistan and Its Possible Health Impact on Consumers - Muhammad Saleem; Javed Iqbal; Zongbo Shi; Scott H. Garrett; Munir H. Shah (Journal of Marine Science and Engineering, 2022)
Although fish are often recommended as a component of a healthy diet, the environmental accumulation of heavy metals in many fish species has been of considerable concern for those weighing the nutritional health benefits against adverse toxic outcome of excess intake of toxic metals. This study aimed to determine the concentration of essential and toxic metals in the tissues of Catla catla in Mangla Lake and to assess the possible risk to the consumers. Fifty samples of Catla catla were collected from Mangla Lake, Mirpur, Azad Jammu and Kashmir, Pakistan and analyzed for eighteen metals including essential and trace metals. The measured range concentrations (µg/g, wet weight) in muscle tissues, in decreasing order, were: K (955–1632), Ca (550–2081), Na (449–896), Mg (129–312), Zn (61.2–215), Fe (11.6–26.8), Sr (2.60–9.27), Pb (1.72–7.81), Se (1.55–3.55), Co (0.12–4.08), Mn (1.04–4.33), Ni (0.69–3.06), Cu (0.88–2.78), Cr (0.45–1.88), As (0.67–1.58), Cd (0.28–0.56), Hg (0.17–0.57) and Li (0.12–0.38). The metal concentrations found in this study were comparatively higher than those reported in literature. A majority of the metals exhibited higher accumulation in gills compared with those in scales and muscles. Mean levels of Pb, As, Co, Mn, Cd, Cr and Zn in Catla catla muscle were found to be exceeding the international permissible limits for the safe human consumption. The condition factor (K), as an indicator of fish health status, indicated that Catla catla of Mangla Lake are in good health condition. The metal pollution index (MPI) of gills (27.9), scales (12.5) and muscle (7.57) indicated low contamination. Moreover, human health risk was evaluated using estimated weekly intake (EWI) and daily intake (EDI), target hazard quotient (THQ), hazard index (HI) and target cancer risk (TCR). Estimated weekly and daily intake values for As, Cd, Cr, Hg, Ni and Pb were higher than provisional permissible tolerable weekly intake and permissible tolerable daily intake while THQ for As, Cd, Cr, Hg, Pb, Se and Zn was higher than 1. The THQ for As, Hg and Pb was several folds higher than 1, indicative of lifetime non-carcinogenic health risks to the consumers. The hazard index indicated cumulative risk, which greatly increased with increasing fish consumption. Target cancer risk indicated that the people eating the Catla catla from Mangla Lake were exposed to As, Cd, Cr, Ni and Pb with a significant lifetime carcinogenic risk. In summary, consumption of Catla catla from this lake was found to be associated with an increased lifetime risk to the general health of the consumers.

Correction to: Multifaceted role of natural sources for COVID-19 pandemic as marine drugs - Md. Mominur Rahman; Md. Rezaul Islam; Sheikh Shohag; Md. Emon Hossain; Muddaser Shah; Shakil khan shuvo; Hosneara Khan; Md. Arifur Rahman Chowdhury; Israt Jahan Bulbul; Md. Sarowar Hossain; Sharifa Sultana; Muniruddin Ahmed; et al. (Environmental Science and Pollution Research, 2022)

RETRACTED ARTICLE: Multifaceted role of natural sources for COVID-19 pandemic as marine drugs - Md. Mominur Rahman; Md. Rezaul Islam; Sheikh Shohag; Md. Emon Hossain; Muddaser Shah; Shakil khan shuvo; Hosneara Khan; Md. Arifur Rahman Chowdhury; Israt Jahan Bulbul; Md. Sarowar Hossain; Sharifa Sultana; Muniruddin Ahmed; et al. (Environmental Science and Pollution Research, 2022)

Therapeutic potential of dopamine agonists in the treatment of type 2 diabetes mellitus - Md. Tanvir Kabir; Jannatul Ferdous Mitu; Raushanara Akter; Muhammad Furqan Akhtar; Ammara Saleem; Ahmed Al-Harrasi; Saurabh Bhatia; Md. Sohanur Rahman; Fouad Damiri; Mohammed Berrada; Md. Habibur Rahman (Environmental Science and Pollution Research, 2022)

Nexus between non-renewable energy production, CO2 emissions, and healthcare spending in OECD economies - Hummera Saleem; Muhammad Bilal Khan; Malik Shahzad Shabbir; Ghulam Yahya Khan; Muhammad Usman (Environmental Science and Pollution Research, 2022)

Investigation of Morchella esculenta and Morchella conica for their antibacterial potential against methicillin-susceptible Staphylococcus aureus, methicillin-resistant Staphylococcus aureus and Streptococcus pyogenes - Faiz Ul Haq; Muhammad Imran; Sidrah Saleem; Usman Aftab; Ayesha Ghazal (Archives of Microbiology, 2022)

Receptiveness of soil bacterial diversity in relation to soil nutrient transformation and canopy growth in Chinese fir monoculture influenced by varying stand density - Taimoor Hassan Farooq; Uttam Kumar; Yao Yan; Muhammad Saleem Arif; Awais Shakoor; Muhammad Tayyab; Paresh H. Rathod; Muhammad Mohsin Altaf; Pengfei Wu (Trees, 2022)

Circadian Variation in Activities of Blackbuck Under Captivity in Punjab, Pakistan - Zahid Farooq; Muhammad Iqbal; Muhammad Saleem Khan; Sana Asad; Muhammad Wajid (Proceedings of the Zoological Society, 2022)

Choline Chloride Mediates Chromium Tolerance in Spinach (Spinacia oleracea L.) by Restricting its Uptake in Relation to Morpho-physio-biochemical Attributes - Iqbal Hussain; Muhammad Hamzah Saleem; Sahar Mumtaz; Rizwan Rasheed; Muhammad Arslan Ashraf; Faisal Maqsood; Muzammal Rehman; Humaira Yasmin; Shakeel Ahmed; Muhammad Ishtiaq; Sana Anwar; Shafaqat Ali (Journal of Plant Growth Regulation, 2022)

Methotrexate-loaded biodegradable nanoparticles exert anti-arthritic effect by downregulating pro-inflammatory cytokines in Freund’s complete adjuvant-induced arthritic rats - Muhammad Usman Saleem; Faqir Muhammad; Ali Sharif; Muhammad Imran Arshad; Kanwal Akhtar; Yasir Javed; Bushra Akhtar (Inflammopharmacology, 2022)

Taurine modulates dynamics of oxidative defense, secondary metabolism, and nutrient relation to mitigate boron and chromium toxicity in Triticum aestivum L. plants - Muhammad Arslan Ashraf; Rizwan Rasheed; Iqbal Hussain; Muhammad Iqbal; Muhammad Umar Farooq; Muhammad Hamzah Saleem; Shafaqat Ali (Environmental Science and Pollution Research, 2022)

Teratological effects of titanium dioxide nanoparticles in mice embryo - Munir Ahmad; Muhammad Khalil Ahmad Khan; Khurram Shahzad; Naveed Ahmad; Munazza Parveen; Muhammad Saleem Khan (Environmental Science and Pollution Research, 2022)

Reducing nutrient uptake in okra weeds by suppressing their population through alligator weed compost mulch for better pod yield and quality - Asif Tanveer; Muhammad Sarwar; Muhammad Shahbaz Asghar; Muhammad Farrukh Saleem; Hamza Maqsood; Basharat Ali; Muhammad Kashif Munir; Muhammad Arshad; Rao Muhammad Ikram; Nabeel Ahmad Ikram; Muhammad Rizwan (Arabian Journal of Geosciences, 2022)

Habitat characterization of Aedes albopictus - Faisal Hafeez; Unsar Naeem-Ullah; Waseem Akram; Muhammad Arshad; Ayesha Iftikhar; Afifa Naeem; Muhammad Jawad Saleem (International Journal of Tropical Insect Science, 2022)

Susceptibility of Helicoverpa armigera Hübner (Lepidoptera: Noctuidae) on detached plant parts of transgenic and non-transgenic cotton - Muhammad Jawad Saleem; Faisal Hafeez; Qurban Ali; Asad Aslam; Muhammad Arshad; Dilbar Hussain; Ayesha Iftikhar; Afifa Naeem; Muhammad Saleem (International Journal of Tropical Insect Science, 2022)

Polystichum braunii ameliorates airway inflammation by attenuation of inflammatory and oxidative stress biomarkers, and pulmonary edema by elevation of aquaporins in ovalbumin-induced allergic asthmatic mice - Ammara Saleem; Afza Mubeen; Muhammad Furqan Akhtar; Alam Zeb (Inflammopharmacology, 2022)

Sarcococca saligna extract attenuates formaldehyde-induced arthritis in Wistar rats via modulation of pro-inflammatory and inflammatory biomarkers - Maryam Farrukh; Uzma Saleem; Muhammad Qasim; Maria Manan; Muhammad Ajmal Shah (Inflammopharmacology, 2022)

Observed changes in seasonal drought characteristics and their possible potential drivers over Pakistan - Irfan Ullah; Xieyao Ma; Jun Yin; Farhan Saleem; Sidra Syed; Abubaker Omer; Birhanu Asmerom Habtemicheal; Mengyang Liu; Muhammad Arshad (International Journal of Climatology, 2022)
Long‐term drought monitoring and its assessment are of great importance for meteorological disaster risk management. The recurrent spells of heat waves and droughts have severely affected the environmental conditions worldwide, including Pakistan. The present work sought to investigate the spatiotemporal changes in drought characteristics over Pakistan during Rabi and Kharif cropping seasons. The role of large‐scale circulation and interannual mode of climate variability is further explored to identify the physical mechanisms associated with droughts in the region. Monthly precipitation and temperature data (1983–2019) from 53 meteorological stations were used to study drought characteristics, using the standardized precipitation evapotranspiration index (SPEI). The nonparametric Mann–Kendall, Sen's Slope, and Sequential Mann–Kendall tests were applied on the drought index to determine the statistical significance and magnitude of the historical trend. The state‐of‐the‐art Bayesian Dynamic Linear model was further used to analyse large‐scale climate drivers of droughts, revealed an increase in drought severity, mostly over arid to semiarid regions for both cropping seasons. While temperature played a significant role in defining droughts over dry and hot seasons, rainfall is influential over the western disturbances influenced region. The analysis of atmospheric circulation patterns revealed that large‐scale changes in wind speed, air temperature, relative humidity, and geopotential height anomalies are the likely drivers of droughts in the region. We found that Niño4, sea surface temperature, and multivariate El Niño‐Southern Oscillation (ENSO4.0) Index are the most influential factors for seasonal droughts across Pakistan. Overall, the findings provide a better understanding of drought‐prone areas in the region, and this information is of potential use for mitigating and managing drought risks.

Recycling of ceramic tiles waste and marble waste in sustainable production of concrete: a review - Sajjad Ali Mangi; Muhammad Saleem Raza; Shabir Hussain Khahro; Abdul Sami Qureshi; Rabinder Kumar (Environmental Science and Pollution Research, 2022)

Quantitative evaluation of zinc metal in meadows and ruminants for health assessment: implications for humans﻿ - Ayesha Maqsood; Zafar Iqbal Khan; Kafeel Ahmad; Shahzad Akhtar; Asma Ashfaq; Ifra Saleem Malik; Razia Sultana; Muhammad Nadeem; Jawaher Alkahtani; Yheni Dwiningsih; Mohamed S. Elshikh (Environmental Science and Pollution Research, 2022)

Insect pests of economic importance attacking wheat crop (Triticum aestivum L.) in Punjab, Pakistan - Dilbar Hussain; Muhammad Asrar; Bushra Khalid; Faisal Hafeez; Muhammad Saleem; Muazzma Akhter; Maqsood Ahmed; Imran Ali; Kanwal Hanif (International Journal of Tropical Insect Science, 2022)

Correction to: Bioaccumulation of lead in different varieties of wheat plant irrigated with wastewater in remote agricultural regions - Wuyi Liu; Asma Zafar; Zafar Iqbal Khan; Muhammad Nadeem; Kafeel Ahmad; Kinza Wajid; Humayun Bashir; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq (Environmental Science and Pollution Research, 2022)

RETRACTED ARTICLE: Attenuating effect of Prosopis cineraria against paraquat-induced toxicity in prepubertal mice, Mus musculus - Muhammad Furqan Akhtar; Muhammad Omer Mehal; Ammara Saleem; Ahmad El Askary; Mohamed M. Abdel-Daim; Fareeha Anwar; Muhammad Ayaz; Alam Zeb (Environmental Science and Pollution Research, 2022)

Unrevealing arsenic and lead toxicity and antioxidant response in spinach: a human health perspective - Natasha; Muhammad Shahid; Sana Khalid; Mazhar Saleem (Environmental Geochemistry and Health, 2022)

Ameliorative effect of ethoxylated chalcone-based MAO-B inhibitor on behavioural predictors of haloperidol-induced Parkinsonism in mice: evidence of its antioxidative role against Parkinson’s diseases - Naseer Maliyakkal; Uzma Saleem; Fareeha Anwar; Muhammad Ajmal Shah; Bashir Ahmad; Filzah Umer; Mohammad Ali Abdullah Almoyad; Della Grace Thomas Parambi; Asmy Appadath Beeran; Lekshmi R Nath; Lotfi Aleya; Bijo Mathew (Environmental Science and Pollution Research, 2022)

Ecological risk assessment of heavy metal chromium in a contaminated pastureland area in the Central Punjab, Pakistan: soils vs plants vs ruminants - Fu Chen; Fatima Ghulam Muhammad; Zafar Iqbal Khan; Kafeel Ahmad; Muhammad Nadeem; Shahid Mahmood; Muhammad Umar Farooq Awan; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq; Razia Sultana; Ayesha Maqsood; et al. (Environmental Science and Pollution Research, 2022)

Evaluation of potential ecological risk and prediction of zinc accumulation and its transfer in soil plants and ruminants: public health implications - Fu Chen; Laraib Saqlain; Jing Ma; Zafar Iqbal Khan; Kafeel Ahmad; Asma Ashfaq; Razia Sultana; Fatima Ghulam Muhammad; Ayesha Maqsood; Majida Naeem; Ifra Saleem Malik; Mudasra Munir; et al. (Environmental Science and Pollution Research, 2022)

Bioaccumulation and transfer of zinc in soil plant and animal system: a health risk assessment for the grazing animals - Fu Chen; Fatima Ghulam Muhammad; Zafar Iqbal Khan; Kafeel Ahmad; Ifra Saleem Malik; Asma Ashfaq; Majida Naeem; Muhammad Nadeem; Jing Ma; Muhammad Umer Farooq Awan; Shahzadi Mahpara; Shahid Mehmood (Environmental Science and Pollution Research, 2022)

Precipitation projections over the Indus River Basin of Pakistan for the 21st century using a statistical downscaling framework - Muhammad Saleem Pomee; Elke Hertig (International Journal of Climatology, 2022)
We estimate future changes in precipitation over the entire Indus basin of Pakistan with a particular focus on the high‐elevation upper indus basin (UIB). A statistical downscaling approach is used. We consider the spatial variability of observed precipitation on seasonal scales. Large‐scale atmospheric patterns are employed for general circulation model (GCM) selection and subsequent projections. Firstly, we identify the precipitation governing predictors from ERA‐Interim reanalysis. We further quantify the robustness of governing predictors against other reanalysis datasets (ERA5 and NCEP‐NCAR‐II) to assess future projections' fidelity. We perform S‐mode Principal Component Analysis on predictor fields and compare loading patterns using Taylor diagrams to assess predictor correspondence between different reanalysis. Similarly, we compare ERA‐Interim variables with model‐simulated fields during the historical period to select better performing GCMs and quantify model uncertainty. The regional suitability of available GCMs in our study is also demonstrated. Ensemble (median) changes in regional precipitation derived through atmospheric fields show an elevation‐dependent response of the UIB at representative concentration pathway (RCP) scenarios RCP4.5 and RCP8.5, where increased precipitation will mostly fall at high elevations. However, the positive signals are more distinct during the winter and monsoon seasons, particularly over the central Karakoram. Meanwhile, a decrease in precipitation is robust during the pre‐monsoon period, particularly over the northwestern regions. These signals intensify and become more robust during 2071–2100 under RCP8.5, and the better‐performing models and signal‐to‐noise ratios further support this finding. The spatial patterns of projected changes suggest stronger (weaker) and further northward penetrating westerly systems during the winter (pre‐monsoon) season. Increased warming will also strengthen monsoon circulations, and these will penetrate further into the northwestern and trans‐Himalayan regions. The Lower Indus shows a mixed seasonal response that is more uncertain. The present analysis provides an alternative perspective to the ongoing research of assessing climate responses in complex regions.

Chemical characterisation, in vitro antioxidant, cytotoxicity and safety evaluation of Polystichum braunii (Spenn.) fee roots - Ammara Saleem; Mohammad Saleem; Muhammad Furqan Akhtar; Azhar Rasul; Mirza Muhammad Faran Ashraf Baig (Natural Product Research, 2021)

Depositional Sedimentary Facies, Stratigraphic Control, Paleoecological Constraints, and Paleogeographic Reconstruction of Late Permian Chhidru Formation (Western Salt Range, Pakistan) - Syed Kamran Ali; Hammad Tariq Janjuhah; Syed Muzyan Shahzad; George Kontakiotis; Muhammad Hussain Saleem; Usman Khan; Stergios D. Zarkogiannis; Panayota Makri; Assimina Antonarakou (Journal of Marine Science and Engineering, 2021)
The Upper Indus Basin, in Pakistan’s western Salt Range, is home to the Zaluch Gorge. The sedimentary rocks found in this Gorge, belonging to the Chhidru Formation, were studied in terms of sedimentology and stratigraphy, and provide new insights into the basin paleogeographic evolution from the Precambrian to the Jurassic period. Facies analysis in the Chhidru Formation deposits allowed the recognition of three lithofacies (the limestone facies—CF1, the limestone with clay interbeds facies—CF2, and the sandy limestone facies—CF3) with five microfacies types (mudstone biomicrite—MF-1, wackestone-biomicrite—MF-2, wackestone-biosparite—MF-3, pack-stone-biomicrite—MF-4, and packstone-biosparite—MF-5), as well as their depositional characteristics. The identified carbonate and siliciclastic formations display various facies in a shallow marine environment, with different lithologies, sedimentary features, and energy conditions. It is thought that the depositional characteristics of these microfacies are closer to those of the middle to outer shelf. Because of the progressively coarsening outcrop sequence, this formation seems to be at the very top of the high stand system tract (HST). A modified dynamic depositional model of the Chhidru Formation is further built using outcrop data, facies information, and stratigraphy. According to this concept, the formation was deposited in the middle to inner shelf area of the shallow marine environment, during the Late-Permian period. The Permo-Triassic Boundary (PTB), which is the end of the type-1 series, is marked by this formation’s top.

Correction to: Automation in Agriculture by Machine and Deep Learning Techniques: A Review of Recent Developments - Muhammad Hammad Saleem; Johan Potgieter; Khalid Mahmood Arif (Precision Agriculture, 2021)

Automation in Agriculture by Machine and Deep Learning Techniques: A Review of Recent Developments - Muhammad Hammad Saleem; Johan Potgieter; Khalid Mahmood Arif (Precision Agriculture, 2021)

Rhizobacterial, Fusarium Complex, and Fungicide Seed Treatments Regulate Shoot and Root Traits of Soybean Plants - Anthony Adesemoye; Zahida H. Pervaiz; Lipi Parikh; Srikanth Kodati; Qingming Zhang; Strahinja Stepanović; Muhammad Saleem (Journal of Soil Science and Plant Nutrition, 2021)

Comparative Effects of Individual and Consortia Plant Growth Promoting Bacteria on Physiological and Enzymatic Mechanisms to Confer Drought Tolerance in Maize (Zea mays L.) - Muhammad Saleem; Fahim Nawaz; Muhammad Baqir Hussain; Rao Muhammad Ikram (Journal of Soil Science and Plant Nutrition, 2021)
Mitigation strategies based on plant–microbe interactions to increase the performance of plants under water-deficit conditions are well documented. However, little is known about a suitable consortium of bacterial inoculants and underlying physiological and enzymatic events to improve drought tolerance in maize. We performed laboratory and pot experiments to understand the synergistic interactions among plant growth-promoting bacteria to alleviate the drought-induced damages in maize. Initially, ten bacterial strains were evaluated for their osmotic stress tolerance capacity by growing them in a media containing 0, 10, 20, and 30% polyethylene glycol (PEG-6000). Also, the seeds of a drought tolerant (NK-6654) and sensitive (SD-626) maize cultivar were inoculated with these bacterial strains in the first pot experiment to determine their effects on the growth and physiological processes. Later, in the second pot experiment, the best performing inoculants were selected to study the individual and synergistic effects of bacterial inoculation to confer drought tolerance in maize. Our findings showed that the inoculation with tolerant strains resulted in higher photosynthetic activity (25–39%), maintenance of leaf water status (14–18%) and pigments (27–32%), and stimulation of antioxidant machinery (28–38%) than no inoculation in water-stressed maize seedlings. Moreover, the treatment with bacteria consortia further stimulated the drought protective mechanisms and resulted in higher efficiency of photosynthetic (47–61%) and antioxidant systems (42–62%) than the individual inoculants under water-deficit conditions. We conclude that the inoculation with microbial consortia regulates water uptake, photosynthetic performance, and stress metabolites to minimize drought-induced damages in maize.

Mitigation of Degraded Soils by Using Biochar and Compost: a Systematic Review - Misbah Batool Zahra; Bakhtawar Fayyaz; Zill-E-Huma Aftab; Muhammad Saleem Haider (Journal of Soil Science and Plant Nutrition, 2021)

Paleostress inversion and outcrop fracture analysis of the brittle deformation along Main Boundary Thrust (MBT), NW Himalaya, Pakistan - Naveed Ahsan; Hassan Mehmood; Muhammad Armaghan Faisal Miraj; Iqra Bano; Abdul Qayyum; Rana Faizan Saleem (Journal of Earth System Science, 2021)

Comparison of individual and combination treatments with naproxen, prednisolone and hydroxychloroquine to treat Complete Freund’s Adjuvant induced arthritis - Muhammad Furqan Akhtar; Summiya Zubair; Ammara Saleem; Khalaf F. Alsharif; Mohamed M. Abdel-Daim (Inflammopharmacology, 2021)

Genome-wide identification and characterization of a plant-specific Dof transcription factor gene family in olive (Olea europaea) and its comparison with Arabidopsis - Mariyam; Muhammad Shafiq; Muhammad Haseeb; Rana Muhammad Atif; Syed Agha Armaghan Asad Abbas Naqvi; Numan Ali; Muhammad Arshad Javed; Fizza Gillani; Muhammad Saleem Haider (Horticulture, Environment, and Biotechnology, 2021)

Influences of environmental factors on the modern 14C reservoir effects in Qinghai-Tibet Plateau lakes - Ding-ding Du; Zhi-wen Li; Hai-ping Hu; Yong-hui Bai; Wen Li; Muhammad Saleem Mughal; Hai-Yan Qian (Journal of Mountain Science, 2021)

First report of Cotton leaf curl Kokhran virus associated with Cotton leaf curl Multan betasatellite infecting soybean in Pakistan - Maddiha Riaz; Muhammad Zubair; Saleem Ur Rahman; Shahid Mansoor (Journal of Plant Pathology, 2021)

Global trends in research on carbon footprint of buildings during 1971–2021: a bibliometric investigation - Muhammad Saleem Raza; Shabir Hussain Khahro; Sheeraz Ahmed Memon; Tauha Hussain Ali; Nafees Ahmed Memon (Environmental Science and Pollution Research, 2021)

Evaluation of Contamination Status and Health Risk Assessment of Essential and Toxic Metals in Cyprinus carpio from Mangla Lake, Pakistan - Muhammad Saleem; Zongbo Shi; Munir H. Shah (Biological Trace Element Research, 2021)

Structural and Functional Determinants of Physiological Pliability in Kyllinga brevifolia Rottb. for Survival in Hyper-Saline Saltmarshes - Sahar Mumtaz; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Iftikhar Ahmad; Muhammad Ashraf; Muhammad Hamzah Saleem (Water, Air, & Soil Pollution, 2021)

Melatonin-Induced Salinity Tolerance by Ameliorating Osmotic and Oxidative Stress in the Seedlings of Two Tomato (Solanum lycopersicum L.) Cultivars - Muhammad Ali; Muhammad Kamran; Ghulam Hassan Abbasi; Muhammad Hamzah Saleem; Salman Ahmad; Aasma Parveen; Zaffar Malik; Sobia Afzal; Sunny Ahmar; Khadim Muhammad Dawar; Sardar Ali; Saud Alamri; et al. (Journal of Plant Growth Regulation, 2021)

Recent updates on immunological, pharmacological, and alternative approaches to combat COVID-19 - Ammara Saleem; Muhammad Furqan Akhtar; Muhammad Haris; Mohamed M. Abdel-Daim (Inflammopharmacology, 2021)

Population structure and phylogenetic relationship of Peach [Prunus persica (L.) Batsch] and Nectarine [Prunus persica var. nucipersica (L.) C.K. Schneid.] based on retrotransposon markers - Hina Naeem; Faisal Saeed Awan; Peter Michael Dracatos; Muhammad Wasim Sajid; Shahzad Saleem; Qudsia Yousafi; Muhammad Saad Khan; Asim Mehmood; Bushra Zulfiqar (Genetic Resources and Crop Evolution, 2021)

Evaluation of pasture allowance of manganese for ruminants - Xiaoping Ge; Fu Chen; Laraib Saqlain; Jing Ma; Zafar Iqbal Khan; Kafeel Ahmad; Ifra Saleem Malik; Asma Ashfaq; Razia Sultana; Mudasra Munir; Muhammad Nadeem; Muhammad Umer Farooq Awan; et al. (Environmental Science and Pollution Research, 2021)

Phosphorus availability increases pathobiome abundance and invasion of rhizosphere microbial networks by Ralstonia - Pengfa Li; Ming Liu; Guilong Li; Kai Liu; Tianshun Liu; Meng Wu; Muhammad Saleem; Zhongpei Li (Environmental Microbiology, 2021)
Summary Soil disease‐suppressiveness depends on complex interactions among pathogens, native microbiota, and physicochemical properties, while these interactions remain understudied. Comparing field and microcosm experiments, we investigated the significance of these interactions in disease emergence or suppression using structural equation modelling (SEM) and receiver operating characteristic curve (ROC) analyses. We observed significant differences in the relative abundance of pathogenic and beneficial microbes, alpha and beta diversity indices between disease‐conducive and ‐suppressive rhizosphere soils. The pathogenic ( Ralstonia ) and beneficial ( Bacillus ) taxa dominated disease‐conducive and ‐suppressive rhizosphere soils, respectively. Moreover, the co‐occurrences of Ralstonia with native microorganisms were positive and negative in the disease‐conducive and ‐suppressive soils, respectively. These results suggest the supportive ( Rudaea ) and suppressive ( Enterobacter , Bacillus ) role of indigenous microbes in the invasion of soil and plant systems by Ralstonia . The SEM and ROC analysis predicted that Ralstonia invaded rhizospheric microbial networks and caused peanut wilt under high than low soil phosphorus conditions. Our results suggest the importance of soil phosphorus availability in altering the microbial interactions, thus leading to soil invasion by Ralstonia . Thus, we conclude by saying that feeding soil with high amounts of available phosphorus could deplete plant‐beneficial microbes and increase the pathobiome abundance that may compromise plant health.

Gradient-based impedance synthesis for breast and lung cancer cell screening deploying planar and nano-structured electrodes - Muhammad Awais Aslam; Kashif Riaz; Muhammad Mubasher Saleem (Medical & Biological Engineering & Computing, 2021)

Assessing the physico-chemical parameters and some metals of underground water and associated soil in the arid and semiarid regions of Tank District, Khyber Pakhtunkhwa, Pakistan - Asif Khan; Muhammad Naeem; Muhammad Bilal; Abbas Khan; Fazle Subhan; Muhammad Ikram; Muhammad Ishaq Ali Shah; Saleem Ullah; Asmat Ullah; Atta Ullah (Environmental Monitoring and Assessment, 2021)

Impact of green trust and green perceived quality on green purchase intentions: a moderation study - Allah Wasaya; Muhammad Abid Saleem; Jamil Ahmad; Muhammad Nazam; M. Mohsin Ali Khan; Mohammad Ishfaq (Environment, Development and Sustainability, 2021)

Antiparkinsonian activity of Cucurbita pepo seeds along with possible underlying mechanism - Uzma Saleem; Aisha Shehzad; Shahid Shah; Zohaib Raza; Muhammad Ajmal Shah; Shabana Bibi; Zunera Chauhdary; Bashir Ahmad (Metabolic Brain Disease, 2021)

Correction to: Production of eco-friendly concrete incorporating rice husk ash and polypropylene fibres - Muhammad Jaffar Memon; Ashfaque Ahmed Jhatial; Ali Murtaza; Muhammad Saleem Raza; Karim Bux Phulpoto (Environmental Science and Pollution Research, 2021)

Bioaccumulation of zinc in edible tropical vegetables in Peninsular Malaysia and its human health risk assessment based on various ethnicities in Malaysia - Koe Wei Wong; Chee Kong Yap; Aziran Yaacob; Rosimah Nulit; Hishamuddin Omar; Ahmad Zaharin Aris; Moslem Sharifinia; Alireza Riyahi Bakhtiari; Salman Abdo Al-Shami; Muhammad Saleem; Hideo Okamura (Environmental Science and Pollution Research, 2021)

Production of eco-friendly concrete incorporating rice husk ash and polypropylene fibres - Muhammad Jaffar Memon; Ashfaque Ahmed Jhatial; Ali Murtaza; Muhammad Saleem Raza; Karim Bux Phulpoto (Environmental Science and Pollution Research, 2021)

Evaluation of transfer of lead in soil plant animal system: assessment of consequences of its toxicity - Fu Chen; Jing Ma; Zafar Iqbal Khan; Kafeel Ahmad; Tasneem Ahmad; Ifra Saleem Malik; Asma Ashfaq; Mudasra Munir; Sonaina Nazar; Zunaira Munir; Abid Ejaz; Muhammad Nadeem; et al. (Environmental Science and Pollution Research, 2021)

Isolation and functional characterization of exopolysaccharide produced by Lactobacillus plantarum S123 isolated from traditional Chinese cheese - Muhammad Saleem; Samiullah Malik; Hafiza Mahreen Mehwish; Muhammad Waqas Ali; Nazim Hussain; Mohsin Khurshid; Muhammad Shahid Riaz Rajoka; Yougen Chen (Archives of Microbiology, 2021)

Geological and petrographic investigations of the Miocene Molasse deposits in Sub-Himalayas, District Sudhnati, Pakistan - Asim Javed; Ali Wahid; Muhammad Saleem Mughal; Muhammad Sabir Khan; Raja Saad Qammar; Syed Haroon Ali; Numair Ahmad Siddiqui; Muhammad Atif Iqbal (Arabian Journal of Geosciences, 2021)

Studying the foliar selenium-modulated dynamics in phenology and quality of terminal heat-stressed cotton ( Gossypium hirsutum L.) in association with yield - Muhammad Farrukh Saleem; Muhammad Asif Kamal; Muhammad Shahid; Muhammad Awais; Amna Saleem; Muhammad Aown Sammar Raza; Bao-Luo Ma (Plant Biosystems, 2021)

Chemical composition of gemstones and characterization of their host pegmatites and country rocks from Chumar Bakhoor, Gilgit-Baltistan, Pakistan: implications for the source of gem-forming fluids - Amjad Hussain; Muhammad Tahir Shah; Mohammad Arif; Muhammad Hassan Agheem; Muhammad Saleem Mughal; Shakir Ullah; Syed Asim Hussain; Izhar Sadiq (Arabian Journal of Geosciences, 2021)

Biostratigraphic investigation and depositional model of the Late Thanetian Ranikot and the Ypresian Laki formations in the subsurface of the Southern Indus Basin, Pakistan - Hussain Asghar; Muhammad Saleem Mughal; Muhammad Sabir Khan; Saeed Abbas; Muhammad Hanif; Gulfam Hussain; Muhammad Ali; Kazim Ali; Amjad Hussain (Arabian Journal of Geosciences, 2021)

Spatio‐temporal evaluation of gridded precipitation products for the high‐altitude Indus basin - Zakir Hussain Dahri; Fulco Ludwig; Eddy Moors; Shakil Ahmad; Bashir Ahmad; Muhammad Shoaib; Irfan Ali; Muhammad Shahid Iqbal; Muhammad Saleem Pomee; Abdul Ghafoor Mangrio; Muhammad Munir Ahmad; Pavel Kabat (International Journal of Climatology, 2021)
The high‐altitude Indus basin is one of the most complex and inadequately explored mountain terrains in the World, where reliable observations of precipitation are highly lacking. Therefore, spatially distributed precipitation products developed at global/regional scale are often used in several scientific disciplines. However, large uncertainties in precipitation estimates of such precipitation data sets often lead to suboptimal outcomes. In this study, performance of 27 widely used gridded precipitation products belonging to three different categories of gauge‐based, reanalysis and merged products is evaluated with respect to high‐quality reference climatologies of mean monthly precipitation. Widely used statistical measures and quantitative analysis techniques are used to analyse the spatial patterns and quantitative distribution of mean monthly, seasonal and annual precipitation at sub‐regional scale. Mean annual precipitation estimates of the gridded data sets are cross validated with the corresponding adjusted streamflows using Turc‐Budyko non‐dimensional analysis. Results reveal poor to moderately good performance of the gridded data sets. Marked differences in spatiotemporal and quantitative distribution of precipitation are found among the data sets. All data sets are consistent in their patterns showing negative or dry bias in wet areas and positive or wet bias in dry areas, although considerable differences in the magnitudes of the biases are noticed at sub‐regional scale. None of the data sets is equally good for all sub‐regions due to very high spatiotemporal variability in their performance at sub‐regional scale. Gauge‐based and merged products performed better in dry regions and during monsoon season, while reanalysis products provided better estimates in wet areas and during winter months. GPCC V8, ERA5 and MSWEP2.2 are found better than their counter‐grouped data sets. Overall, ERA5 is found most acceptable for all sub‐regions, particularly at higher‐altitudes, in wet areas and during winter months.

Neuroprotective potential of Malva neglecta is mediated via down-regulation of cholinesterase and modulation of oxidative stress markers - Uzma Saleem; Rubina Akhtar; Fareeha Anwar; Muhammad Ajmal Shah; Zunera Chaudary; Muhammad Ayaz; Bashir Ahmad (Metabolic Brain Disease, 2021)

Implications of Solid Lipid Nanoparticles of Ganoderic Acid for the Treatment and Management of Hepatocellular Carcinoma - Mahfoozur Rahman; Sarwar Beg; Khalid S. Alharbi; Nabil K. Alruwaili; Nasser Hadal Alotaibi; Abdulaziz I. Alzarea; Waleed H. Almalki; Sattam Khulaif Alenezi; Waleed M. Altowayan; Mohammed S. Alshammari; Muhammad Afzal; Shakir Saleem; et al. (Journal of Pharmaceutical Innovation, 2021)

Correction to: Monitoring of copper accumulation in water, soil, forage, and cows impacted by heavy automobiles - Tasneem Ahmad; Sonaina Nazar; Kafeel Ahmad; Zafar Iqbal Khan; Humayun Bashir; Asma Ashfaq; Mudasra Munir; Zunaira Munir; Khadim Hussain; Jawaher Alkahtani; Mohamed Soliman Elshikh; Muhammad Nadeem; et al. (Environmental Science and Pollution Research, 2021)

Monitoring of copper accumulation in water, soil, forage, and cows impacted by heavy automobiles in Sargodha, Pakistan - Tasneem Ahmad; Sonaina Nazar; Kafeel Ahmad; Zafar Iqbal Khan; Humayun Bashir; Asma Ashfaq; Mudasra Munir; Zunaira Munir; Khadim Hussain; Jawaher Alkahtani; Mohamed Soliman Elshikh; Muhammad Nadeem; et al. (Environmental Science and Pollution Research, 2021)

Chromium retention potential of two contrasting Solanum lycopersicum Mill. cultivars as deciphered by altered pH dynamics, growth, and organic acid exudation under Cr stress - Muhammad Tariq Javed; Kashif Tanwir; Saghir Abbas; Muhammad Hamzah Saleem; Robina Iqbal; Hassan Javed Chaudhary (Environmental Science and Pollution Research, 2021)

Growth and physio-biochemical responses of maize ( Zea mays L.) to drought and heat stresses - Madiha Ayub; Muhammad Yasin Ashraf; Abida Kausar; Salman Saleem; Sumera Anwar; Volkan Altay; Munir Ozturk (Plant Biosystems, 2021)

RETRACTED ARTICLE: Evaluation of toxicity potential of cobalt in wheat irrigated with wastewater: health risk implications for public - Fu Chen; Zafar Iqbal Khan; Asma Zafar; Jing Ma; Muhammad Nadeem; Kafeel Ahmad; Shehzadi Mahpara; Kinza Wajid; Humayun Bashir; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq; et al. (Environmental Science and Pollution Research, 2021)

Arbuscular mycorrhizal fungi and its major role in plant growth, zinc nutrition, phosphorous regulation and phytoremediation - Parashuram Bhantana; Muhammad Shoaib Rana; Xue-cheng Sun; Mohamed G. Moussa; Muhammad Hamzah Saleem; Muhamad Syaifudin; Ashrafuzzaman Shah; Amrit Poudel; Amar Bahadur Pun; Mufid Alam Bhat; Dhanik Lal Mandal; Sujit Shah; et al. (Symbiosis, 2021)

Correction to: COVID‑19 and therapy with essential oils having antiviral, anti‑inflammatory, and immunomodulatory properties - Muhammad Asif; Mohammad Saleem; Malik Saadullah; Hafiza Sidra Yaseen; Raghdaa Al Zarzour (Inflammopharmacology, 2021)

Chemical characterization and anti-arthritic appraisal of Monotheca buxifolia methanolic extract in Complete Freund’s Adjuvant-induced arthritis in Wistar rats - Muhammad Furqan Akhtar; Khushdil Khan; Ammara Saleem; Mirza Muhammad Faran Ashraf Baig; Azhar Rasul; Mohamed M. Abdel-Daim (Inflammopharmacology, 2021)

Asphodelus tenuifolius extracts arrested inflammation and arthritis through modulation of TNF-α, NF-κB, ILs, and COX-2 activities in in vivo models - Mohammad Saleem; Anam Iftikhar; Muhammad Asif; Khalid Hussain; Alamgeer; Pervaiz Akhtar Shah; Ammara Saleem; Muhammad Furqan Akhtar; Muhammad Tanzeem; Hafiza Sidra Yaseen (Inflammopharmacology, 2021)

Benzilydene and thiourea derivatives as new classes of carbonic anhydrase inhibitors: an in vitro and molecular docking study - Shama Qaiser; Mohammad S. Mubarak; Sajda Ashraf; Muhammad Saleem; Zaheer Ul-Haq; Muhammad Safdar; Abdur Rauf; Tareq Abu-Izneid; Malak I. Qadri; Aneela Maalik (Medicinal Chemistry Research, 2021)

Correction to: In Silico Evaluation of Food Derived Bioactive Peptides as Inhibitors of Angiotensin Converting Enzyme (ACE) - Qudsia Yousafi; Jannat Batool; Muhammad Saad Khan; Tamsila Perveen; Muhammad Wasim Sajid; Abrar Hussain; Asim Mehmood; Shahzad Saleem (International Journal of Peptide Research and Therapeutics, 2021)

In Silico Evaluation of Food Derived Bioactive Peptides as Inhibitors of Angiotensin Converting Enzyme (ACE) - Qudsia Yousafi; Jannat Batool; Muhammad Saad Khan; Tamsila Perveen; Muhammad Wasim Sajid; Abrar Hussain; Asim Mehmood; Shahzad Saleem (International Journal of Peptide Research and Therapeutics, 2021)

Appraisal of chromium in chicken reared on maize irrigated with sewage water - Zill-e-Huma; Zafar Iqbal Khan; Ijaz Rasool Noorka; Kafeel Ahmad; Kinza Wajid; Muhammad Nadeem; Mudasra Munir; Ifra Saleem Malik; Madiha Kiran; Tahir Hussain; Muhammad F. Qamar; Tasneem Ahmad; et al. (Environmental Science and Pollution Research, 2021)

Hydrochemistry modelling: evaluation of groundwater quality deterioration due to anthropogenic activities in Lahore, Pakistan - Muhammad Irfan Jalees; Muhammad Umar Farooq; Mehwish Anis; Ghulam Hussain; Arfa Iqbal; Sana Saleem (Environment, Development and Sustainability, 2021)

Treatment of Wilms’ nephroblastoma cancer cells via EGFR targeting of dactinomycin loaded DNA-nanowires - Mirza Muhammad Faran Ashraf Baig; Chengfei Zhang; Muhammad Furqan Akhtar; Ammara Saleem; Naveed Nisar (Journal of Pharmaceutical Investigation, 2021)

New insights into the phytochemical composition, enzyme inhibition and antioxidant properties of desert cotton ( Aerva javanica (Bum.f) Shult. -Amaranthaceae) - Hammad Saleem; Gokhan Zengin; Kashif-Ur-Rehman Khan; Irshad Ahmad; Muhammad Waqas; Fawzi M. Mahomoodally; Kannan R.R. Rengasamy; Noorazwani Zainol; Syafiq Asnawi Zainal Abidin; Nafees Ahemad (Natural Product Research, 2021)

Molybdenum supply increases root system growth of winter wheat by enhancing nitric oxide accumulation and expression of NRT genes - Muhammad Imran; Xuecheng Sun; Saddam Hussain; Muhammad Shoaib Rana; Muhammad Hamzah Saleem; Muhammad Riaz; Xiangru Tang; Imran Khan; Chengxiao Hu (Plant and Soil, 2021)

Fruitful decade of fungal metabolites as anti-diabetic agents from 2010 to 2019: emphasis on α-glucosidase inhibitors - Hidayat Hussain; Mamona Nazir; Muhammad Saleem; Ahmed Al-Harrasi; Elizbit; Ivan R. Green (Phytochemistry Reviews, 2021)
In recent years the prevalence of diabetes has increased globally and by 2040 the number of diabetic people has been estimated to increase to 642 million. Various classes of drugs are available to treat Type ll diabetes. However, these drugs are associated with certain side effects. α-Glucosidase is an intriquing target enzyme to treat Type II diabetes, and α-glucosidase inhibitors are considered as first-line drugs for Type ll patients. Fungi, in general, produce natural products with some amazing chemical diversity and many fungal metabolites have illustrated a wide range of biological and pharmacological effects. In this review the focus is on describing the α-glucosidase effects and their potential as anti-diabetic agents of various metabolites isolated from fungi.

Fungal metabolites as anti-diabetic agents: emphasis on PTP1B inhibitors - Mamona Nazir; Muhammad Saleem; Iftikhar Ali; Ghulam Abbas; Najeeb Ur Rehman; Ivan R. Green; Wahid Hussain; Saima Khan; Hidayat Hussain (Phytochemistry Reviews, 2021)

Impact of heat stress responsive factors on growth and physiology of cotton (Gossypium hirsutum L.) - Muhammad Asif Saleem; Waqas Malik; Abdul Qayyum; Sami Ul-Allah; Muhammad Qadir Ahmad; Hammad Afzal; Muhammad Waqas Amjid; Muhammad Farjad Ateeq; Zia Ullah Zia (Molecular Biology Reports, 2021)

Biochemically Triggered Heat and Drought Stress Tolerance in Rice by Proline Application - Sajid Hanif; Muhammad Farrukh Saleem; Muhammad Sarwar; Muhammad Irshad; Abdul Shakoor; Muhammad Ashfaq Wahid; Haroon Zaman Khan (Journal of Plant Growth Regulation, 2021)

Investigation of in vivo anti-inflammatory and anti-angiogenic attributes of coumarin-rich ethanolic extract of Melilotus indicus - Mohammad Saleem; Muhammad Asif; Anum Parveen; Hafiza Sidra Yaseen; Malik Saadullah; Asiya Bashir; Jawaria Asif; Mehwish Arif; Ikram Ullah Khan; Rizwan Ullah Khan (Inflammopharmacology, 2021)

Research advances and applications of biosensing technology for the diagnosis of pathogens in sustainable agriculture - Qurban Ali; Sunny Ahmar; Muhammad Aamir Sohail; Muhammad Kamran; Mohsin Ali; Muhammad Hamzah Saleem; Muhammad Rizwan; Agha Mushtaque Ahmed; Freddy Mora-Poblete; Antônio Teixeira do Amaral Júnior; Mustansar Mubeen; Shafaqat Ali (Environmental Science and Pollution Research, 2021)

Characterization of fungal flora associated with sternorrhyncha insects of cotton plants - Waheed Anwar; Kiran Nawaz; Muhammad Asim Javed; Adnan Akhter; Ahmad Ali Shahid; Muhammad Saleem Haider; Muhammad Zia Ur Rehman; Sajid Ali (Biologia, 2021)

Determination of insecticide resistance in Bemisia tabaci (Hemiptera: Aleyrodidae) populations from Punjab, Pakistan - Muhammad Saleem; Mansoor ul Hasan; Muhammad Sagheer; Muhammad Atiq (International Journal of Tropical Insect Science, 2021)

Higher biochar rate strongly reduced decomposition of soil organic matter to enhance C and N sequestration in nutrient-poor alkaline calcareous soil - Samar Fatima; Muhammad Riaz; Mohammad I. Al-Wabel; Muhammad Saleem Arif; Tahira Yasmeen; Qaiser Hussain; Mahnaz Roohi; Shah Fahad; Kawsar Ali; Muhammad Arif (Journal of Soils and Sediments, 2021)

Correction to: Appraisal of chromium in chicken reared on maize irrigated with sewage water - Zill-e-Huma; Zafar Iqbal Khan; Ijaz Rasool Noorka; Kafeel Ahmad; Kinza Wajid; Muhammad Nadeem; Mudasra Munir; Ifra Saleem Malik; Madiha Kiran; Tahir Hussain; Muhammad F. Qamar; Tasneem Ahmad; et al. (Environmental Science and Pollution Research, 2021)

Nexus between willingness to pay for renewable energy sources: evidence from Turkey - Iftikhar Muhammad; Malik Shahzad Shabbir; Sharjeel Saleem; Kanwal Bilal; Recep Ulucak (Environmental Science and Pollution Research, 2021)

Bioaccumulation of cadmium in different genotypes of wheat crops irrigated with different sources of water in agricultural regions - Asma Zafar; Zafar Iqbal Khan; Wuyi Liu; Humayun Bashir; Kafeel Ahmad; Kinza Wajid; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq; Muhammad Nadeem; Tasneem Ahmad; Ijaz Rasool Noorka; et al. (Environmental Science and Pollution Research, 2021)

Diversity and recombination analysis of Cotton leaf curl Multan betasatellite associated with cotton leaf curl begomovirus disease complex - Muhammad Zubair; Saleem Ur Rahman; Ishtiaq Hassan; Azhar Hussain Shah; Imran Amin; Shahid Mansoor (Australasian Plant Pathology, 2021)

Comparative secondary metabolites profiling and biological activities of aerial, stem and root parts of Salvadora oleoides decne (Salvadoraceae) - Hammad Saleem; Irshad Ahmad; Gokhan Zengin; Fawzi M. Mahomoodally; Kashif-Ur- Rehman Khan; Hafiz Muhammad Ahsan; Syafiq Asnawi Zainal Abidin; Nafees Ahemad (Natural Product Research, 2020)

Interactive role of zinc and iron lysine on Spinacia oleracea L. growth, photosynthesis and antioxidant capacity irrigated with tannery wastewater - Ihsan Elahi Zaheer; Shafaqat Ali; Muhammad Hamzah Saleem; Mohsin Ali; Muhammad Riaz; Sehar Javed; Anam Sehar; Zohaib Abbas; Muhammad Rizwan; Mohamed A. El-Sheikh; Mohammed Nasser Alyemeni (Physiology and Molecular Biology of Plants, 2020)

Plant growth-promoting Bacillus sp. strain SDA-4 confers Cd tolerance by physio-biochemical improvements, better nutrient acquisition and diminished Cd uptake in Spinacia oleracea L. - Muhammad Shahid; Muhammad Tariq Javed; Kashif Tanwir; Muhammad Sohail Akram; Syeda Khola Tazeen; Muhammad Hamzah Saleem; Sajid Masood; Sadia Mujtaba; Hassan Javed Chaudhary (Physiology and Molecular Biology of Plants, 2020)

Foliar Potassium-Induced Regulations in Glycine Betaine and Malondialdehyde Were Associated with Grain Yield of Heat-Stressed Bread Wheat (Triticum aestivum L.) - Muhammad Shahid; Muhammad Farrukh Saleem; Amna Saleem; Muhammad Sarwar; Haroon Zaman Khan; Abdul Shakoor (Journal of Soil Science and Plant Nutrition, 2020)

Correction to: Evaluation of in vivo anti-inflammatory and anti-angiogenic attributes of methanolic extract of Launaea spinosa - Muhammad Asif; Mahrukh; Malik Saadullah; Hafiza Sidra Yaseen; Mohammad Saleem; Hafiz Muhammad Yousaf; Ikram Ullah Khan; Maria Yaseen; Muhammad Usman Shams (Inflammopharmacology, 2020)

Methanolic extract of Ephedra ciliata promotes wound healing and arrests inflammatory cascade in vivo through downregulation of TNF-α - Hafiza Sidra Yaseen; Muhammad Asif; Malik Saadullah; Mahrukh; Sajid Asghar; Muhammad Usman Shams; Rizwan Rashid Bazmi; Mohammad Saleem; Hafiz Muhammad Yousaf; Maria Yaseen (Inflammopharmacology, 2020)

RETRACTED ARTICLE: Polystichum braunii extracts inhibit Complete Freund’s adjuvant-induced arthritis via upregulation of I-κB, IL-4, and IL-10, downregulation of COX-2, PGE2, IL-1β, IL-6, NF-κB, and TNF-α, and subsiding oxidative stress - Ammara Saleem; Mohammad Saleem; Muhammad Furqan Akhtar; Muhammad Shahzad; Shah Jahan (Inflammopharmacology, 2020)

Unraveling the effects of cadmium on growth, physiology and associated health risks of leafy vegetables - Junaid Latif; Javaid Akhtar; Iftikhar Ahmad; Muhammad Mahmood-ur-Rehman; Ghulam Mustafa Shah; Qamaruz Zaman; Tariq Javaid; Zia Ur Rahman Farooqi; Muhammad Shakar; Azka Saleem; Muhammad Rizwan (Brazilian Journal of Botany, 2020)

Correction to: A study on the transfer of chromium from meadows to grazing livestock: an assessment of health risk - Zafar Iqbal Khan; Kafeel Ahmad; Samra Siddique; Tasneem Ahmad; Humayun Bashir; Mudasra Munir; Shahzadi Mahpara; Ifra Saleem Malik; Kinza Wajid; Ilker Ugulu; Muhammad Nadeem; Ijaz Rasool Noorka; et al. (Environmental Science and Pollution Research, 2020)

Impact assessment of urban development patterns on land surface temperature by using remote sensing techniques: a case study of Lahore, Faisalabad and Multan district - Muhammad Sajid Saleem; Sajid Rashid Ahmad; Shafiq-Ur-Rehman; Muhammad Asif Javed (Environmental Science and Pollution Research, 2020)

Single tube multiplex PCR assay for the identification of banned meat species - Memoona Iqbal; Muhammad Sulyman Saleem; Muhammad Imran; Waseem Ahmad Khan; Kamran Ashraf; M. Yasir Zahoor; Imran Rashid; Habib-Ur Rehman; Asif Nadeem; Saadat Ali; Sarwat Naz; Wasim Shehzad (Food Additives & Contaminants Part B-Surveillance, 2020)

Modeling regional precipitation over the Indus River basin of Pakistan using statistical downscaling - Muhammad Saleem Pomee; Moetasim Ashfaq; Bashir Ahmad; Elke Hertig (Theoretical and Applied Climatology, 2020)
Complex processes govern spatiotemporal distribution of precipitation within the high-mountainous headwater regions (commonly known as the upper Indus basin (UIB)), of the Indus River basin of Pakistan. Reliable precipitation simulations particularly over the UIB present a major scientific challenge due to regional complexity and inadequate observational coverage. Here, we present a statistical downscaling approach to model observed precipitation of the entire Indus basin, with a focus on UIB within available data constraints. Taking advantage of recent high altitude (HA) observatories, we perform precipitation regionalization using K-means cluster analysis to demonstrate effectiveness of low-altitude stations to provide useful precipitation inferences over more uncertain and hydrologically important HA of the UIB. We further employ generalized linear models (GLM) with gamma and Tweedie distributions to identify major dynamic and thermodynamic drivers from a reanalysis dataset within a robust cross-validation framework that explain observed spatiotemporal precipitation patterns across the Indus basin. Final statistical models demonstrate higher predictability to resolve precipitation variability over wetter southern Himalayans and different lower Indus regions, by mainly using different dynamic predictors. The modeling framework also shows an adequate performance over more complex and uncertain trans-Himalayans and the northwestern regions of the UIB, particularly during the seasons dominated by the westerly circulations. However, the cryosphere-dominated trans-Himalayan regions, which largely govern the basin hydrology, require relatively complex models that contain dynamic and thermodynamic circulations. We also analyzed relevant atmospheric circulations during precipitation anomalies over the UIB, to evaluate physical consistency of the statistical models, as an additional measure of reliability. Overall, our results suggest that such circulation-based statistical downscaling has the potential to improve our understanding towards distinct features of the regional-scale precipitation across the upper and lower Indus basin. Such understanding should help to assess the response of this complex, data-scarce, and climate-sensitive river basin amid future climatic changes, to serve communal and scientific interests.

COVID-19 and therapy with essential oils having antiviral, anti-inflammatory, and immunomodulatory properties - Muhammad Asif; Mohammad Saleem; Malik Saadullah; Hafiza Sidra Yaseen; Raghdaa Al Zarzour (Inflammopharmacology, 2020)

Foliar application of gibberellic acid endorsed phytoextraction of copper and alleviates oxidative stress in jute (Corchorus capsularis L.) plant grown in highly copper-contaminated soil of China - Muhammad Hamzah Saleem; Shah Fahad; Muhammad Adnan; Mohsin Ali; Muhammad Shoaib Rana; Muhammad Kamran; Qurban Ali; Inas A. Hashem; Parashuram Bhantana; Mubassir Ali; Reem M. Hussain (Environmental Science and Pollution Research, 2020)

RETRACTED ARTICLE: The integrin facilitated internalization of fibronectin-functionalized camptothecin-loaded DNA-nanofibers for high-efficiency anticancer effects - Mirza Muhammad Faran Ashraf Baig; Wing-Fu Lai; Saba Ashraf; Ammara Saleem; Muhammad Furqan Akhtar; Reyaj Mikrani; Muhammad Naveed; Farhan Siddique; Abdoh Taleb; Jahanzeb Mudassir; Ghulam Jilany Khan; Muhammad Tayyab Ansari (Drug Delivery and Translational Research, 2020)

Soil selenium transformation across different parent materials in Pothwar uplands of Pakistan - Muhammad Imran; Mohammad Saleem Akhtar; Ayaz Mehmood; Shah Rukh; Ahmad Khan; Chen Zhikun; Ghulam Mujtaba (Arabian Journal of Geosciences, 2020)

Evaluation of indigenous Omani alfalfa landraces for morphology and forage yield under different levels of salt stress - Safaa Mohammed Al-Farsi; Saleem K. Nadaf; Abdullah M. Al-Sadi; Aman Ullah; Muhammad Farooq (Physiology and Molecular Biology of Plants, 2020)

Changes in Soil Organic Carbon Fractions Across a Loess Toposequence - Arsalan Azam; Mohammad Saleem Akhtar; Shah Rukh; Ayaz Mehmood; Muhammad Imran; Ahmad Khan; Abdul Qayyum; Waseem Ahmad; Ali Raza Gurmani (Journal of Soil Science and Plant Nutrition, 2020)

Biofortification with Zinc and Iron Improves the Grain Quality and Yield of Wheat Crop - Yasir Ramzan; Muhammad Bilal Hafeez; Shahbaz Khan; Majid Nadeem; Saleem-ur-Rahman; Sumaira Batool; Javed Ahmad (International Journal of Plant Production, 2020)

Microfacies analysis, diagenetic overprints, geochemistry, and reservoir quality of the Jurassic Samanasuk Formation at the Kahi Section, Nizampur Basin, NW Himalayas, Pakistan - Emad ullah Khan; Maryam Saleem; Abbas Ali Naseem; Waqar Ahmad; Muhammad Yaseen; Tehseen Ullah Khan (Carbonates and Evaporites, 2020)

First report of pepper leaf curl Bangladesh virus (PepLCBV) associated with cotton leaf curl Multan betasatellite on kidney bean (Phaseolus vulgaris) in Pakistan - Saleem Ur Rahman; Muhammad Zubair; Nasim Ahmed; Muhammad Zuhaib Khan; Ghulam Raza; Imran Amin; Shahid Mansoor (Journal of Plant Pathology, 2020)

Evaluation of in vivo anti-inflammatory and anti-angiogenic attributes of methanolic extract of Launaea spinosa - Muhammad Asif; Mahrukh; Malik Saadullah; Hafiza Sidra Yaseen; Mohammad Saleem; Hafiz Muhammad Yousaf; Ikram Ullah Khan; Maria Yaseen; Muhammad Usman Shams (Inflammopharmacology, 2020)

Investigating the potential of different jute varieties for phytoremediation of copper-contaminated soil - Muhammad Hamzah Saleem; Muzammal Rehman; Muhammad Kamran; Javaria Afzal; Hamza Armghan Noushahi; Lijun Liu (Environmental Science and Pollution Research, 2020)

Bioaccumulation of lead in different varieties of wheat plant irrigated with wastewater in remote agricultural regions - Wuyi Liu; Asma Zafar; Zafar Iqbal Khan; Muhammad Nadeem; Kafeel Ahmad; Kinza Wajid; Humayun Bashir; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq (Environmental Science and Pollution Research, 2020)

Spatial modeling of Dengue prevalence and kriging prediction of Dengue outbreak in Khyber Pakhtunkhwa (Pakistan) using presence only data - Hammad Ahmad; Asad Ali; Syeda Hira Fatima; Farrah Zaidi; Muhammad Khisroon; Syed Basit Rasheed; Ihsan Ullah; Saleem Ullah; Muhammad Shakir (Stochastic Environmental Research and Risk Assessment, 2020)

Application of Fluorescence Spectroscopy in Wheat Crop: Early Disease Detection and Associated Molecular Changes - Babar Manzoor Atta; Muhammad Saleem; Hina Ali; Muhammad Bilal; Muhammad Fayyaz (Journal of Fluorescence, 2020)

A study on the transfer of chromium from meadows to grazing livestock: an assessment of health risk - Zafar Iqbal Khan; Kafeel Ahmad; Samra Siddique; Tasneem Ahmad; Humayun Bashir; Mudasra Munir; Shahzadi Mahpara; Ifra Saleem Malik; Kinza Wajid; Ilker Ugulu; Muhammad Nadeem; Ijaz Rasool Noorka; et al. (Environmental Science and Pollution Research, 2020)

Cotton leaf curl Kokhran virus in association with Chili leaf curl betasatellite infecting mungbean (Vigna radiata.) and black gram (Vigna mungo.) in Pakistan - Saleem Ur Rahman; Muhammad Zubair; Nasim Ahmed; Ghulam Raza; Muhammad Zuhaib Khan; Shahid Mansoor; Imran Amin (Australasian Plant Pathology, 2020)

Urbanization and energy consumption effects on carbon dioxide emissions: evidence from Asian-8 countries using panel data analysis - Muhammad Ali Abbasi; Shabana Parveen; Saleem Khan; Muhammad Abdul Kamal (Environmental Science and Pollution Research, 2020)

A study on the seasonal transfer of two metals from pasture to animals: health risk assessment - Zafar Iqbal Khan; Mubeen Akhtar; Kafeel Ahmad; Asma Ashfaq; Muhammad Nadeem; Humayun Bashir; Mudasra Munir; Ifra Saleem Malik (Environmental Science and Pollution Research, 2020)

Exogenous Selenium-Instigated Physiochemical Transformations Impart Terminal Heat Tolerance in Bt Cotton - Muhammad Farrukh Saleem; Muhammad Asif Kamal; Muhammad Shahid; Amna Saleem; Amir Shakeel; Shakeel Ahmad Anjum (Journal of Soil Science and Plant Nutrition, 2020)

Approaches in Enhancing Thermotolerance in Plants: An Updated Review - Shafaqat Ali; Muhammad Rizwan; Muhammad Saleem Arif; Rehan Ahmad; Mirza Hasanuzzaman; Basharat Ali; Afzal Hussain (Journal of Plant Growth Regulation, 2020)

Testing the effect of different insecticides on Myzus persicae (Homoptera: Aphididae) in field mustard (Brassicae campestris L.) Czern for possible consideration in an IPM strategy - Muhammad Shahbaz Khan; Muhammad Faheem Akbar; Amjad Sultan; Muhammad Shoaib Saleem; Chand Gul (International Journal of Tropical Insect Science, 2020)

The role of garlic oil in the amelioration of oxidative stress and tissue damage in rohu Labeo rohita treated with silver nanoparticles - Muhammad Saleem Khan; Naureen Aziz Qureshi; Farhat Jabeen; Muhammad Wajid; Sabeen Sabri; Muhammad Shakir (Fisheries Science, 2020)

Urease inhibitory potential of extracts and active phytochemicals of Hypochaeris radicata (Asteraceae) - Tareq Abu-Izneid; Abdur Rauf; Muhammad Saleem; Nashwa Mansour; Mohamed I. S. Abdelhady; Munjed M. Ibrahim; Seema Patel (Natural Product Research, 2020)

Correction to: Moringa oleifera leaf extracts attenuate Complete Freund’s adjuvant-induced arthritis in Wistar rats via modulation of inflammatory and oxidative stress biomarkers - Ammara Saleem; Mohammad Saleem; Muhammad Furqan Akhtar; Muhammad Shahzad; Shah Jahan (Inflammopharmacology, 2020)

Moringa rivae leaf extracts attenuate Complete Freund’s adjuvant-induced arthritis in Wistar rats via modulation of inflammatory and oxidative stress biomarkers - Ammara Saleem; Mohammad Saleem; Muhammad Furqan Akhtar; Muhammad Shahzad; Shah Jahan (Inflammopharmacology, 2020)

Copper-induced oxidative stress, initiation of antioxidants and phytoremediation potential of flax (Linum usitatissimum L.) seedlings grown under the mixing of two different soils of China - Muhammad Hamzah Saleem; Shah Fahad; Shahid Ullah Khan; Mairaj Din; Abid Ullah; Ayman EL Sabagh; Akbar Hossain; Analía Llanes; Lijun Liu (Environmental Science and Pollution Research, 2020)

The role of financial development, energy demand, and technological change in environmental sustainability agenda: evidence from selected Asian countries - Hummera Saleem; Muhammad Bilal Khan; Malik Shahzad Shabbir (Environmental Science and Pollution Research, 2020)

Dynamics of AB-DTPA-extractable Zn in high and low limed calcareous soils amended with biochar and farmyard and poultry manures - Abida Saleem; Dost Muhammad; Mumtaz Khan; Qudrat Ullah Khan; Muhammad Rizwan; Salma Shaheen; Hamza Noor; Shiza Gul; Muhammad Daud Khan; Shafaqat Ali (Arabian Journal of Geosciences, 2020)

In-vitro and in-silico anticancer potential of taxoids from Taxus wallichiana Zucc - Mughal Qayum; Muhammad Nisar; Abdur Rauf; Imran Khan; Waqar Ahmad Kaleem; Muslim Raza; Nasiara Karim; Munawar Ahmad Saleem; Saud Bawazeer; Sengul Uysal; Gokhan Zengin; Saqib Jahan; et al. (Biologia Futura, 2020)
Introduction Natural products derived from medicinal plants provide beneficial cancer chemotherapeutic drugs. Bioactive constituents from plants are explored for their anticancer properties. Methods Three known compounds (deacetylbaccatin III, tasumatrol B, and taxawallin J) were isolated from Taxus wallichiana . Compounds were screened against four cancer cell lines, such as eA498, HepG2, NCI-H226, and MDR 2780AD. Cytotoxic activity was evaluated using MTT assay against cancer cell lines. Results Tasumatrol B showed good cytotoxic activity conducted for the improvement of inhibiting potential of these compounds against the cancer drug target protein (EGFR tyrosine kinase enzyme). The docking study showed that all compounds have binding affinities and interaction profile with the receptor tyrosine kinase. Discussion The study suggests that these compounds could be used for the discovery of novel inhibitors against the target receptors for the treatment of cancer.

Characterization of tomato mosaic virus and search for its resistance in Solanum species - Najeeb Ullah; Khalid Pervaiz Akhtar; Muhammad Yussouf Saleem; Mudasser Habib (European Journal of Plant Pathology, 2019)

Morphological changes and antioxidative capacity of jute (Corchorus capsularis, Malvaceae) under different color light-emitting diodes - Muhammad Hamzah Saleem; Muzammal Rehman; Muhammad Zahid; Muhammad Imran; Wei Xiang; Lijun Liu (Brazilian Journal of Botany, 2019)

Evaluation of tomato genotypes for early blight disease resistance caused by Alternaria solani in Pakistan - Khalid Pervaiz Akhtar; Najeeb Ullah; Muhammad Yussouf Saleem; Qumer Iqbal; Muhammad Asghar; Abdul Rehman Khan (Journal of Plant Pathology, 2019)

Nexus between financial development, energy consumption, income level, and ecological footprint in CEE countries: do human capital and biocapacity matter? - Shujah-ur-Rahman; Songsheng Chen; Shah Saud; Nyla Saleem; Muhammad Waseem Bari (Environmental Science and Pollution Research, 2019)

Zircon U-Pb dating, whole-rock and Sr-Nd isotope geochemistry of the Reshian granite gneiss of Indian Shield in Jhelum Valley, Lesser Himalayas (Azad Kashmir, Pakistan) - Dingding Du; Yanning Niu; Muhammad Saleem Mughal (Arabian Journal of Geosciences, 2019)

STATISTICAL DATA COLLECTION METHODOLOGIES OF IRRIGATED AREAS AND THEIR LIMITATIONS: A REVIEW - Ali Ajaz; Poolad Karimi; Xueliang Cai; Charlotte De Fraiture; Muhammad Saleem Akhter (Irrigation and Drainage, 2019)
Inconsistencies in the statistical data sets of irrigated areas at the national level could have considerable implications for policies developed for food and water security. Remote sensing can address this issue; however, doubts about its reliability inhibit its protagonist role. Methods that integrate both remote sensing based and statistical data sets seem expedient, and they are more likely to be acknowledged by policymakers. Therefore, it is important for scientists to know the basis and limitations of statistical data sets which originate at the country level. Data collection methodologies of irrigated areas have been reviewed for seven Asian countries, namely China, India, Pakistan, Bangladesh, Nepal, Indonesia and Thailand. Factors causing the uncertainties in data, and the limitations of data collection methodologies, were highlighted. Also, an irrigation density distribution analysis was conducted to understand the relation of spatial spread pattern of irrigated areas and uncertainty in their statistical records. It was found that irrigated area statistics are mostly based on information originating from water user associations and farmers, which is either self‐reported or collected through interviews during surveys and censuses. The main causes of discrepancy were lack of resources to frequently enumerate the irrigated land, inconsistency in data collection methodologies, unaccounted secondary crops, illegal and unregulated water use, and bureaucratic and political constraints. Irrigation density distribution analysis showed that largely scattered irrigated areas might be prone to a lack of comprehensive and frequent enumeration. Furthermore, dense irrigation regions might have potentially unrecorded irrigated areas where temporary or supplementary irrigation arrangements are made by marginal farmers. © 2019 John Wiley & Sons, Ltd.

Characterization of recombinant endo-1,4-β-xylanase of Bacillus halodurans C-125 and rational identification of hot spot amino acid residues responsible for enhancing thermostability by an in-silico approach - Malik Siddique Mahmood; Faiz Rasul; Mahjabeen Saleem; Amber Afroz; Muhammad Faheem Malik; Naeem Mehmood Ashraf; Umar Rashid; Shumaila Naz; Nadia Zeeshan (Molecular Biology Reports, 2019)

First report of cucumber mosaic virus subgroup IB and II isolates infecting tomatoes in Pakistan - Marium Anwer; Khalid P. Akhtar; Najeeb Ullah; Muhammad Y. Saleem; Hafiza Massoma Naseer Cheema (Journal of Plant Pathology, 2019)

Financial development and its moderating role in environmental Kuznets curve: evidence from Pakistan - Shujah-ur-Rahman; Songsheng Chen; Nyla Saleem; Muhammad Waseem Bari (Environmental Science and Pollution Research, 2019)

Comparison of dynamical and statistical rainfall downscaling of CMIP5 ensembles at a small urban catchment scale - Muhammad Saleem Akhter; Asaad Yahia Shamseldin; Bruce William Melville (Stochastic Environmental Research and Risk Assessment, 2019)

Copper environmental toxicology, recent advances, and future outlook: a review - Muzammal Rehman; Lijun Liu; Qin Wang; Muhammad Hamzah Saleem; Saqib Bashir; Sana Ullah; Dingxiang Peng (Environmental Science and Pollution Research, 2019)

Evaluation of Potential Toxic Metals Accumulation in Wheat Irrigated with Wastewater - Kafeel Ahmad; Kinza Wajid; Zafar Iqbal Khan; Ilker Ugulu; Hafsa Memoona; Madiha Sana; Khalid Nawaz; Ifra Saleem Malik; Humayun Bashir; Muhammad Sher (Bulletin of Environmental Contamination and Toxicology, 2019)

Socio-economic and environmental factors influenced the United Nations healthcare sustainable agenda: evidence from a panel of selected Asian and African countries - Hummera Saleem; Wen Jiandong; Abdullah Mohammed Aldakhil; Abdelmohsen A. Nassani; Muhammad Moinuddin Qazi Abro; Khalid Zaman; Aqeel Khan; Zainudin Bin Hassan; Mohd Rustam Mohd Rameli (Environmental Science and Pollution Research, 2019)

High intrinsic seed Zn concentration improves abiotic stress tolerance in wheat - Muhammad Faran; Muhammad Farooq; Abdul Rehman; Ahmad Nawaz; Muhammad Kamran Saleem; Nauman Ali; Kadambot H. M. Siddique (Plant and Soil, 2019)

Chemical characterisation and hepatoprotective potential of Cosmos sulphureus Cav. and Cosmos bipinnatus Cav. - Mohammad Saleem; Hafiz Akbar Ali; Muhammad Furqan Akhtar; Uzma Saleem; Ammara Saleem; Iram Irshad (Natural Product Research, 2019)

Assessment of Circulating Biochemical Markers in Mice Receiving Cinnamon and Glycyrrhizin Under Carbon Tetrachloride Induced Hepatic Injury - Mahmood Rasool; Arif Malik; Sadia Saleem; Shakeel Ahmed Ansari; Javed Iqbal; Muhammad Asif; Mohammed Amjad Kamal; Mohammed Hussain Al-Qahtani; Sajjad Karim (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Exogenous Potassium–Instigated Biochemical Regulations Confer Terminal Heat Tolerance in Wheat - Muhammad Shahid; Muhammad Farrukh Saleem; Amna Saleem; Muhammad Aown Sammar Raza; Muhammad Kashif; Abdul Shakoor; Muhammad Sarwar (Journal of Soil Science and Plant Nutrition, 2019)

Thermal Effects on Biochemical Signatures of UHT, Pasteurized and Domestically Boiled Buffalo Milk Detected by Synchronous Fluorescence Spectroscopy - Hina Ali; Muhammad Saleem; Rahat Ullah; Saranjam Khan; Babar Manzoor Atta; Muhammad Bilal (Journal of Fluorescence, 2019)

Endocrine disruption as an adverse effect of non-endocrine targeting pharmaceuticals - Shakila Sabir; Muhammad Furqan Akhtar; Ammara Saleem (Environmental Science and Pollution Research, 2019)

Tattooing trend: major cause of HCV transmission among youngsters - Braira Wahid; Komal Saleem; Nouman Rasool; Shazia Rafique; Amjad Ali; Muhammad Waqar; Muhammad Idrees (Infectious Diseases, 2018)

5-Aminolevulinic Acid-Induced Heavy Metal Stress Tolerance and Underlying Mechanisms in Plants - Shafaqat Ali; Muhammad Rizwan; Abbu Zaid; Muhammad Saleem Arif; Tahira Yasmeen; Afzal Hussain; Muhammad Rizwan Shahid; Syed Asad Hussain Bukhari; Saddam Hussain; Ghulam Hassan Abbasi (Journal of Plant Growth Regulation, 2018)

Ameliorative Effects of Selenium in ZnO NP-Induced Oxidative Stress and Hematological Alterations in Catla catla - Muhammad Saleem Asghar; Naureen Aziz Qureshi; Farhat Jabeen; Muhammad Saleem Khan; Muhammad Shakeel; Abdul Shakoor Chaudhry (Biological Trace Element Research, 2018)

Petrography, geochemistry and provenance of the sediments of the Early Cretaceous Yanguoxia Formation, Lanzhou-Minhe Basin, Northwest China - Ding-ding Du; Muhammad Saleem Mughal; Cheng-jun Zhang (Journal of Mountain Science, 2018)

Oxyphenbutazone promotes cytotoxicity in rats and Hep3B cellsvia suppression of PGE2 and deactivation of Wnt/β-catenin signaling pathway - Shakir Saleem; Ruqaiyah Khan; Muhammad Afzal; Imran Kazmi (Molecular and Cellular Biochemistry, 2018)

Influence of composted poultry manure and irrigation regimes on some morpho-physiology parameters of maize under semiarid environments - Wajid Farhad; Mumtaz Akhtar Cheema; Hafiz Mohkum Hammad; Muhammad Farrukh Saleem; Shah Fahad; Farhat Abbas; Ikramullah Khosa; Hafiz Faiq Bakhat (Environmental Science and Pollution Research, 2018)

Potential impacts of climate change and adaptation strategies for sunflower in Pakistan - Muhammad Awais; Aftab Wajid; Muhammad Farrukh Saleem; Wajid Nasim; Ashfaq Ahmad; Muhammad Aown Sammar Raza; Muhammad Usman Bashir; Muhammad Mubeen; Hafiz Mohkum Hammad; Muhammad Habib ur Rahman; Umer Saeed; Muhammad Naveed Arshad; et al. (Environmental Science and Pollution Research, 2018)

Determination of the role of salicylic acid and Benzothiadiazole on physico-chemical alterations caused by Cucumber mosaic virus in tomato - Rana M. Sabir Tariq; Khalid P. Akhtar; Amjad Hameed; Najeeb Ullah; Muhammad Y. Saleem; Imran ul Haq (European Journal of Plant Pathology, 2018)

Spatial modeling of rat bites and prediction of rat infestation in Peshawar valley using binomial kriging with logistic regression - Asad Ali; Farrah Zaidi; Syeda Hira Fatima; Muhammad Adnan; Saleem Ullah (Environmental Monitoring and Assessment, 2018)

Association of textile industry effluent with mutagenicity and its toxic health implications upon acute and sub-chronic exposure - Muhammad Furqan Akhtar; Muhammad Ashraf; Aqeel Javeed; Aftab Ahmad Anjum; Ali Sharif; Mohammad Saleem; Ghulam Mustafa; Moneeb Ashraf; Ammara Saleem; Bushra Akhtar (Environmental Monitoring and Assessment, 2018)

RETRACTED ARTICLE: Assessment of Waterborne Amine-Coated Silver Nanoparticle (Ag-NP)-Induced Toxicity in Labeo rohita by Histological and Hematological Profiles - Muhammad Saleem Khan; Naureen Aziz Qureshi; Farhat Jabeen; Muhammad Shakeel; Muhammad Saleem Asghar (Biological Trace Element Research, 2018)

RETRACTED ARTICLE: Assessment of Titanium Dioxide Nanoparticles (TiO2-NPs) Induced Hepatotoxicity and Ameliorative Effects of Cinnamomum cassia in Sprague-Dawley Rats - Muhammad Shakeel; Farhat Jabeen; Rehana Iqbal; Abdul Shakoor Chaudhry; Sadia Zafar; Muhammad Ali; Muhammad Saleem Khan; Adeel Khalid; Samina Shabbir; Muhammad Saleem Asghar (Biological Trace Element Research, 2018)

Detrital apatite fission track constraints on Cenozoic tectonic evolution of the northeastern Qinghai-Tibet Plateau, China: Evidence from Cenozoic strata in Lulehe section, Northern Qaidam Basin - Ding-ding Du; Cheng-jun Zhang; Muhammad Saleem Mughal; Xiao-yu Wang; Dembele Blaise; Jun-ping Gao; Yuan Ma; Xin-rong Luo (Journal of Mountain Science, 2018)

Application of gravity and magnetic methods for the crustal study and delineating associated ores in the western limb of Hazara Kashmir Syntaxis, Northwest Himalayas, Pakistan - Muhammad Rustam Khan; Shahid Saleem Bilali; Fahad Hameed; Awais Rabnawaz; Sohail Mustafa; Naveed Azad; Muhammad Basharat; Abrar Niaz (Arabian Journal of Geosciences, 2018)

Prevailing trends of climatic extremes across Indus-Delta of Sindh-Pakistan - Farhat Abbas; Iqra Rehman; Muhammad Adrees; Muhammad Ibrahim; Farhan Saleem; Shafaqat Ali; Muhammad Rizwan; Muhammad Raza Salik (Theoretical and Applied Climatology, 2018)

PAAN135, a novel rhizospheric fungus associated with Cholistan desert grass Panicum antidotale, is a species of Saccharomycetales and a new source of cyclo-L-prolylglycine diketopiperazine - Faiz-ul-Hassan Nasim; Adeela Naureen; Muhammad Saleem; Naheed Riaz; Muhammad Shafiq Choudhary; Muhammad Ashraf (Symbiosis, 2018)

Regional climate assessment of precipitation and temperature in Southern Punjab (Pakistan) using SimCLIM climate model for different temporal scales - Asad Amin; Wajid Nasim; Muhammad Mubeen; Saleem Sarwar; Peter Urich; Ashfaq Ahmad; Aftab Wajid; Tasneem Khaliq; Fahd Rasul; Hafiz Mohkum Hammad; Muhammad Ishaq Asif Rehmani; Hussani Mubarak; et al. (Theoretical and Applied Climatology, 2018)

A Brief Review on Fluorescent Copper Sensor Based on Conjugated Organic Dyes - Muhammad Saleem; Muhammad Rafiq; Muhammad Hanif; Muhammad Ashraf Shaheen; Sung-Yum Seo (Journal of Fluorescence, 2018)

Regenerative Potential of Platelet Rich Fibrin (PRF) for Curing Intrabony Periodontal Defects: A Systematic Review of Clinical Studies - Shariq Najeeb; Zohaib Khurshid; Muhammad Atif Saleem Agwan; Shazia Akhbar Ansari; Muhammad Sohail Zafar; Jukka Pekka Matinlinna (Tissue Engineering and Regenerative Medicine, 2017)

3D graphene-based nanostructured materials as sorbents for cleaning oil spills and for the removal of dyes and miscellaneous pollutants present in water - Muhammad Adil Riaz; Gordon McKay; Junaid Saleem (Environmental Science and Pollution Research, 2017)

Petrography, provenance, diaganesis and depositional environment of Murree Formation in Jhelum Valley, Sub Himalayas, Azad Jammu and Kashmir, Pakistan - Muhammad Zaheer; Muhammad Sabir Khan; Muhammad Saleem Mughal; Noman Abbasi (Arabian Journal of Geosciences, 2017)

Pseudomonas syringae pv. tomato DC3000 growth in multiple gene knockouts predicts interactions among hormonal, biotic and abiotic stress responses - Muhammad Saleem; Hao Ji; Amalina Amirullah; Milton Brian Traw (European Journal of Plant Pathology, 2017)

Association of chili leaf curl betasatellite with tomato leaf curl disease - Muhammad Qasim Aslam; Khalid P. Akhtar; Mohy-u-Din Akram; Muhammad Y. Saleem; Nighat Sarwar; Sumaira Yousaf (Journal of General Plant Pathology, 2017)

Nitrogen and plant population change radiation capture and utilization capacity of sunflower in semi-arid environment - Muhammad Awais; Aftab Wajid; Muhammad Usman Bashir; Muhammad Habib-ur-Rahman; Muhammad Aown Sammar Raza; Ashfaq Ahmad; Muhammad Farrukh Saleem; Hafiz Mohkum Hammad; Muhammad Mubeen; Umer Saeed; Muhammad Naveed Arshad; Shah Fahad; et al. (Environmental Science and Pollution Research, 2017)

Biochar soil amendment on alleviation of drought and salt stress in plants: a critical review - Shafaqat Ali; Muhammad Rizwan; Muhammad Farooq Qayyum; Yong Sik Ok; Muhammad Ibrahim; Muhammad Riaz; Muhammad Saleem Arif; Farhan Hafeez; Mohammad I. Al-Wabel; Ahmad Naeem Shahzad (Environmental Science and Pollution Research, 2017)

Eco-Friendly Synthesis of Silver Nanoparticles Through Economical Methods and Assessment of Toxicity Through Oxidative Stress Analysis in the Labeo Rohita - Muhammad Saleem Khan; Naureen Aziz Qureshi; Farhat Jabeen; Muhammad Saleem Asghar; Muhammad Shakeel; Muhammad Fakhar -e -Alam (Biological Trace Element Research, 2017)

Pathogenic diversity of Xanthomonas oryzae pv. oryzae isolates collected from Punjab Province of Pakistan - Hafiz Muhammad Imran Arshad; Kamran Saleem; Junaid Ahmed Khan; Muhammad Rashid; Muhammad Atiq; Syed Sarwar Alam; Shahbaz Talib Sahi (European Journal of Plant Pathology, 2017)

Low C/N ratio raw textile wastewater reduced labile C and enhanced organic-inorganic N and enzymatic activities in a semiarid alkaline soil - Mahnaz Roohi; Muhammad Riaz; Muhammad Saleem Arif; Sher Muhammad Shahzad; Tahira Yasmeen; Muhammad Arslan Ashraf; Muhammad Atif Riaz; Ishaq A. Mian (Environmental Science and Pollution Research, 2017)

Organic Material Based Fluorescent Sensor for Hg2+: a Brief Review on Recent Development - Muhammad Saleem; Muhammad Rafiq; Muhammad Hanif (Journal of Fluorescence, 2017)

Tourism in Austria: biodiversity, environmental sustainability, and growth issues - Muhammad Asad Saleem Malik; Syed Asim Shah; Khalid Zaman (Environmental Science and Pollution Research, 2016)

Oxidative stress responses in Wistar rats on subacute exposure to pharmaceutical wastewater - Ali Sharif; Muhammad Ashraf; Aqeel Javeed; Aftab Ahmed Anjum; Muhammad Furqan Akhtar; Bushra Akhtar; Ammara Saleem (Environmental Science and Pollution Research, 2016)

Tectonic study of the Sub-Himalayas based on geophysical data in Azad Jammu and Kashmir and northern Pakistan - Muhammad Rustam Khan; Fahad Hameed; Muhammad Saleem Mughal; Muhammad Basharat; Sohail Mustafa (Journal of Earth Science, 2016)

Comparison of antioxidant enzyme activities and DNA damage in chickpea (Cicer arietinum L.) genotypes exposed to vanadium - Muhammad Imtiaz; Muhammad Adnan Mushtaq; Muhammad Shahid Rizwan; Muhammad Saleem Arif; Balal Yousaf; Muhammad Ashraf; Xiong Shuanglian; Muhammad Rizwan; Sajid Mehmood; Shuxin Tu (Environmental Science and Pollution Research, 2016)

Aluminum and Chromium Toxicity in Maize: Implications for Agronomic Attributes, Net Photosynthesis, Physio-Biochemical Oscillations, and Metal Accumulation in Different Plant Parts - Shakeel Ahmad Anjum; Umair Ashraf; Imran Khan; Mohsin Tanveer; Muhammad Farrukh Saleem; Longchang Wang (Water, Air, & Soil Pollution, 2016)

New lipoxygenase and cholinesterase inhibitory sphingolipids from Carthamus oxyacantha - Muhammad Dilshad; Naheed Riaz; Muhammad Saleem; Nusrat Shafiq; Muhammad Ashraf; Tayaba Ismail; Hafiza Mehwish Rafiq; Abdul Jabbar (Natural Product Research, 2016)

Toxicity of Nano-Titanium Dioxide (TiO2-NP) Through Various Routes of Exposure: a Review - Muhammad Shakeel; Farhat Jabeen; Samina Shabbir; Muhammad Saleem Asghar; Muhammad Saleem Khan; Abdul Shakoor Chaudhry (Biological Trace Element Research, 2016)

Osmoregulation and antioxidant production in maize under combined cadmium and arsenic stress - Shakeel Ahmad Anjum; Mohsin Tanveer; Saddam Hussain; Babar Shahzad; Umair Ashraf; Shah Fahad; Waseem Hassan; Saad Jan; Imran Khan; Muhammad Farrukh Saleem; Ali Ahsan Bajwa; Longchang Wang; et al. (Environmental Science and Pollution Research, 2016)

Petrology and geochemistry of Jura granite and granite gneiss in the Neelum Valley, Lesser Himalayas (Kashmir, Pakistan) - Muhammad Saleem Mughal; Muhammad Sabir Khan; Muhammad Rustam Khan; Sohail Mustafa; Fahad Hameed; Muhammad Basharat; Abrar Niaz (Arabian Journal of Geosciences, 2016)

Geochemistry and petrology of Late Miocene-Pleistocene Dibdibba sandstone formation in south and central Iraq: implications for provenance and depositional setting - Salih Muhammad Awadh; Zinah Saleem Al-Ankaz (Arabian Journal of Geosciences, 2016)

Gaseous pollutants from brick kiln industry decreased the growth, photosynthesis, and yield of wheat (Triticum aestivum L.) - Muhammad Adrees; Muhammad Ibrahim; Aamir Mehmood Shah; Farhat Abbas; Farhan Saleem; Muhammad Rizwan; Saadia Hina; Fariha Jabeen; Shafaqat Ali (Environmental Monitoring and Assessment, 2016)

Sediment yield assessment and identification of check dam sites for Rawal Dam catchment - Nida Samad; Muhammad Hamid Chauhdry; Muhammad Ashraf; Muhammad Saleem; Qudsia Hamid; Umair Babar; Hassan Tariq; Muhammad Shahid Farid (Arabian Journal of Geosciences, 2016)

Phytochemistry of Daphne oleoides - Muhammad Riaz; Asma Saleem; Shabana Siddique; Bilal Ahmad Khan; Mohammad Nur-e-Alam; Syed Shahzad-ul-Hussan; Ghulam Abbas Miana; Muhammad Qayyum Khan (Natural Product Research, 2016)

Toxicity Appraisal of Untreated Dyeing Industry Wastewater Based on Chemical Characterization and Short Term Bioassays - Muhammad Furqan Akhtar; Muhammad Ashraf; Aqeel Javeed; Aftab Ahmad Anjum; Ali Sharif; Ammara Saleem; Bushra Akhtar; Abdul Muqeet Khan; Imran Altaf (Bulletin of Environmental Contamination and Toxicology, 2016)

Benzamide sulfonamide derivatives: potent inhibitors of carbonic anhydrase-II - Muhammad Saleem; Aamer Saeed; Atia-tul-Wahab; Ajmal Khan; Sanaullah Abbasi; Waqasuddin Khan; Sher Bahadar Khan; M. Iqbal Choudhary (Medicinal Chemistry Research, 2016)

Contrasting effects of untreated textile wastewater onto the soil available nitrogen-phosphorus and enzymatic activities in aridisol - Muhammad Saleem Arif; Muhammad Riaz; Sher Muhammad Shahzad; Tahira Yasmeen; Alexandre Buttler; Juan Carlos Garcıa-Gil; Mahnaz Roohi; Akhtar Rasool (Environmental Monitoring and Assessment, 2016)

Pharmaceutical wastewater being composite mixture of environmental pollutants may be associated with mutagenicity and genotoxicity - Ali Sharif; Muhammad Ashraf; Aftab Ahmed Anjum; Aqeel Javeed; Imran Altaf; Muhammad Furqan Akhtar; Mateen Abbas; Bushra Akhtar; Ammara Saleem (Environmental Science and Pollution Research, 2016)

Chromo/Fluorogenic Detection of Co2+, Hg2+ and Cu2+ by the Simple Schiff Base Sensor - Muhammad Saleem; Chung Ho Khang; Moon-Hwan kim; Ki Hwan Lee (Journal of Fluorescence, 2016)

Copper-resistant bacteria reduces oxidative stress and uptake of copper in lentil plants: potential for bacterial bioremediation - Faisal Islam; Tahira Yasmeen; Qasim Ali; Muhammad Mubin; Shafaqat Ali; Muhammad Saleem Arif; Sabir Hussain; Muhammad Riaz; Farhat Abbas (Environmental Science and Pollution Research, 2016)

Spatial distribution of pollutant emissions from crop residue burning in the Punjab and Sindh provinces of Pakistan: uncertainties and challenges - Muhammad Irfan; Muhammad Riaz; Muhammad Saleem Arif; Sher Muhammad Shahzad; Sabir Hussain; Muhammad Javed Akhtar; Leon van den Berg; Farhat Abbas (Environmental Science and Pollution Research, 2015)

Geotechnical study of marble, schist, and granite as dimension stone: a case study from parts of Lesser Himalaya, Neelum Valley Area, Azad Kashmir, Pakistan - Sohail Mustafa; Muhammad Arshad Khan; Muhammad Rustam Khan; Fahad Hameed; Muhammad Saleem Mughal; Aamir Asghar; Abrar Niaz (Bulletin of Engineering Geology and the Environment, 2015)

Bioanalytical evaluation of Cinnamomum zeylanicum essential oil - Muhammad Saleem; Haq Nawaz Bhatti; Muhammad Idrees Jilani; Muhammad Asif Hanif (Natural Product Research, 2015)

Baseline susceptibility and resistance stability of Earias vittella fabricius (Lepidoptera: Noctuidae) to cypermethrin, deltamethrin and spinosad - Muhammad Tahir Jan; Naeem Abbas; Sarfraz Ali Shad; Muhammad Rafiq; Mushtaq Ahmad Saleem (Phytoparasitica, 2015)

Genetics and mechanism of resistance to deltamethrin in the house fly, Musca domestica L., from Pakistan - Hafiz Azhar Ali Khan; Waseem Akram; Muhammad Saleem Haider (Ecotoxicology, 2015)

Gibberellic acid in combination with pressmud enhances the growth of sunflower and stabilizes chromium(VI)-contaminated soil - Muhammad Saleem; Hafiz Naeem Asghar; Muhammad Yahya Khan; Zahir Ahmad Zahir (Environmental Science and Pollution Research, 2015)

Synthesis, Characterization and Photophysical Properties of Novel Azole Derivatives - Muhammad Saleem; Ki Hwan Lee (Journal of Fluorescence, 2015)

Optical Properties of Some Novel 2,5-Disubstituted 1,3,4-Oxadiazole Derivatives and their Application as an Efficient Cell Staining Azo Dyes - Muhammad Saleem; Anser Ali; Bong Joo Park; Eun Ha Choi; Ki Hwan Lee (Journal of Fluorescence, 2014)

The Smart 2-(2-Fluorobenzoyl)-N-(2-Methoxyphenyl)Hydrazinecarbothioamide Functionalized as Ni(II) Sensor in Micromolar Concentration Level and its Application in Live Cell Imaging - Muhammad Saleem; Anser Ali; Chang-Shik Choi; Bong Joo Park; Eun Ha Choi; Ki Hwan Lee (Journal of Fluorescence, 2014)

A distinct strain of chickpea chlorotic dwarf virus (genus Mastrevirus, family Geminiviridae) identified in cotton plants affected by leaf curl disease - Muhammad Tariq Manzoor; Muhammad Ilyas; Muhammad Shafiq; Muhammad Saleem Haider; Ahmad Ali Shahid; Rob W. Briddon (Archives of Virology, 2014)

Co-inoculation integrated with P-enriched compost improved nodulation and growth of Chickpea (Cicer arietinum L.) under irrigated and rainfed farming systems - Sher Muhammad Shahzad; Azeem Khalid; Muhammad Saleem Arif; Muhammad Riaz; Muhammad Ashraf; Zafar Iqbal; Tahira Yasmeen (Biology and Fertility of Soils, 2014)

Chemical and physical control processes on the development of caves in the Injana Formation, Central Iraq - Salih Muhammad Awadh; Zenah Saleem Abood; Murtadha Jabar Eisa (Arabian Journal of Geosciences, 2013)

Two new triterpenes from Alstonia scholaris flowers - Nighat Sultana; Zafar Saeed Saify; Muhammad Saleem; Mustafa Kamal (Natural Product Research, 2013)

Complete nucleotide sequences of two begomoviruses infecting Madagascar periwinkle (Catharanthus roseus) from Pakistan - Muhammad Ilyas; Kiran Nawaz; Muhammad Shafiq; Muhammad Saleem Haider; Ahmad Ali Shahid (Archives of Virology, 2013)

Effect of management on reproductive performances of the Achai cattle in the Hindu Kush (Northern Pakistan) - Muhammad Saleem; Inam-ur Rahim; Henri Rueff; Momen Khan; Daniel Maselli; Urs Wiesmann; Sher Muhammad (Tropical Animal Health and Production, 2012)

Field evolved resistance to carbamates, organophosphates, pyrethroids, and new chemistry insecticides in Spodoptera litura Fab. (Lepidoptera: Noctuidae) - Sarfraz Ali Shad; Ali H. Sayyed; Sahar Fazal; Mushtaq A. Saleem; Syed Muhammad Zaka; Muhammad Ali (Journal of Pest Science, 2012)

Characterization of a thermostable and alkaline xylanase from Bacillus sp. and its bleaching impact on wheat straw pulp - Mahjabeen Saleem; Farheen Aslam; Muhammad Saleem Akhtar; Mohsin Tariq; Muhammad Ibrahim Rajoka (World Journal of Microbiology and Biotechnology, 2012)

Granzyme M: characterization with sites of post-translational modification and specific sites of interaction with substrates and inhibitors - Rukhshan Khurshid; Mahjabeen Saleem; Muhammad Saleem Akhtar; Asmat Salim (Molecular Biology Reports, 2011)

Overexpression of the phytochrome B gene from Arabidopsis thaliana increases plant growth and yield of cotton (Gossypium hirsutum) - Abdul Qayyum Rao; Muhammad Irfan; Zafar Saleem; Idrees Ahmad Nasir; Sheikh Riazuddin; Tayyab Husnain (Journal of Zhejiang University-SCIENCE B, 2011)

Resistance of Solanum species to Cucumber mosaic virus subgroup IA and its vector Myzus persicae - Khalid Pervaiz Akhtar; Muhmmad Yussouf Saleem; Muhammad Asghar; Mushtaq Ahmad; Nighat Sarwar (European Journal of Plant Pathology, 2010)

Study of heritable variation and genetics of earliness in mungbean (Vigna radiata L. Wilczek) - Aziz ur Rehman; Muhammad Amjad Ali; Muhammad Saleem; W. Tadesse (Euphytica, 2010)

Serum Electrolyte and Mineral Variations During Pregnancy and Lactation in Nili-Ravi Buffalo - M. Saleem Akhtar; Abdul Asim Farooq; Syed Aun Muhammad; Laeeq Akbar Lodhi; C. Sikandar Hayat; M. Mushtaq Aziz (Biological Trace Element Research, 2010)

Complete nucleotide sequences of a distinct bipartite begomovirus, bitter gourd yellow vein virus, infecting Momordica charantia - Muhammad Tahir; Muhammad Saleem Haider; Rob W. Briddon (Archives of Virology, 2010)

Correlative evidence for peroxidase involvement in disease resistance against Alternaria leaf blight of tomato - Amjad Hameed; Khalid Pervaiz Akhtar; Muhammad Yussouf Saleem; Muhammad Asghar (Acta Physiologiae Plantarum, 2010)

Measurement of soil radioactivity levels and radiation hazard assessment in southern Rechna interfluvial region, Pakistan - Abdul Jabbar; Waheed Arshed; Arshad Saleem Bhatti; Syed Salman Ahmad; Perveen Akhter; Saeed -Ur -Rehman; Muhammad Iftikhar Anjum (Environmental Monitoring and Assessment, 2010)

Synthesis of Novel Fluorescent Cyclohexenone Derivatives and their Partitioning Study in Ionic Micellar Media - Amir Badshah; Saleem Nawaz; Muhammad Faizan Nazar; Syed Sakhawat Shah; Aurangzeb Hasan (Journal of Fluorescence, 2010)

Cytology of infection of Fusarium mangiferae Britz in different malformed reproductive parts of mango - Zafar Iqbal; Sohail Hameed; Muhammad Akbar Anjum; Altaf Ahmad Dasti; Ahmad Saleem (European Journal of Plant Pathology, 2010)

Surface properties and sub-surface aggregate assimilation of rhamnolipid surfactants in different aqueous systems - Zulfiqar Ali Raza; Zafar M. Khalid; Mohammad Saleem Khan; Ibrahim M. Banat; Asma Rehman; Abdul Naeem; Muhammad Tahir Saddique (Biotechnology Letters, 2010)

Pre and post cloning characterization of a β-1,4-endoglucanase from Bacillus sp. - Sumra Afzal; Mahjabeen Saleem; Riffat Yasmin; Mamoona Naz; Muhammad Imran (Molecular Biology Reports, 2010)

Bioremediation and Phytoremediation of Pesticides: Recent Advances - Sarfraz Hussain; Tariq Siddique; Muhammad Arshad; Muhammad Saleem (Critical Reviews in Environmental Science and Technology, 2009)

Concentration dependent growth/non-growth linked kinetics of endosulfan biodegradation by Pseudomonas aeruginosa - Sarfraz Hussain; Muhammad Arshad; Baby Shaharoona; Muhammad Saleem; Azeem Khalid (World Journal of Microbiology and Biotechnology, 2009)

Epidermal growth factor receptors: function modulation by phosphorylation and glycosylation interplay - Afshan Kaleem; Ishtiaq Ahmad; Daniel C. Hoessli; Evelyne Walker-Nasir; Muhammad Saleem; Abdul Rauf Shakoori; Nasir-ud-Din (Molecular Biology Reports, 2009)

Solid-state fermentation-supported enhanced production of α-galactosidase by a deoxyglucose-resistant mutant of Aspergillus niger and thermostabilization of the production process - Muhammad Ibrahim Rajoka; Muhammad Siddique Awan; Mahjabeen Saleem; Najma Ayub (World Journal of Microbiology and Biotechnology, 2009)

Biodegradation of α- and β-endosulfan by soil bacteria - Sarfraz Hussain; Muhammad Arshad; Muhammad Saleem; Azeem Khalid (Biodegradation, 2007)

Contribution of cultivated crops, vegetables, weeds and ornamental plants in harboring of Bemisia tabaci (Homoptera: Aleyrodidae) and associated parasitoids (Hymenoptera: Aphelinidae) in cotton agroecosystem in Pakistan - Muhammad Naveed; Abdus Salam; Mushtaq Ahmad Saleem (Journal of Pest Science, 2007)

Some new prospects in the understanding of the molecular basis of the pathogenesis of stroke - Sheikh Arshad Saeed; Kaneez Fatima Shad; Taimur Saleem; Faisal Javed; Muhammad Umair Khan (Experimental Brain Research, 2007)

Screening of soil fungi for in vitro degradation of endosulfan - Sarfraz Hussain; Muhammad Arshad; Muhammad Saleem; Zahir Ahmad Zahir (World Journal of Microbiology and Biotechnology, 2007)

Improved production of biosurfactant by a Pseudomonas aeruginosa mutant using vegetable oil refinery wastes - Zulfiqar Ali Raza; Asma Rehman; Muhammad Saleem Khan; Zafar M. Khalid (Biodegradation, 2006)

Production Kinetics and Tensioactive Characteristics of Biosurfactant from a Pseudomonas aeruginosa Mutant Grown on Waste Frying Oils - Zulfiqar Ali Raza; Muhammad Saleem Khan; Zafar M. Khalid; Asma Rehman (Biotechnology Letters, 2006)

Longifoamide-A and B: Two new ceramides from Mentha longifolia (Lamiaceae) - Muhammad Shaiq Ali; Waqar Ahmed; Muhammad Saleem; Taous Khan (Natural Product Research, 2006)

Longifoside-A and -B: Two new cerebrosides from Mentha longifolia (Lamiaceae) - Muhammad Shaiq Ali; Waqar Ahmed; Muhammad Saleem; Mohammad Ashfaq Ali (Natural Product Research, 2006)

Purification and Characterization of a Xylanase Produced by Chaetomium thermophile NIBGE - Farooq Latif; Muhammad Asgher; Rabia Saleem; Ahmed Akrem; R. L. Legge (World Journal of Microbiology and Biotechnology, 2006)

Irrigation management turnover: an option for improved utilization of limited water resources in Pakistan - Muhammad Latif; Muhammad Saleem Pomee (Irrigation and Drainage, 2003)
Underperformance of the irrigation systems and poor cost recovery from irrigated area in Pakistan have been a source of concern for the last few decades and since then it has been the subject of considerable external assistance and internal policy reforms. To address these problems in the management of irrigation systems, the World Bank proposed a number of institutional changes for irrigation management turnover (IMT). After thorough consideration it was decided to decentralize instead of privatizing the irrigation system management and to promote farmers' participation in the system management. Under these reforms, management at secondary canal level has recently been handed over to the farmers' organizations (FOs) of selected distributaries at a pilot scale. This study was designed to evaluate the farmer‐managed distributary in southern Punjab. Initial field measurements revealed that hydraulic aspects of the irrigation service delivered by the FO management have been significantly improved and as a result a highly proportionate and equitable water distribution pattern was observed, particularly at the tail reaches of the distributary during the post‐transfer scenario. Due to effective FO management farmers' interventions to increase the outlet discharge by illegal means have almost ceased. As a result of these improvements made by the FO in system management the extent of irrigated area has on average increased by 6–7% even under severe drought and continued famine‐like conditions prevailing in the country during recent years. Most importantly, cost recoveries have increased by an amount of 14% for summer and 23% for winter growing seasons respectively from the irrigated area of the distributary. Thus experience from the Hakra 4‐R distributary has shown that even under undesirable natural circumstances IMT was quite effective in achieving the key targets of the institutional reforms launched at pilot scale in the country. Copyright © 2003 John Wiley & Sons, Ltd.